Co-designed nanozyme-polymer antimicrobial films for sustainable active food packaging: Interfacial regulation and food-matrix applications - Yue Hu; Hongbin Pu; Da-Wen Sun (Trends in Food Science & Technology, 2026)

Phylogenomics of Tanypodinae (Diptera: Chironomidae) redefines relationships in Procladiini and Tanypodini and supports a new tribe - Xiu-Ru Xiao; Yi-Ni Zhang; Hai-Feng Xu; Zhi-Chao Zhang; Yu-Yi Jiang; Yan-Xin Chen; Chen-Hong Li; Bing-Jiao Sun; Fabio Laurindo da Silva; Xiao-Long Lin (Molecular Phylogenetics and Evolution, 2026)

Stage-dependent dual effects of folic acid in esophageal squamous cell carcinogenesis: precancerous lesions as a potential transition point - Niannian Wang; Da Pan; Xingyuan Ren; Shiyun Wan; Huan Zhang; Xiangjun Chen; Shaokang Wang; Guiju Sun (Food Research International, 2026)

An enhanced YOLO-based deep learning framework for automated structural defect inspection in complex backgrounds - Zheyu Liu; Di Su; Youqi Zhang; Da-Wei Lin; Zhen Sun (Engineering Structures, 2026)

Lateral impact performance of concrete-encased concrete-filled steel tubular (CECFST) members after exposure to fire: Tests and analysis - Yuan Zheng; Wen-Da Wang; Sun-Hang Ji; Yan-Li Shi; Wei Xian; Rui Wang (Engineering Structures, 2026)

Novel multimodal data fusion strategies for nondestructive real-time monitoring of guava quality during storage - Jingxiao Yu; Zongxin Liu; Hongbin Pu; Da-Wen Sun (Postharvest Biology and Technology, 2026)

Hybrid cultured meat as an integrated food production system: Recent advances and commercialization challenges - ChanJin Kim; SoHee Kim; Da Young Lee; Ermie Mariano; SiHoon An; Young-Hwa Hwang; Sun Jin Hur; Seon-Tea Joo (Food Research International, 2026)

Thermodynamic compatibility and conformational adaptability enable the matrix-adaptive protection of glycated pea protein isolate-curcumin nanoparticles in frying oils - Zhi-feng Tan; Cong Sun; Shi-hui Zhao; Zhen-wen Shao; Da-yong Zhou; Liang Song (Food Chemistry, 2026)

Metal–insulator–metal metamaterial assisted signal enhanced spectroscopy for sugar concentration prediction in a simulated juice matrix - Jingxiao Yu; Da-Wen Sun; Zongxin Liu; Hongbin Pu (Food Chemistry, 2026)

Impact of harvesting method and advanced post-harvest processing technologies on the potentially toxic trace elements and iodine content of brown seaweed Alaria esculenta - Gaoya Dong; Rahel Suchintita Das; Zhipeng Hu; Rachida Chekri; Petru Jitaru; Xianglu Zhu; Da-Wen Sun; Brijesh K. Tiwari (Food Chemistry, 2026)

Design strategies of lipid nanovehicles for controlled functional component release in food systems - Qiyuan Jing; Hongbin Pu; Da-Wen Sun (Food Chemistry, 2026)

Bioinspired rose-petal-like SnS₂ semiconductor with sulphur vacancies for highly sensitive SERS detection of acetamiprid in vegetables and fruits - Xinru Yu; Hongbin Pu; Da-Wen Sun (Food Chemistry, 2026)

Thermally regulated interfacial alloy evolution enables stable Zn metal anodes - Yu Zhang; Yiyang Bi; Da Zhang; Lianshan Sun; Haoran Sun; Jian Li; Zhenyu Hu; Wanqiang Liu; Gang Huang (Chemical Engineering Journal, 2026)

Mechanistic insights into the adsorption and separation of nonpolar molecules on delocalization porous carbon: Dispersion interactions enhanced by multiple bonds - Peixin Wang; Jingxu Tian; Da Wei; Yue Sun; Bo Liu; Wenji Pi; Jun Ma; Yunfeng Zhang; Hongyu Chen; Rui Shi; Yang Guo; Xiang Xu; et al. (Chemical Engineering Journal, 2026)

The degradation and greenhouse gas emissions of microplastic-derived dissolved organic matter: Role of mineral and polymer types - Da Lv; Yalan Chen; Peng Wang; Ji Chen; Xinru Liang; Yunxian Zhang; Panpan Liu; Shishu Zhu; Qun Gao; Fei Wang; Bo Gao; Ke Sun (Water Research, 2026)

Deep neural network frameworks (DNNFs) for enhanced non-destructive spectroscopic quantification in foods: From hybrid pipelines to end-to-end modelling - Yuchen Ban; Yuqiao Ren; Wenrui Dong; Da-Wen Sun; Brijesh K. Tiwari (Trends in Food Science & Technology, 2026)

Mechanism of high-frequency response and mooring fatigue in a 15 MW TLP floating offshore wind turbine under second-order sum-frequency wave excitation - Siyu Sun; Xiaopeng Shen; Junrong Wang; Da Li (Ocean Engineering, 2026)

Hydroxylamine stabilizes low-ammonium comammox–anammox cooperation through selective metabolic regulation of complete nitrification - Jiantao Wen; Da Jin; Wen Sun; Peng Wu (Environmental Research, 2026)

Integrated geophysical investigation of a contaminated abandoned industrial site validated by borehole sample analysis: A case study in northeastern Shanghai, China - Shi-Jin Feng; Jin-Hui Shu; Xiao-Lei Zhang; Qi-Teng Zheng; Zhen-Xing Sun; Wen-Da Wang (Engineering Geology, 2026)

Mesozoic continental crustal growth: A comprehensive review of the accretion-arc system in the Jilin-Heilongjiang high-pressure belt - Zhong-Hua Xin; Jian-Bo Zhou; Wen-Jiao Xiao; Jiang-Tao Han; Gong-Yu Li; Xiao-Miao Tan; Hong-Da Liang; Zhuo Chen; Hong-Yan Wang; Ning-Chen Sun; Rui Gao (Earth-Science Reviews, 2026)

Engineering robust EVA/OMMT frameworks for polymer electrolytes boosting mechanical strength and lithium-ion conductivity - Yangmingyue Zhao; Chunbao Wang; Fang Wu; Xilang Sun; Libo Li; Da Zhou; Yuhang Shan; Hang Yang (Chemical Engineering Journal, 2026)

Annexin A2 orchestrates CSFV entry route selection via the annexin A2/S100A10 heterotetrameric complex - Tao Wang; Liangcai Da; Junfang Zhao; Hong Yuan; Ying Sun; Liang Zhang; Jiaoyang Li; Kun Li; Jing Zhang; Pu Sun; Zhixun Zhao; Qiang Zhang; et al. (Veterinary Microbiology, 2026)

Mechanism-driven artificial intelligence for food cold-chain control and governance - Siguo Xiong; Zhiwei Zhu; Da-Wen Sun (Trends in Food Science & Technology, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Isolation, structural elucidation, and activities evaluation of proaporphine alkaloids from Thalictrum baicalense - Meng-Yue Yang; Jing-Jing Xue; Zhao-Jing Chen; Xiao-Peng Guo; Shi-Meng Qin; Han-Gao Yang; Fang-Shen Liu; Zhan-Lin Li; Da-Hong Li; Ya-Ting Sun; Hui-Ming Hua (Phytochemistry, 2026)

Synergistic design of oxygen-rich and microporous biomass derived carbon for the catalytic adsorption of cyanide gases - Yali Wang; Mingzhe Ma; Shicai Liu; Xueyuan Pan; Yanren Jin; Ting Zhao; Ao Wang; MengMeng Fan; Da Li; Kang Sun; Jianchun Jiang; Hao Sun (Journal of Environmental Chemical Engineering, 2026)

Composite beeswax-glycerol monolaurate oleogelation enhances encapsulation efficiency and oxidative stability of microencapsulated Antarctic krill oil - Xin Sun; Liang Song; Rui-Ying Wang; Xin-Yang Ha; Fa-Wen Yin; Lei Qin; Bei-Wei Zhu; Da-Yong Zhou (Food Research International, 2026)

Artificial intelligence-enabled machine olfaction for volatile profiling and food quality decision-making - Yitian Gao; Jun-Hu Cheng; Han Wang; Yuandong Lin; Jinhua Wang; Da-Wen Sun (Food Chemistry, 2026)

Co-fermentation of Ampelopsis grossedentata with Camellia sinensis reduces bitterness, enhances sweet aroma, and generates novel bioactive theaflavin analogues - Si-Rui Li; Zi Yang; Na Song; Jia-Yi Li; Yu-Xing Zhang; Hao Li; Peng Zhang; Yu-Lan Song; Yu Sun; Kun Qian; Da-Wei Zhang; Guan-Hu Bao (Food Chemistry, 2026)

Plantain seed mucilage-derived aerogel for microplastics removal in aged traditional Chinese spirit - Meiting Liu; Hongbin Pu; Xiaojie Xu; Da-Wen Sun (Food Chemistry, 2026)

Stable and reliable method for simultaneous quantification of five neonicotinoid residues in plant-derived foods - Xinru Yu; Hongbin Pu; Da-Wen Sun (Food Chemistry, 2026)

Molecularly imprinted polymers-based sensors for antibiotic detection: from rational design and performance optimization to multiplatform sensing applications - Lingjun Geng; Da Cai; Yanjie Dong; Lei Wang; Shancang Zhao; Yemin Guo; Xia Sun (Food Bioscience, 2026)

Mechanochemical fabrication of Se-doped poly(triazine imide) with donor–acceptor motifs for photocatalytic cleavage of C–C bonds in lignin - Xudong Guo; Shuangzhen Guo; Linglong Shi; Da Li; Hao Nie; Jianjie Wang; Liping Zhao; Yihan Sun; Sitong Wu; Zeyun Hao (Bioresource Technology, 2026)

Correction: MdSOS2L1 phosphorylates MdVHA-B1 to modulate malate accumulation in response to salinity in apple - Da-Gang Hu; Cui-Hui Sun; Mei-Hong Sun; Yu-Jin Hao (Plant Cell Reports, 2026)

Development and evaluation of recombinant Varicella-Zoster virus glycoprotein E protein microneedles for enhanced pediatric vaccine delivery - Da-Eun Lee; Hye-Ran Cha; Ye-Lim Lee; Hyeon Woo Chung; Sunghoon Park; Yu-Jeong Oh; Eunjung Jung; Seung-Ki Baek; Byung Cheol Ahn; Jung Sun Yum; Jae Myun Lee; Jung-Hwan Park (Drug Delivery and Translational Research, 2026)

Functional noncoding variants within the TBX1 enhancer contribute to tetralogy of Fallot - Jimiao Gao; Tao Jiang; Yingyi Quan; Xinyue Liu; Min Da; Jiang Jiang; Jun Zhou; Hao Sun; Yan Zhou; Wanting Ma; Zicheng Zhang; Yiwei Cheng; et al. (Science China Life Sciences, 2026)

A dual-functional single-crystalline layer boosts operational stability of organic light-emitting diodes - Gao-Da Ye; Guan-Ran Wang; Xue-Peng Wang; Su-Heng Li; Nai-Qi Wang; Hu Zhang; Yu-Ting Huang; Lingjie Sun; Yajing Sun; Fangxu Yang; Jin-Bei Wei; Yue-Feng Liu; et al. (Science Bulletin, 2026)

Advancing digital depth: AI-enhanced 3D reconstruction for post-harvest food supply chain quality management - Yuqiao Ren; Tong Lei; Weihao Meng; Da-Wen Sun; Dimitrios Argyropoulos (Postharvest Biology and Technology, 2026)

Disentangling climate-driven and vegetation-mediated impacts on water resources in the upper Yellow River Basin - Zhi Liang; Ruochen Sun; Qingyun Duan; Da Xu (Journal of Hydrology, 2026)

Electric-field-driven ultra-fine fibres (EDF): A sustainable and intelligent platform for future food packaging - Jun-Hu Cheng; Kai Zhang; Zichen Li; Da-Wen Sun (Trends in Food Science & Technology, 2026)

Experimental investigation of pile anchors in sand under inclined cyclic loading for TLP supported floating offshore wind turbines - Jianbin Cui; Youhu Zhang; Shuzhao Li; Da Li; Ying Huang; Guodong Sun (Ocean Engineering, 2026)

High-voltage electrostatic field technology in food processing and preservation: mechanisms, applications, and emerging innovations - Qijun Wang; Zihan Zhang; Da-Wen Sun (Food Chemistry, 2026)

Green enzyme–ultrasound-membrane extraction of rapeseed protein: Enhancing purity and reducing antinutritional factors - Gaoya Dong; Zhipeng Hu; Shay Hannon; Dilip K. Rai; Alina Culetu; Da-Wen Sun; Brijesh K. Tiwari (Food Chemistry, 2026)

The effects and mechanisms of corn zein hydrolysate on intestinal inflammation in mouse and organoid models - Kangkai Chen; Ping Liu; Zirui Wang; Hui Xia; Ligang Yang; Da Pan; Guiju Sun; Wang Liao (Food Bioscience, 2026)

The potential of natural antimicrobials for cultured meat production: A literature review - Colin Venter; Ermie Jr. Mariano; Da-Young Lee; Sun Jin Hur (Food Bioscience, 2026)

Tailor-made sulfonated lignin derivatives with controllable anionic charge and enhanced aqueous solubility for the fabrication of uniform microspheres - Ji Won Heo; Min Soo Kim; Min Sun Kwon; Da Ye Kim; Ji Won Yang; Yong Sik Kim (Chemical Engineering Journal, 2026)

Aged nanoplastics exacerbate CPPD-induced ocular toxicity via the thyroxine pathway in zebrafish - Jin Li; Yi Zheng; Yuying Yin; Wenda Gao; Fan Tang; Xinlin Zhao; Qi Xin; Suiyi Liu; Jiaqi Xiong; Jian Lin; Da Sun; Jiangfei Chen (Aquatic Toxicology, 2026)

Impact of land use transition on ecosystem services in the Yangtze River economic belt and associated mechanism - Youzhi An; Mengsha Fan; Zhihao Tao; Peng Zhao; Hualin Chen; Da Li; Yun Wu; Qiuju Wu; Jin Sun; Feng Xu; Fengtai Zhang (Environment, Development and Sustainability, 2026)

Muscone Exerts Rapid Antidepressant Effects Through Modulating Glutamatergic Neural Transmission in the Anterior Cingulate Cortex Against Peripheral Inflammation-induced Depression - Xiaoyun Qiu; Xiaojie Zhang; Yuanzhi Yang; Minjuan Sun; Xiaoli Da; Jiaying Liu; Rui Wang; Jingjia Liang; Xuhong Jiang; Gang Tian; Qiyuan Shan; Yu Du; et al. (Neuroscience Bulletin, 2026)

Self-triggered “Core-Shell” hydrogel sensor integrated with copper nano-aggregates for aquatic product freshness monitoring and preservation - Yajun Jin; Yuandong Lin; Jun-Hu Cheng; Da-Wen Sun (Food Chemistry, 2026)

Engineering pore structure of bamboo-derived porous carbons via pyrolysis behavior of various organic potassium salts for efficient nitrate removal by capacitive deionization - Rencheng Li; Menghan Pu; Weilong Xiao; Yufeng Da; Luwei Miao; Yang Bao; Ke Li; Qiulin Yang; Wenqing Chen; Hui Sun (Desalination, 2026)

Development of Novel Host-Associated Low-Temperature Probiotics (HALP) Tailored to Aquaculture Applications - Su-Jeong Lee; Young-Sun Lee; Yu-Ri Kim; Mi-Hyeon Jeon; Da-In Noh; Seong-Mok Jeong; Kang-Woong Kim; Eun-Woo Lee; Won Je Jang (Probiotics and Antimicrobial Proteins, 2026)

Biogeographic Barriers and Historic Climate Shape the Genetic Structure and Demography of the Freshwater Crab (Brachyura, Potamidae) in Continental‐Island Systems - Ruxiao Wang; Meijun Liu; Ruyi Jin; Boyang Shi; Hongying Sun; Da Pan (Zoologica Scripta, 2026)
Island biogeography provides a crucial framework for interpreting global biodiversity patterns; however, the distinctive dynamics of continental islands remain underexplored relative to those of volcanic oceanic islands. This knowledge gap obscures our understanding of species dispersal and evolution, particularly on small continental islands whose connectivity has been modulated by Quaternary sea‐level oscillations. Here, we integrate double‐digest restriction‐site‐associated DNA (ddRAD) sequencing with mitochondrial COI and 16S rRNA data to investigate the phylogeography, population structure, demographic history and ecological niche of the narrowly distributed freshwater crab Nanhaipotamon nanriense inhabiting mainland and nearby islands in southeastern China. Our analyses revealed strong genetic differentiation, highlighting a deeply divergent island lineage isolated by a narrow marine channel and an inland lineage isolated by the Minjiang River. Demographic reconstructions indicated significant population expansions during lower sea level in the Pleistocene, followed by population contractions correlated strongly with post‐glacial sea level rise in the Holocene. By synthesising genomic, demographic and ecological evidence, our study demonstrates how marine inundation, riverine barriers and glacio‐eustatic cycles jointly shape the genetic and distributional patterns of continental island freshwater species and also provide critical insights for conservation strategies.

Tm4sf19 inhibition alleviates imiquimod-induced psoriatic dermatitis by regulating inflammatory signaling pathways and keratinocyte proliferation in mice - Min Gi Kang; Sujin Park; Eunji Hong; Min-Jung Lee; Da Seul Jung; Jin Sun Heo; Haein An; Min Woo Kim; Naim Park; Hyeyeon Park; Pyunggang Kim; Minjung Son; et al. (Inflammation Research, 2026)

Three-Dimensional Fast Marching Seismic Traveltime Computation Based on Coarse-Grid Interpolation - Yan-song Li; Jun-jie Yang; Xue-feng Gao; Hui Sun; Yun Long; Peng Lin; Song-da Ji; Hong-yong Ren; Rui Chen (Applied Geophysics, 2026)

Quantifying soil micro-element state distribution and predicting tillage performance during sodic saline-alkali subsoiling based on mathematical model and DEM simulation approach - Min Liu; Jinchun Sun; Pinyan Lv; Dongyan Huang; Da Qiao; Yingjie Guo; Weizhi Feng; Daping Fu; Limin Jiang; Jingli Wang (Computers and Electronics in Agriculture, 2026)

Integrated multi-dimensional framework for water conservation capacity evaluation and attribution in the Yellow River water conservation area - Da Xu; Ruochen Sun; Qingyun Duan; Zhi Liang; Xuejia Wang; Yan Ma (Journal of Hydrology, 2026)

ESKAPE pathogens contribute largely to antibiotic resistance spread via horizontal gene transfer in aquatic environments - Shunshun Li; Zeping Gao; Yanmei Da; Ying Zhang; Zunwei Huang; Guiying Yuan; Chao Wu; Tao Huang; Qingye Sun; Guowei Zhou (Journal of Contaminant Hydrology, 2026)

Effects of hot air pretreatment on digestibility and quality of steamed bread - Yuze Jia; Jun-Hu Cheng; Xiangwei Tang; Xucong Yu; Da-Wen Sun (Food Chemistry, 2026)

Cold plasma-assisted enzymatic hydrolysis of shrimp protein for bioactive peptide production: Structural, antioxidant, and molecular docking characterization - Caidie Tang; Jun-Hu Cheng; Jilin Li; Da-Wen Sun (Food Chemistry, 2026)

Ultra-strong green plastics from marine-sourced alginate dendritic colloids and chitin nanocrystals with a “cement–mortar” structure - Xijia Zhang; Hongbin Pu; Da-Wen Sun (Food Hydrocolloids, 2026)

Fabrication of porous cellulose acetate‑copper ferrocyanide adsorbent via thermally induced phase separation for highly efficient removal of cesium from wastewater - Kangrui Sun; Laibo Ma; Da Song; Xiaocui Hao; Wenyan Zhang; Shujing Chai; Haihong Wu; Yuqi Wang; Yi Zhang (Chemical Engineering Journal, 2026)

Stress-induced orbital splitting and lone-pair modulation in anharmonic phonon transport of BiAgSeO superlattice - Shuwei Tang; Yufei Meng; Pengfei Zhang; Da Wan; Peng Ai; Zhiwei Zhang; Ying Liu; Zhanpeng Xu; Hao Sun; Shulin Bai (Chemical Engineering Journal, 2026)

Multi-objective decision model for wastewater treatment technology selection based on machine learning - Yanbo Liu; Zhaohan Zhang; Xinyi Chen; Guohong Liu; Da Li; Jiannan Li; Yanfang Song; Jinhao Duan; Kuokai Sun; Yujie Feng (Bioresource Technology, 2026)

Collaboration of the symbiotic microbiome and host genome during the high altitude adaptation of chickens - Jiaming Jin; Chaoliang Wen; Junying Li; Chunning Mai; Jingwei Yuan; Ping Wang; Da Peng; Yiqiang Zhao; Congjiao Sun; Xueying Ma; Jing Feng; Ning Yang (Science China Life Sciences, 2026)

Mantle dunites archive multistage melt metasomatism under a fossil slow-ultraslow spreading center: an example from the Tibetan Xigaze ophiolite - Li Wang; Qing Xiong; Hong-Kun Dai; Xiang Zhou; Hong-Da Zheng; Hao-Qin Sun; Yi-Cong Li; Long-Fei Xue; Alessio Sanfilippo; Valentin Basch; Jian-Ping Zheng (Contributions to Mineralogy and Petrology, 2026)

Genetic improvement of nitrogen- and phosphorus-use efficiency in crops: Old goals with new aspirations - Wei Wang; Da Chen; Huwei Sun; Surya Kant; John P. Hammond; Lei Shi; Chengcai Chu (Molecular Plant, 2026)

Determination of anisotropic effective thermo-mechanical properties of leafy vegetables via X-ray CT and finite element modelling using forward and inverse analyses - Hui Gao; Zhiwei Zhu; Da-Wen Sun (Journal of Food Engineering, 2026)

Continuous monitoring of moisture loss of beef, beetroot, and banana slices during microwave vacuum dehydration by using THz-TDS combined with transformer-based neural network - Ying Fu; Zhihang Zhang; Da-Wen Sun (Journal of Food Engineering, 2026)

Responses of a harmful algal bloom-causing dinoflagellate Karenia mikimotoi to elevated temperature and high N:P ratio - Xiang Ye; Wen-Jing Sun; Wei-Ping Zhang; Yang Zhou; Shuo-Yu Zhang; Can-Jun Cai; Shu-Feng Zhang; Jae-Seong Lee; Minghua Wang; Da-Zhi Wang (Harmful Algae, 2026)

Uncovering cryoprotective mechanism of natural deep eutectic solvents for highly efficient cryopreservation of Lactiplantibacillus plantarum - You Tian; Da-Wen Sun; Shu-Ti Zhang; Rui Hu; Zhiwei Zhu (Food Chemistry, 2026)

Dual-enhanced copper nanocluster sensing label via metal ion-induced aggregation for on-site seafood freshness monitoring - Yajun Jin; Yuandong Lin; Jun-Hu Cheng; Da-Wen Sun (Food Chemistry, 2026)

Insight into cryopreservation mechanism of natural deep eutectic solvents (NADESs) from the transcriptomics perspective - Rui Hu; Da-Wen Sun; You Tian; Liang Xu; Libin Sun (Chemical Engineering Journal, 2026)

Clinical Evidence on the Health Benefits and Safety of Probiotic Lacticaseibacillus rhamnosus: A Systematic Review - Yu Yang; Jing Sui; Wang Liao; Shaokang Wang; Da Pan; Guiju Sun; Peng Gao; Xuesong Xiang; Hui Xia (Probiotics and Antimicrobial Proteins, 2026)

Yak dung generates lower soil N retention and stimulates higher N2O emissions relative to Tibetan sheep dung in an alpine meadow on the Eastern Qinghai-Tibetan Plateau - Zhaoyang Xiong; Xiaodan Wang; Yanjiang Cai; Da Wei; Jian Sun; Jiangtao Hong; Yongheng Gao; Xue Zhang; Ying Cao; Huan Qian; Yaxian Guo; Ziyin Du (Plant and Soil, 2026)

ANXA2 stabilizes mTOR at the plasma membrane to facilitate autophagic flux for CSFV release - Tao Wang; Liangcai Da; Junfang Zhao; Hong Yuan; Ying Sun; Liang Zhang; Kun Li; Jing Zhang; Pu Sun; Zhixun Zhao; Qiang Zhang; Yuanji Zhang; et al. (Veterinary Microbiology, 2026)

Downscaling prediction of urban wind environment based on PBMs and hybrid MLP-CNN model - Xiaohan Shen; Ruolan Sun; Gerui Sui; Rongmao Xu; Xin Zhou; Da Yan; Jingjing An (Urban Climate, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Effects of cold plasma on volatile organic compounds in foods: fundamentals, mechanisms, and applications - Jun-Hu Cheng; Jin Li; Xiao Yang; Da-Wen Sun (Food Chemistry, 2026)

Hydration-driven structural engineering via enzymatic glycation: Sustained quercetin release in pullulan-zein coatings for extended walnut preservation - Zi-han Wang; Xue-li Liu; Rui-qi Sun; Bin Qi; Jun-xia Xia; Da-yong Zhou; Liang Song (Food Hydrocolloids, 2026)

Catalytic conversion of fatty acid methyl esters to biofuels under mild reaction conditions - Xiaolong Yan; Lei Wang; Weimin Da; Yawen Shi; Zhaowei Tian; Zhitong Qian; Yu Sun; Xu Zhao; Xin Zhang; Weiming Zhai; Feng Liu; Yusen Yang; et al. (Chemical Engineering Journal, 2026)

Efficient biodegradation and detoxification of 6:2 fluorotelomer sulfonic acid by Phanerochaete chrysosporium: Insights into enzymatic mechanisms and reduced ecotoxicity - Baihui Wu; Haiyang Yu; Haiyang Huang; Tao Jiang; Haoran Zou; Hanbing Wang; Rongbing Chen; Qinsi Yang; Guoming Zeng; Jiangfei Chen; Da Sun (Chemical Engineering Journal, 2026)

Effective production of biosyngas from biomethane over spatially confined Ni catalyst with captured CO2 - Su-Ji Kim; Yeon Jeong Yu; Sung-Bin Choi; Gwan-Joong Park; Da-Bin Kang; Byung Sun Yoon; Ye-Eun Jeon; Min-Young Kim; Jeong-Chul Kim; Young-Kwon Park; Chang Hyun Ko (Bioresource Technology, 2026)

Investigating the predictability of building occupancy time series using an information entropy-based approach - Xiao Wang; Xuyuan Kang; Xin Zhou; Hongsan Sun; Zhi Shuai; Da Yan (Building and Environment, 2026)

E-cigarette vapor alters gut microbiota composition in zebrafish - Thi Ngoc Mai Dong; Delbert Almerick T. Boncan; Carl Andersen Macaraeg Tan; Da-Wei Liu; Hsin-Yu Sun; Ting-Wei Huang; Chen Hsu; Kuo-Chang Chu; Zulvikar Syambani Ulhaq; Keng Po Lai; Douglas Robert Drummond; Yukiko Ogino; et al. (Science of The Total Environment, 2026)

Naringenin as a bioactive preservative: Coordinated suppression of ethylene biosynthesis and cell wall disassembly delays apple senescence during storage - Ming-Fei Qiao; Peng-Liang Han; Meng-Meng Wei; Zhao-Peng Nie; Song Zhang; Wen-Yan Wang; Hai-Bo Wang; Tian-Ge Chu; Ze Chen; Quan Sun; Da-Gang Hu (Postharvest Biology and Technology, 2026)

Melatonin regulates petal senescence in peony (Paeonia lactiflora Pall.) cut flowers via the ROS pathway - Yuxuan Wang; Miao Sun; Mengdi Wang; Xiaolong Lv; Wei Zhu; Le Chen; Xi Chen; Chang Guo; Jaime A. Teixeira da Silva; Xiaonan Yu (Postharvest Biology and Technology, 2026)

Asthenosphere-crust interactions in a continental-subduction channel: Records from UHP peridotite-hosted pyroxenites - Si-Yi Cao; Qing Xiong; Jian-Ping Zheng; Hong-Kun Dai; Qiang Ma; Wen Zhang; Hong-Da Zheng; Hao-Qin Sun; William L. Griffin; Suzanne Y. O'Reilly (Lithos, 2026)

Radiant solutions: Unlocking the mysteries of Mn2+ and Pd2+ with a mobile fluorescence wizard - Virender; Manpreet Kaur; Hari Om; Bakhtiyar Najafov; Ashok Kumar Sharma; Ismayil M. Garazade; M.Fátima C. Guedes da Silva; Armando J.L. Pombeiro; Wei Sun; Brij Mohan (Journal of Hazardous Materials, 2026)

A mutually beneficial waste-to-biochar strategy: Mn-mediated dual enhancement of 5-HMF production and catalytic performance - Yan Sun; Ranxin Li; Qiubo Wang; Wen-da Oh; Mingjie Huang; Xiaohui Wu; Tao Zhou (Chemical Engineering Journal, 2026)

Genetic and morphological data indicate the occurrence of a Rhipicephalus sp. and the absence of Rhipicephalus linnaei in Pakistan - Muhammad Numan; Zaibullah Khan; Sher Bahadar Khan; Mohibullah Shah; Iram Liaqat; Itabajara da Silva Vaz Junior; Lidia Chitimia-Dobler; Abid Ali; Zhihua Sun; Mashal M. Almutairi (Tropical Animal Health and Production, 2026)

Inter-comparison of soybean models for simulation of evapotranspiration under rainfed and irrigated conditions - Kritika Kothari; Andrew Suyker; Rafael Battisti; Kenneth J. Boote; Sotirios Archontoulis; Julie Constantin; Santiago V. Cuadra; Philippe Debaeke; Elvis F. Elli; Babacar Faye; David Fleisher; Brian Grant; et al. (Agricultural and Forest Meteorology, 2026)

Regulated cell death in endometrial diseases: from molecular mechanisms to targeted therapies - Duo Zi; Jing Sun; Na Zuo; Tingting Li; Junzhi Liang; Jia Hu; Zhijing Na; Hao Zhang; Lixia He; Da Li (Archives of Toxicology, 2026)

Recent advances and strategies in cultured satellite cell cultivation for efficient cultured meat production: A review - Dong Bin Kim; Hyo Jin Lee; Hye Won Lee; Ho Gun Jang; Jong Hyuk Kim; Sun Jin Hur; Da Young Lee; Seon-Tea Joo; Sang-Eun Jung; Seung Yun Lee (Trends in Food Science & Technology, 2025)

Intelligent non-invasive testing of food quality: Advancing accuracy and efficiency powered by artificial intelligence - Jingxiao Yu; Hongbin Pu; Da-Wen Sun (Trends in Food Science & Technology, 2025)

Determination of porosity and permeability correlation of leafy vegetable based on X-ray computed tomography and cell segmentation - Hui Gao; Zhiwei Zhu; Da-Wen Sun (Journal of Food Engineering, 2025)

Biochar-loaded nano zero-valent iron toward Microcystis aeruginosa removal: Performance and mechanisms - Haoxuan Wei; Jun Luo; Fei Wang; Quanfeng Wang; Guoming Zeng; Jujiao Zhao; Xiaoling Lei; Da Sun (Journal of Environmental Chemical Engineering, 2025)

Modulating physicochemical and interfacial properties of faba bean proteins under thermal treatment and pH shifting: implications for emulsion stabilization - Shuyang Wang; Song Miao; Da-Wen Sun (Food Research International, 2025)

The inhibitory mechanisms of plasma-activated water on biofilm formation of Pseudomonas fluorescens by disrupting quorum sensing - Yi-Ming Zhao; Lin Zhang; Yulong Bao; Yiting Guo; Haile Ma; Ronghai He; Paula Bourke; Da-Wen Sun (Food Research International, 2025)

Development of scale-up isochoric freezing equipment for better preserving litchi fruit: Basic characteristics, aroma quality, and water status - Enze Wang; Da-Wen Sun; You Tian (Food Chemistry, 2025)

Egg components as bioactive and structural inputs for cultured meat - Da Young Lee; Colin Venter; Ermie Jr. Mariano; Ji Won Park; Seok Namkung; So Young Choi; Ye Won Shin; Chae Hyeon Bok; Woo Jin Lee; Sun Jin Hur (Food Bioscience, 2025)

Corrigendum to “Evaluation of bacteriostatic and antioxidant screening of secondary metabolites of endophytic fungi in Lanzhou lily” [Bioresour. Technol. Rep. 32 (2025) 102380] - Xinlan Wang; Bolu Sun; Ying Lv; Miao Zhou; Xuanxiu Da; Jiali Kang; Haiying He; Chenyu Qin; Quhuan Ma; Hongxia Shi; Lin Yang; Xiaofeng Shi (Bioresource Technology Reports, 2025)

Evaluation of bacteriostatic and antioxidant screening of secondary metabolites of endophytic fungi in Lanzhou lily - Xinlan Wang; Bolu Sun; Ying Lv; Miao Zhou; Xuanxiu Da; Jiali Kang; Haiying He; Chenyu Qin; Quhuan Ma; Hongxia Shi; Lin Yang; Xiaofeng Shi (Bioresource Technology Reports, 2025)

Research and application of CMA numerical weather prediction in meteorological support for the Beijing Winter Olympics (2022) - Guo Deng; Xueshun Shen; Huiling Yuan; Jiandong Gong; Hua Tong; Liantang Deng; Zhifang Xu; Jing Chen; Jian Sun; Yong Wang; Mingxuan Chen; Jianjie Wang; et al. (Science China Earth Sciences, 2025)

Arthroderma guizhouense sp. nov., a Novel Geophilic Species from Guizhou, China - Kai-Rong Wang; Heng Pan; Bing-Da Sun; Gang Tao; Zhi-Yuan Zhang (Mycopathologia, 2025)

Combustion Behavior and Thermal Disaster Quantification of Weathered Water-Saturated Coal in an Oxygen-Poor Environment of Goaf - Hui-yong Niu; Hao-liang Zhu; Qing-qing Sun; Hai-yan Wang; Gong-da Wang; Lu-lu Sun (Natural Resources Research, 2025)

Identification of grape H3K27 methyltransferase genes and their expression profiles during grape fruit ripening - Ding-Ding Zuo; Hao-Ting Sun; Lu Yang; Fang-Hui-Zi Shang; Da-Long Guo (Molecular Biology Reports, 2025)

Development and validation of a portable TDLAS system for gas chromatography–level quantification of methane emissions from rice - Sujeevan Rajendran; Wonbok Lee; Sun Hwa Lee; Dongjin Shin; Da Hee Jung; Yu Mi Kang; Seok-in Yun; Byoung Il Je; Chul Min Kim; Young Hun Song (Plant Biotechnology Reports, 2025)
Rice cultivation is a significant source of agricultural methane (CH₄), yet routine quantification still relies heavily on gas chromatography (GC), which limits throughput and field deployment. Here, we evaluated a portable tunable-diode-laser absorption spectroscopy (TDLAS) detector (PMD) as an alternative to GC for measuring CH₄ released from pot-grown rice plants under field conditions. Weekly closed-chamber samples from five cultivars were analyzed in parallel by GC (FID/MS) and the PMD. Standard gas tests showed an excellent linear relationship for the PMD (R 2 = 0.9995), indicating a near-ideal response. Across field samples, GC and PMD were strongly associated (R 2 = 0.9943). Bland–Altman analysis revealed a mean bias (GC − PMD) of 8.55 with 95% limits of agreement − 9.16 to 26.26, and Lin’s concordance correlation coefficient was 0.991, evidencing near-perfect agreement despite a slight systematic offset. A simple calibration with a linear regression eliminated the bias and narrowed the limits of agreement, while preserving the high correlation. Residual analyses suggested a modest influence of CO₂ (but not N₂O) on between-method differences. Taken together, the PMD provides rapid, robust, and labor-efficient CH₄ measurements that closely match GC when a fixed calibration is applied, enabling high-throughput phenotyping of rice genotypes and management practices in both laboratory and field settings. This calibrated, portable approach lowers barriers to large-scale screening for low-emission rice, supporting climate-smart crop improvement.

Corrigendum to “Immunological characteristics of the recombinant pseudorabies virus with chimeric PCV Cap protein in pigs” [Vet. Microbiol. 305 (2025) 110529] - Chenhe Lu; Wenjing Chen; Heng Chen; Gang Xing; Jiayu Ma; Hui Zhou; Linglong Qin; Da Liu; Shiping Sun; Peng Peng; Haimin Li; Yulan Jin; et al. (Veterinary Microbiology, 2025)

Multifunctional radiative cooling materials: A transformative pathway for zero-energy food preservation and postharvest management - Liang Xu; Da-Wen Sun (Trends in Food Science & Technology, 2025)

Intelligent hydrogels: Food detection, preservation and delivery driven by material-derived intelligence - Shiwei Zheng; Da-Wen Sun; Zhiwei Zhu (Trends in Food Science & Technology, 2025)

Nonlinear theoretical model for predicting the progressive damage of composite pipes in deep-sea mining - Haibo Sun; Yingying Wang; Da Li; Lusheng Jia; Hanchen Zhou; Junjie Han (Ocean Engineering, 2025)

Responses of a harmful algal bloom-causing dinoflagellate Prorocentrum obtusidens to elevated temperature and urea - Wei-Ping Zhang; Yang Zhou; Wen-Jing Sun; Shuo-Yu Zhang; Shu-Feng Zhang; Jae-Seong Lee; Minghua Wang; Da-Zhi Wang (Harmful Algae, 2025)

Characterisation of dynamic changes in nutritional components and aroma compound formation in natto during fermentation and post-ripening - Mubai Sun; Ni Yang; Yuguang He; Xinyu Miao; Honghong Niu; Mei Hua; Jinghui Wang; Da Li (Food Research International, 2025)

Pd/his@SiO2 colourimetric sensor array for ethylene monitoring under variable temperature and humidity conditions - Zhiwei Zhu; Shuqi Huang; Da-Wen Sun (Food Chemistry, 2025)

Advanced supramolecular food safety sensing technology: principles and applications - Hongbin Pu; Chuying Shi; Da-Wen Sun (Food Chemistry, 2025)

Effects of cold plasma-assisted alcalase on the structure, allergenicity and epitopes of shrimp tropomyosin - Caidie Tang; Jun-Hu Cheng; Hangyu Zhong; Jilin Li; Da-Wen Sun (Food Chemistry, 2025)

Meta-terahertz sensing: Metamaterial-enhanced rapid and efficient detection of food contaminants - Jingxiao Yu; Hongbin Pu; Da-Wen Sun (Chemical Engineering Journal, 2025)

Functional activities of Lacticaseibacillus casei in culture of Oplegnathus punctatus - Yin Han; Duoxiang Zhao; Da Liang; Yuanyuan Sun; Wenjie Wang; Jiansong Chu; Zizhong Qi (Aquaculture International, 2025)

Enhancing food safety and quality: multiplex detection using smart nanostructured molecular logic technologies - Xinru Yu; Hongbin Pu; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2025)

Valorization of potato by-products as a source of plant proteins: novel extraction techniques and potential applications - Zhipeng Hu; Xianglu Zhu; Gaoya Dong; Joncer Naibaho; Shay Hannon; Da-Wen Sun; Brijesh K. Tiwari (Critical Reviews in Food Science and Nutrition, 2025)

Exploring hypoxia-triggered edema in sea cucumbers: Molecular perspectives on environmental stress - Da Huo; Bayden Russell; Fang Su; Botao Liu; Libin Zhang; Hongsheng Yang; Mary A. Sewell; Lina Sun (Aquaculture, 2025)

Chiral switching of many-body steady states in a dissipative Rydberg gas - Chongwu Xie; Konghao Sun; Kang-Da Wu; Chuan-Feng Li; Guang-Can Guo; Wei Yi; Guo-Yong Xiang (Science Bulletin, 2025)

Dating of Early Triassic Chaohu Fauna by precise U-Pb age constraints: Temporal calibration of the emergence and first radiation of Mesozoic marine reptiles - Yi-Nuo Wang; Da-Yong Jiang; Ryosuke Motani; Ming-Tao Yao; Min Zhou; Zuo-Yu Sun; Jian-Dong Huang; Zhao-Liang Ma (Palaeoworld, 2025)

OsSPT38 encodes a novel SUMO E3 ligase that improves rice stress resilience and grain yield - Zi-Sheng Zhang; Zheng-Yi Zhang; Jin-Qiu Xia; Si-Yan Chen; Liang-Qi Sun; Jie Wu; Da-Yu He; Jing-Xian Wang; Qin-Yu Liang; Lei Wang; Ke Ruan; Tian Sang; et al. (Molecular Plant, 2025)

Maternal ingestion of polyethylene microplastics results in reduced antiviral responses by dysregulating the immune system in their progeny - Subin Park; Jae-Eun Byun; Jihyun Yang; Wang Sik Lee; Bohyeon Jeong; Jeong Yeob Baek; Mi Sun Kim; Jahong Koo; Jun Young Heo; Jinyoung Jeong; Haiyoung Jung; Da Yong Lee (Journal of Hazardous Materials, 2025)

Gut-brain axis dysfunction mediates neurotoxicity of embryonic p-phenylenediamine exposure in zebrafish - Minyan Xu; Dongliang Pan; Jia Yi; Yi Zheng; Guoming Zeng; Jian Lin; Yang Song; Da Sun; Jiangfei Chen (Journal of Hazardous Materials, 2025)

Defect-engineered MOF-based magnetic SERS substrate with “berries-on-hedgehog” morphology for sensitive detection of organophosphorus pesticide residues in rice samples - Mingchun Lv; Hongbin Pu; Da-Wen Sun (Food Chemistry, 2025)

Reducing anti-nutritional factors in pea protein using advanced hydrodynamic cavitation, ultrasonication, and high-pressure processing technologies - Gaoya Dong; Zhipeng Hu; Jiafei Tang; Rahel Suchintita Das; Da-Wen Sun; Brijesh K. Tiwari (Food Chemistry, 2025)

Fast real-time monitor of rice grains infested with Sitophilus oryzae based on terahertz imaging combined with machine learning - Jingxiao Yu; Hongbin Pu; Da-Wen Sun (Food Control, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

Eco-friendly eugenol curing agent-derived biobased epoxy resins for multi-functional integration - Zhiyong Li; Xiangyan Ji; Xiaoge Li; Da Gao; Lei Shen; Wei He; Jie Sun; Dingqiang Lu; Jingjing Meng; Kai Guo (Chemical Engineering Journal, 2025)

Ten questions concerning calibrating building energy simulation models - Adrian Chong; Da Yan; Kaiyu Sun; Sicheng Zhan; Siyu Cheng; Yi Wu; Yixing Chen; Tianzhen Hong (Building and Environment, 2025)

Editorial Expression of Concern: HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Chlorella vulgaris-derived biochar loaded with nano zero-valent iron induces different responses in algal cells in terms of growth, physiological, antioxidant defense, and biochemical indices - Guoming Zeng; Zilong Ma; Yu He; Qian Luo; Qiaoli Xie; Da Sun (Algal Research, 2025)

Structure-activity relationships and activity enhancement techniques of marine bioactive peptides (MBPs) - Cai-die Tang; Jun-Hu Cheng; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2025)

Insights Into the Separate and Joint Effects of Cadmium and Cesium on the Risk of Circadian Syndrome and the Underlying Mechanism: An Integrated Epidemiological and Network Toxicological Study - Zhiying Huo; Wei Liu; Qiang Sun; Jiahao Song; Shuhui Wan; Wendi Shi; Yueru Yang; Le Hong; Qing Liu; Yongfang Zhang; Da Shi; Weihong Chen; et al. (Biological Trace Element Research, 2025)

Seismic Data Interpolation by AVO-Preserving Hyperbolic Radon Transform Using FISTA and Polynomial Fitting - Sheng-chao Wang; Han-feng Liu; De-fu Zhang; Hui Sun; Wei Zhang; Song-da Ji (Applied Geophysics, 2025)

Revolutionizing cryopreservation: Bio-based cryoprotectants, mechanisms, and advanced applications for sustainable pan-food systems - Xiao-Yi Liu; Da-Wen Sun; You Tian (Trends in Food Science & Technology, 2025)

Bacterial cellulose-driven sustainable food packaging innovations: Biosynthesis, functionalization, and applications - Yibing Zhang; Da-Wen Sun; Liang Xu (Trends in Food Science & Technology, 2025)

Variation in dietary preference related the per- and polyfluoroalkyl substance exposure in two sympatric seabird species from the Yellow Sea, China - Yachang Cheng; Yuanyuan Liu; Yuanyuan Zhao; Da Zheng; Kaize Feng; Jinye Cheng; Jiansong Chu; Yang Liu; Jiachen Sun (Journal of Hazardous Materials, 2025)

Chiral spiny L-au@ag@ZIF-8 three-layer core-shell SERS substrate for sensitive detection of quinalphos in tangerines - Qing Yang; Hongbin Pu; Da-Wen Sun (Food Chemistry, 2025)

Dual-band terahertz metamaterial sensor integrated with deep learning for synergistic identification of red wine varieties - Jingxiao Yu; Hongbin Pu; Da-Wen Sun (Chemical Engineering Journal, 2025)

Screening of biocontrol agents against lily bulb rot caused by F. oxysporum and research on their fermentation process - Bolu Sun; Xinlan Wang; Ying Lv; Xuanxiu Da; Miao Zhou; Jiali Kang; Haiying He; Chenyu Qin; Xiangdong Wang; Lin Yang; Quhuan Ma; Hongxia Shi; et al. (Bioresource Technology Reports, 2025)

Exposure and health effects follow-up study of residents near a former smelter site - Young-Hun Kim; Da-Som Lee; Jung-Eum Lee; Heon Kim; Yong-Dae Kim; Young-Seoub Hong; Jung-Duck Park; Byung-Sun Choi (Toxicological Research, 2025)

Decadal variability in δ18O over the East Asian monsoon region responding to solar activity over the last millennium - Caiwei Da; Xiaoqing Wang; Weiyi Sun; Jian Liu; Liang Ning; Gongzhe Chen (Science China Earth Sciences, 2025)

Genome-wide association analysis provides genetic insights into variation of nutritional quality traits in sea cucumber Apostichopus japonicus - Hongyuan Zhao; Da Huo; Wei Cui; Chunxi Jiang; Shilin Liu; Irène Rasoamananto; Libin Zhang; Lina Sun (Journal of Oceanology and Limnology, 2025)

A novel nanocatalyst of the multi-walled carbon nanotubes decorated with niobium pentoxide for the Eriochrome black T dye degradation - Claudir Gabriel Kaufmann; Daniel Moro Druzian; William Leonardo da Silva; Rubia Young Sun Zampiva; Marco Rossi; Giovani Pavoski; Denise Crocce Romano Espinosa; Annelise Kopp Alves; Carlos Pérez Bergmann; Cristiano Rodrigo Bohn Rhoden; Sergio Roberto Mortari (Environmental Science and Pollution Research, 2025)

Advancements in novel polysaccharide analysis: Emerging spectral technology approaches - Nan Lin; Yuqiao Ren; Da-Wen Sun (Trends in Food Science & Technology, 2025)

Particulate matter 2.5 stimulates pyroptosis and necroptosis via the p38 MAPK/Akt/NF-κB signaling pathway in human corneal epithelial cells - Da Hye Kim; Hyesook Lee; Min Yeong Kim; Hyun Hwangbo; Seon Yeong Ji; EunJin Bang; Su Hyun Hong; Gi Young Kim; Sun-Hee Leem; Dongryeol Ryu; JaeHun Cheong; Yung Hyun Choi (Toxicology, 2025)

Controlling high-concentration precursor crystallization to minimize photon loss in bifacial perovskite solar cells - Shan Gan; Haoxuan Sun; Min Wang; Da Dou; Siyang Zhang; Chen Li; Liang Li (Science Bulletin, 2025)

Efficient catalytic degradation and detoxification of 6PPD-quinone by the multifunctional enzyme system of phanerochaete chrysosporium - Haiyang Yu; Li Luo; Baihui Wu; Jiaxuan He; Hanbing Wang; Rongbing Chen; Mingxia Ji; Qinsi Yang; Guoming Zeng; Wei Wu; Da Sun (Journal of Hazardous Materials, 2025)

Mechanism of electrochemical algal control and its effect on metabolic pathways of algal cells - Guoming Zeng; Zilong Ma; Rui Zhang; Yu He; Yong Xiao; Da Sun; Xiaoling Lei (Journal of Hazardous Materials, 2025)

Designing novel truncated aptamers for sensitive tropomyosin detection in shrimp products - Meixi Chen; Jun-Hu Cheng; Da-Wen Sun (Journal of Food Engineering, 2025)

Fabrication and application of ferrocene contained MOF derived porous carbon: A single multi-interference clean-up QuEChERS sorbent for facile analysis of triazine herbicides in various fruits and vegetables by LC-MS/MS - Zi-Ling Li; Da-Jin Yang; Jia-Qi Zhao; Wen-Jie Sun; Jie Gao; Shu-Feng Song; Hou-Jun Xu; Hai-Jie Li; Fa-Ming Tian; Man-Man Wang (Food Chemistry, 2025)

Effects of chain lengths and unsaturation degrees of fatty acids on microwave-processed wheat starch-fatty acid complexes: Structure, digestion, and storage stability - Tingting Gao; You Tian; Ji Ma; Da-Wen Sun (Food Chemistry, 2025)

Exploring the moisture absorption behaviours of microwave-processed wheat starch-stearic acid complexes from a molecular view - Tingting Gao; You Tian; Fei Pan; Da-Wen Sun (Food Chemistry, 2025)

Green modification of rheological properties of agar and alginate using atmospheric pressure plasma jets (APPJ) - Kexin Zhang; Laura G. Gómez-Mascaraque; Farhad Garavand; Ming Zhao; Da-Wen Sun; Brijesh K. Tiwari (Algal Research, 2025)

Multifactorial analysis of allergen variability in Alaria esculenta seaweed: Influence of drying techniques, harvesting methods, and pre-treatments - Gaoya Dong; Zhipeng Hu; Xianglu Zhu; Julie McGuire; Da-Wen Sun; Brijesh K. Tiwari (Algal Research, 2025)

Importance of the ECM –receptor interaction for adaptive response to hypoxia based on integrated transcription and translation analysis - Da Huo; Shilin Liu; Libin Zhang; Hongsheng Yang; Lina Sun (Molecular Ecology, 2025)
Low dissolved oxygen (LO) conditions represent a major environmental challenge to marine life, especially benthic animals. For these organisms, drastic declines in oxygen availability (hypoxic events) can trigger mass mortality events and thus, act as agents of selection influencing the evolution of adaptations. In sea cucumbers, one of the most successful groups of benthic invertebrates, the exposure to hypoxic conditions triggers adaptive adjustments in metabolic rates and behaviour. It is unclear, however, how these adaptive responses are regulated and the genetic mechanisms underpinning them. Here, we addressed this knowledge gap by assessing the genetic regulation (transcription and translation) of hypoxia exposure in the sea cucumber Apostichopus japonicus . Transcriptional and translational gene expression profiles under short‐ and long‐term exposure to low oxygen conditions are tightly associated with extracellular matrix (ECM)–receptor interaction in which laminin and collagen likely have important functions. Finding revealed that genes with a high translational efficiency (TE) had a relatively short upstream open reading frame (uORF) and a high uORF normalized minimal free energy, suggesting that sea cucumbers may respond to hypoxic stress via altered TE. These results provide valuable insights into the regulatory mechanisms that confer adaptive capacity to holothurians to survive oxygen deficiency conditions and may also be used to inform the development of strategies for mitigating the harmful effects of hypoxia on other marine invertebrates facing similar challenges.

Elevating nanomaterial optical sensor arrays through the integration of advanced machine learning techniques for enhancing visual inspection of food quality and safety - Yuandong Lin; Jun-Hu Cheng; Ji Ma; Chenyue Zhou; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2025)

Impacts of non-thermal pretreatments on banana slices during microwave vacuum dehydration using THz-TDS and NIR-HSI techniques - Ying Fu; Yuqiao Ren; Da-Wen Sun (Journal of Food Engineering, 2025)

Different straw lengths and burial modes affect the salt distribution in coastal saline soil and the regulation of salt stress resistance in tomato - Da Huang; Yugeng Guo; Sheng Chen; Zhenchang Wang; Boming Sun; Yingyuan Niu; Shiquan Dong (Plant and Soil, 2025)

Mechanism of pH-sensitive Amphiphilic Endosomal Escape of Ionizable Lipid Nanoparticles for Cytosolic Nucleic Acid Delivery - Zheng-Rong Lu; Da Sun (Pharmaceutical Research, 2025)
Lipid nanoparticles (LNPs) are among the most successful classes of nonviral delivery systems for nucleic acid-based therapeutics in treating human diseases. One of the key challenges in achieving efficient cytosolic delivery of nucleic acids is overcoming endosomal entrapment within cells. Conventional lipid bilayer-forming cationic and amino lipids mediate endosomal escape via the mechanism of lamellar-to-inverted hexagonal phase transition, resulting in suboptimal cytosolic cargo delivery. pH-sensitive amphiphilic cell membrane disruption and endosomal escape have emerged as a strategy for designing protonatable or ionizable lipids, especially nonlamellar lipids, for efficient cytosolic nucleic acid delivery. Nonlamellar amino lipids possess a large wedge-shaped tail structure and do not form stable lipid bilayers. These lipids and their corresponding LNPs remain neutral, non-amphiphilic, or minimally amphiphilic at physiological pH (7.4). They become amphiphilic upon protonation or ionization in acidic endosomes (pH 6.5–5.4). The electrostatic interaction of ionized nonlamellar lipids with the negatively charged endosome membrane, combined with their large wedge-like structures, disrupts the lipid bilayer, facilitating efficient endosomal escape. Additionally, the nonlamellar ionizable lipids can be fine-tuned by altering the structure of amino head groups and lipid tails to achieve the precisely controlled pH-sensitive amphiphilic membrane disruption at endosomal pH. Therefore, these lipids exhibit excellent safety profiles and high efficiency for in vivo delivery of various therapeutic nucleic acids. pH-sensitive amphiphilic membrane disruption and endosomal escape provide a feasible and effective mechanism for designing ionizable lipids for safe and efficient in vivo nucleic acid delivery.

Multi-routine-data driven spatio-temporal short-term predictions for surface ozone in China - Canju Zheng; Hengqing Shen; Jianan Sun; Guangliang Liu; Haowei Cao; Jie Zhang; Xiang Gong; Da Xu (Air Quality, Atmosphere & Health, 2025)

Immunological characteristics of the recombinant pseudorabies virus with chimeric PCV Cap protein in pigs - Chenhe Lu; Wenjing Chen; Heng Chen; Gang Xing; Jiayu Ma; Hui Zhou; Linglong Qin; Liu Da; Shiping Sun; Peng Peng; Haimin Li; Yulan Jin; et al. (Veterinary Microbiology, 2025)

Identification of novel sulfur-containing petroporphyrins in a natural bitumen: Potential biomarkers for aerobic organisms - Fang Zheng; Weisheng Yang; Yanbin Wang; Mi An; Da Huo; Chunyan Wang; Qing Cao; Jing He; Quan Shi; Yongge Sun (Organic Geochemistry, 2025)

Environmental fate, toxicity, and mitigation of 6PPD and 6PPD-Quinone: Current understanding and future directions - Jia Yi; Jing Ruan; Haiyang Yu; Baihui Wu; Jing Zhao; Hanbing Wang; Rongbing Chen; Qinsi Yang; Jiangfei Chen; Da Sun (Environmental Pollution, 2025)

Eco-friendly lily bulb-derived polysaccharide aerogel for efficient microplastics and nanoplastics removal - Meiting Liu; Hongbin Pu; Da-Wen Sun (Carbohydrate Polymers, 2025)

Modulation of Intestinal Flora: a Novel Immunotherapeutic Approach for Enhancing Thyroid Cancer Treatment - Weiqiang Huang; Tao Jiang; Jiaxuan He; Jing Ruan; Baihui Wu; Runchao Tao; Peiye Xu; Yongpan Wang; Rongbing Chen; Hanbing Wang; Qinsi Yang; Kun Zhang; et al. (Probiotics and Antimicrobial Proteins, 2025)

Analysis of current technology status for the industrialization of cultured meat - Da Young Lee; Jinmo Park; Dahee Han; Yeongwoo Choi; Jin Soo Kim; Ermie Mariano; Juhyun Lee; Seung Hyeon Yun; Seung Yun Lee; Sungkwon Park; Suk Ho Bhang; Sun Jin Hur (Critical Reviews in Food Science and Nutrition, 2025)

Artificial intelligence for prediction of shelf-life of various food products: Recent advances and ongoing challenges - Mahdi Rashvand; Yuqiao Ren; Da-Wen Sun; Julia Senge; Christian Krupitzer; Tobi Fadiji; Marta Sanzo Miró; Alex Shenfield; Nicholas J. Watson; Hongwei Zhang (Trends in Food Science & Technology, 2025)

Emerging eutectogel materials: Development, synthesis, properties, and applications in food science - Rui Hu; Da-Wen Sun; You Tian (Trends in Food Science & Technology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Performance evaluation of a miniature UV particle charger - Jitong Zhou; Gehang Huang; Xiaoqi Lei; Qiang Sun; Fajun Yu; Huaqiao Gui; Jianguo Liu; Huanqin Wang; Da-Ren Chen (Journal of Aerosol Science, 2025)

Hollow-whisker modified calcium phosphate loaded with deferoxamine to promote osteoporotic bone regeneration by acting HIF-1α signaling pathway - Linyun Tan; Wacili Da; Cong Feng; Yitian Wang; Xin Hu; Guifeng Du; Hao Wang; Minghao Sun; Yuanrui Luo; Jingyang Li; Xiangfeng Li; Li Min; et al. (Chemical Engineering Journal, 2025)

Hydrogel-elastomer hybrid integrated with radiative and evaporative cooling for passive temperature-adaptive regulation - Libin Sun; Da-Wen Sun; Liang Xu; You Tian; Rui Hu; Zhiwei Zhu (Chemical Engineering Journal, 2025)

CD38 Coordinates with NF-κB to Promote Cochlear Inflammation in Noise-Induced Hearing Loss: the Protective Effect of Apigenin - Da Liu; Na Sai; Ying Zhou; Ning Yu; Qing-qing Jiang; Wei Sun; Wei-ju Han; Weiwei Guo (Molecular Neurobiology, 2025)

Experimental Study on the Hole-Forming Process at the Borehole Bottom During Hot Water Drilling in Ice and Its Influence Mechanisms - Zhipeng Deng; Youhong Sun; Xiaopeng Fan; Pavel Talalay; Yifan Yang; Ximu Liu; Da Gong; Bing Li; Ting Wang; Wei Wu; Nan Zhang; Xianzhe Wei (Journal of Marine Science and Engineering, 2025)
Hot water drilling is a drilling method that employs high-temperature and high-pressure hot water jetting to achieve ice melting drilling. Characterized by rapid drilling speed and large hole diameter, it is widely used for drilling observation holes in polar ice sheets and ice shelves. Understanding the hole-enlargement process at the bottom of hot water-drilled holes is crucial for rationally designing the structure of hot water drills. However, due to the complexity of heat transfer processes, no suitable theoretical model currently exists to accurately predict this process. To address this, this paper establishes an experimental platform for hot water drilling and conducts 24 sets of experiments under different drilling parameters using visualization techniques. The study reveals the influence mechanisms of drilling speed, hot water flow rate, hot water temperature, downhole drill shape, and nozzle structure on the hole-forming process at the borehole bottom. Experimental results indicate that the primary hole enlargement occurs near the nozzle, achieving 69–81% of the theoretical maximum borehole diameter. The thermal melting efficiency at the borehole bottom is approximately 80%, with about 20% of the input hot water energy heating the surrounding ice. Under identical hot water parameters, jet shapes and drill shapes exhibit minimal impact on borehole geometry. But the improvement of the jet speed and hot water temperature can accelerate the hole-forming process.

Regulating bacterial biofilms in food and biomedicine: unraveling mechanisms and Innovating strategies - Jun-Hu Cheng; Rong Du; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2025)

Dissection of the potential mechanism of polystyrene microplastic exposure on cardiomyocytes - Dahui Xue; Jingnan Huang; Xin Sun; Wei Zhang; Huan Ma; Da Yin; Yuanhao Wang; Jigang Wang; Chuanbin Yang; Qingshan Geng (Science of The Total Environment, 2025)

Corrigendum to “Controlled atmosphere storage enhances Korean melon shelf life and quality: A comparative metabolic analysis with reefer container export” [Postharvest Biol. Technol. 219, January 2025, 113238] - Woochul Ju; Ji-Hyun Lee; Eunsu Do; Da-yeong Ko; Eungu Jee; Min-Sun Chang; Hyang Lan Eum; Haejo Yang; Kang-Mo Ku (Postharvest Biology and Technology, 2025)

Chemical constituents of Himantormia lugubris collected from Antarctica and their PTP1B and α-glucosidase inhibitory activities - Manh Tuan Ha; Thi Thanh Le; Da Yeong Lee; Chung Sub Kim; Ui Joung Youn; Sang Hee Kim; Jeong Ah Kim; Byung Sun Min (Phytochemistry Letters, 2025)

Boosting catalytic performance of N doped porous carbon derived from coal tar pitch: The role of N species and the contribution of 1O2 - Linlin Huang; Xuwen Zhang; Lin Wang; Tingting Liu; Da Li; Tao Sheng; Caiyu Sun; Lixin Li (Journal of Water Process Engineering, 2025)

Large-scale protein extraction from oat hulls using two hydrodynamic cavitation techniques: A comparison of extraction efficiency and protein nutritional properties - Jiafei Tang; Gulden Goksen; Md Saiful Islam; Vivek Ranade; Shay Hannon; Da-Wen Sun; Brijesh K. Tiwari (Food Chemistry, 2025)

Fermentation performances, bioactivity, and metabolic profiles of fermentated tomato juice by lactic acid bacteria isolated from Chinese traditional fermented foods - Jun Sun; Xunyu Song; Xinbing Zhang; Aroosa Mushtaq; Mingzhi Da; Fang Chen (Food Bioscience, 2025)

Exploring the epigenetic impacts of atrazine in zebrafish: Unveiling mechanisms of neurotoxicity, reproductive toxicity, and implications for human health - Haiyang Yu; Baihui Wu; Jiaxuan He; Jia Yi; Wei Wu; Hanbing Wang; Qinsi Yang; Da Sun; Hongliang Zheng (Environmental Pollution, 2025)

Development of potential intron polymorphic (PIP) markers in melon (Cucumis melo L.) - Rui Sun; Yan-Ge Li; Ding-Ding Zuo; Meng-Ling Zheng; Jing Zhang; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Genetic Resources and Crop Evolution, 2025)

Research on fault diagnosis method and interpretability of nuclear power plant based on hybrid transformer model - Gui Zhou; Min-jun Peng; Hang Wang; Da-bin Sun; Zi-kang Li (Annals of Nuclear Energy, 2025)

Developments in food neonicotinoids detection: novel recognition strategies, advanced chemical sensing techniques, and recent applications - Xinru Yu; Hongbin Pu; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2025)

Histological and transcriptome analysis of gonadal development provides new insights into the characteristics of sex differentiation and the screening of key genes in the golden pompano (Trachinotus blochii) - Feibiao Song; Huan Liang; Zhi Li; Da Zheng; Huapeng Chen; Xinxin Wang; Chaoyue Deng; Wenyan Lin; Changlin Chen; Junlong Sun; Li Zhou; Jian Luo (Aquaculture, 2025)

Unprecedented short-circuit current density and efficiency of vacuum-deposited organic solar cells based on 8H-thieno[2′,3′:4,5]thieno[3,2-b] thieno[2,3-d]pyrrole - Bin-Wen Chen; Ming-Wei An; Kang Wang; Sang Young Jeong; Xu Wang; Zhen-Lin Qiu; Kun Cao; Shan-Yu Zheng; Lu Wang; Han Young Woo; Da-Qin Yun; Lin-Long Deng; et al. (Science Bulletin, 2025)

Comparative efficacy of anaerobic digestion systems in removing antimicrobial resistance genes from swine wastewater - Da Sun; Xiaomin Shi; Yingbo Shen; Ying Liu; Sunlin Luo; Yongpeng Jin; Weishuai Zhai; Lu Liu; Zhaoju Deng; Chengtao Sun; Dejun Liu; Xin Yang; et al. (Journal of Hazardous Materials, 2025)

A review on the characterization of edible scaffolds for cultured meat: Physical, chemical, biocompatibility, and food safety evaluation methods - Ermie Mariano; Da Young Lee; Juhyun Lee; Yeongwoo Choi; Jinmo Park; Dahee Han; Jin Soo Kim; Ji Won Park; Seok Namkung; Sun Jin Hur (Food Chemistry, 2025)

Reduced graphene oxide prepared by cold plasma green treatment in liquid phase for fluorescence biosensing of tropomyosin in shrimp - Meixi Chen; Jun-Hu Cheng; Da-Wen Sun (Food Chemistry, 2025)

Numerical analysis on fire behaviour of concrete-filled steel tubular columns after lateral impact - Sun-Hang Ji; Wen-Da Wang; Yan-Li Shi; Jing-Xuan Wang (Engineering Structures, 2025)

Mapping of leaf lobe-related genes in melon (Cucumis melo L.) via bulked segregant analysis - Meng-Ling Zheng; Lu Yang; Ding-Ding Zuo; Rui Sun; Jing Zhang; Yan-Ge Li; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Euphytica, 2025)

Paleoclimate Fluctuations Facilitate the Biogeographical History of Endemic Species of Freshwater Crabs in China via Cycles of Introgressive Hybridisation and Habitat Isolation - Boyang Shi; Ruxiao Wang; Danhong Song; Juanjuan Xu; Lin Zhu; Yufang Sun; Rui Hu; Neil Cumberlidge; Da Pan; Hongying Sun (Journal of Biogeography, 2025)
Aim The impact of Pleistocene climate fluctuations on the biogeographical history of aquatic species has been a topic of enduring debate. This issue poses particular challenges for parapatric closely related species, especially those situated in transition zones where species assemblages occur between distinct zoogeographic boundaries. Location Eastern China. Taxon Five closely related Sinopotamon species and subspecies, S. shensiense , S. honanense , S. y. yangtsekiense , S. y. shanxianense , and S. y. tongbaiense . Methods These parapatric Sinopotamon species and subspecies, distributed along the boundary between the Palaearctic and Oriental realms in eastern China, offer an ideal model for addressing these challenges. We explored the biogeographic history of these species by conducting a comparative phylogeographic analysis using nine microsatellite loci and two mitochondrial DNA sequences, combined with morphological variation and fine‐tuned ecological niche modelling. Results Our phylogeographic analyses consistently revealed two well‐supported clades: clade A, for S. y. yangtsekiense , and clade B, which includes other species showing polyphyletic patterning and significant gene introgression. The Nanyang Basin and surrounding mountains regions (NBSM) was identified as a critical shared refuge and hybrid zone, facilitating interspecific introgression through at least two putative hybridisation events. During the Late Pleistocene glacial cycles, introgressive hybridisation of these species occurred in the NBSM, followed by rapid expansion and colonisation of heterogenous habitats during interglacial cycles, with dispersal corridors largely aligning with the local river system. In particular, the diffusion corridor of S. honanense significantly disrupted the continuous distribution of S. y. shanxianense and S. y. tongbaiense , indicating that S. honanense has replaced S. y. shanxianense and S. y. tongbaiense in the NYSM and caused a disruption in its distribution. Main Conclusions The biogeographic histories of the species in clade B are consistent with a mixing–isolation–mixing model, which suggests that populations experienced repeated introgressive hybridisation during glacial periods and regional habitat isolation during interglacial periods. Our findings represent a classic case of fine tracking biogeographical scenarios in parapatric species and provide unprecedented insights into the evolutionary radiation of the freshwater fauna that occupies zoogeographic boundaries.

Enhancing moisture transfer and quality attributes of tomato slices through synergistic cold plasma and Osmodehydration pretreatments during infrared-assisted pulsed vacuum drying - Obafemi Ibitayo Obajemihi; Jun-Hu Cheng; Da-Wen Sun (Journal of Food Engineering, 2025)

Experimental analysis and optimization of the variable valve timing on attaining high efficiency with low NOx emission of a direct-injected hydrogen engine - Feng-yu Lai; Bai-gang Sun; Shi-wei Zhang; Kang-da Wang; Qing-he Luo; Ling-zhi Bao; Felix Leach (Fuel, 2025)

Highly cost-effective wheat starch-stearic acid complexes enabled by microwave processing: Structural properties, anti-digestion, and molecular dynamics simulation - Tingting Gao; Da-Wen Sun; You Tian; Ji Ma; Fei Pan (Food Chemistry, 2025)

Leveraging zebrafish models for advancing radiobiology: Mechanisms, applications, and future prospects in radiation exposure research - Ting Xu; Fan Liu; Jiaxuan He; Peiye Xu; Junying Qu; Hanbing Wang; Jinghui Yue; Qinsi Yang; Wei Wu; Guoming Zeng; Da Sun; Xia Chen (Environmental Research, 2025)

Gaps and solutions for large scale production of cultured meat: a review on last findings - Da Young Lee; Sun Jin Hur (Current Opinion in Food Science, 2025)

Fraxetin inhibits IKKβ, blocks NF-κB pathway and NLRP3 inflammasome activation, and alleviates spleen injury in sepsis - Liwei Huangfu; Jing Wang; Da Li; Haiyang Fei; Xuan Chen; Jingquan Dong; Lan Sun (Chemico-Biological Interactions, 2025)

Controlled atmosphere storage enhances Korean melon shelf life and quality: A comparative metabolic analysis with reefer container export - Woochul Ju; Ji-Hyun Lee; Eunsu Do; Da-yeong Ko; Eungu Jee; Min-Sun Chang; Hyang Lan Eum; Haejo Yang; Kang-Mo Ku (Postharvest Biology and Technology, 2025)

Quantifying supply and demand of cultural ecosystem services from a dynamic perspective - Yuxin Zhang; Bin Fu; Juying Sun; Ramon Felipe Bicudo da Silva (Land Use Policy, 2025)

Strategic analysis of avian conservation within key areas and key species – A case study of Baiyangdian, China - Zengrui Tian; Zhenguang Lu; Da Huo; Zongjun Zhang; Qi Sun; Heng Wu; Jiaojiao Wang; Yitong Kang; Yu Xie; Yongchang Tian; Kunpeng Yi; Jianhua Hou (Journal of Environmental Management, 2025)

Dynamic analysis of green technology innovation in products and processes under supply chain competition scenarios—A study based on stochastic differential game model - Rui Sun; Da-yi He; Jing-jing Yan (Journal of Environmental Management, 2025)

Divergent responses of an armored and an unarmored dinoflagellate to ocean acidification - Wei-Ping Zhang; Shuo-Yu Zhang; Yang Zhou; Wen-Jing Sun; Shu-Feng Zhang; Jae-Seong Lee; Minghua Wang; Da-Zhi Wang (Harmful Algae, 2025)

A needle in a haystack: Projecting the climate impacts on Brazil's pulp and paper industry - Roberto Kimura; Bruno Kanieski da Silva; Changyou Sun (Forest Policy and Economics, 2025)

An advanced deep learning-driven Terahertz metamaterial sensor for distinguishing different red wines - Jingxiao Yu; Hongbin Pu; Da-Wen Sun (Chemical Engineering Journal, 2025)

Pyrite geochemistry and its implications for ore formation in reduced copper skarn systems: A case study of the Saibo deposit, Northwest China - Qing-Fei Sun; Ju-Xing Tang; Shun-Da Li; Qiu-Ming Pei; Xin-Hao Sun; Chuan Chen; Ling-Ling Gao; Xiao-Fei Du; Jin-Ling Xie (Chemical Geology, 2025)

Development of chromosome-specific potential intron polymorphism markers in watermelon - Liang-Jie Li; Ding-Ding Zuo; Meng-Ling Zheng; Lu Yang; Rui Sun; Xue‑Jie Zhu; Zhong‑Hou Zhu; Da-Long Guo (Genetic Resources and Crop Evolution, 2025)

Ultrasound-Targeted β-Catenin Gene Therapy Improves the Cardiac Function in Mice After Myocardial Infarction - Lei Yang; Tong Gao; Yu Huang; Pei-he Wang; Xin-hao Han; Jie Wu; Lei Huang; Qing-en Da; Kun-fu Ouyang; Zhen Han; Hai Tian; Lu Sun (Cardiovascular Toxicology, 2025)

Design of Deep-Sea Acoustic Vector Sensors for Unmanned Platforms - Qindong Sun; Lianglong Da (Journal of Marine Science and Engineering, 2024)
To meet the critical need for compact, multifunctional acoustic vector sensors on deep-sea unmanned platforms such as acoustic profiling buoys and underwater gliders, we have developed a novel composite resonant acoustic vector sensor capable of large-depth operations. The sensor innovatively integrates the sound pressure channel and the vector channel, and utilizes the conjugate cross-spectrum between them to effectively reduce the isotropic noise, enhance the detection of weak signals from ships, and make up for the shortcomings of a single sound pressure channel and a vector channel. Certified to function reliably at depths up to 1500 m, field sea trials confirm its efficacy in deep-sea deployments, capturing essential marine environmental noise data. Key analysis during sea trials focused on marine ambient noise levels captured at frequencies of 65 Hz, 125 Hz, 315 Hz, 400 Hz, and 500 Hz, correlating these with changes in depth. The test results revealed the following insights: (a) At the same depth, the marine environmental noise level increases as the frequency decreases; (b) At the same frequency, the marine environmental noise level decreases with increasing depth; (c) Under favorable deep-sea conditions, the marine environmental noise level reaches 55 decibels (dB) at 500 Hz; (d) Noise levels tend to increase at various frequencies when surface ships are in proximity. These findings underscore its significant potential for enhancing deep-sea acoustic surveillance and exploration.

Buffering moisture variation during cherry tomatoes preservation through deep eutectic solvent films - Hongchen Wan; Zhiwei Zhu; Da-Wen Sun (Postharvest Biology and Technology, 2024)

Multi-omics analysis of the effects of low-temperature storage on chilling injury of bitter gourd - Hongwei Wang; Ling Li; Da-Wen Sun; Lili Ma; Lichun Han; Xuelian He; Qing Wang; Christopher B. Watkins; Jinhua Zuo; Yanyan Zheng (Postharvest Biology and Technology, 2024)

Numerical investigation of free surface flow impact using an accelerated three-dimensional smoothed particle hydrodynamics - Guiyong Zhang; Xi Yang; Zhifan Zhang; Da Hui; Zhe Sun; Guangqi Liang; Peng Li (Ocean Engineering, 2024)

Phylogenomic analysis of brachyuran crabs using transcriptome data reveals possible sources of conflicting phylogenetic relationships within the group - Da Pan; Yunlong Sun; Boyang Shi; Ruxiao Wang; Peter K.L. Ng; Danièle Guinot; Neil Cumberlidge; Hongying Sun (Molecular Phylogenetics and Evolution, 2024)

Deep learning-assisted detection of psychoactive water pollutants using behavioral profiling of zebrafish embryos - Ya Zhu; Lan Li; Shaokui Yi; Rui Hu; Jianjun Wu; Jinqian Xu; Junguang Xu; Qinnan Zhu; Shijia Cen; Yuxuan Yuan; Da Sun; Waqas Ahmad; et al. (Journal of Hazardous Materials, 2024)

Instability of natural deep eutectic solvents (NADESs) induced by Amadori rearrangement and its effects on cryopreservation of yeast cells - Rui Hu; Da-Wen Sun; You Tian; Liang Xu; Libin Sun (Food Chemistry, 2024)

High sensitive Ratiometric fluorescent Aptasensor with AIE properties for Deoxynivalenol (DON) detection - Yuandong Lin; Nian Lu; Ji Ma; Jun-Hu Cheng; Da-Wen Sun (Food Chemistry, 2024)

Fabrication of Aspergillus oryzae lipase-immobilized magnetic Cu3(PO4)2∙3H2O nanoflowers for efficient synthesis of structured phospholipids - Hua-Wei Zhang; Ke Cheng; Jing-Jing Tang; Ling-Zhi Liu; Ruo-Xuan Qin; Yi-Nuo Sun; Jiang-Hua Zhang; Da-Yong Zhou (Food Bioscience, 2024)

Exploring the response mechanism of Pseudomonas plecoglossicida to high-temperature stress by transcriptomic analyses for 2-keto gluconic acid production - Da-Ming Wang; Xi Chen; Hao Guo; Qing-Hong Wang; Lei Sun; Wen-Jing Sun (Food Bioscience, 2024)

How do we decarbonize one billion vehicles by 2050? Insights from a comparative life cycle assessment of electrifying light-duty vehicle fleets in the United States, China, and the United Kingdom - Da Huo; Ben Davies; Jianxin Li; Nadine Alzaghrini; Xin Sun; Fanran Meng; Amir F.N. Abdul-Manan; Jon McKechnie; I. Daniel Posen; Heather L. MacLean (Energy Policy, 2024)

Activated carbon fiber loaded nano zero-valent iron for Microcystis aeruginosa removal: Performance and mechanisms - Guoming Zeng; Dong Liang; Xuanhao Fan; Yu He; Rui Zhang; Xiaoling Lei; Haoxuan Wei; Da Sun (Bioresource Technology, 2024)

Hydrogen peroxide priming triggers splicing memory in grape berries - Ding-Ding Zuo; Hao-Ting Sun; Lu Yang; Meng-Ling Zheng; Jing Zhang; Da-Long Guo (Plant Molecular Biology, 2024)

Elevated temperature as the dominant stressor on the harmful algal bloom-causing dinoflagellate Prorocentrum obtusidens in a future ocean scenario - Wei-Ping Zhang; Hui Wei; Shuo-Yu Zhang; Shu-Feng Zhang; Yang Zhou; Wen-Jing Sun; Jae-Seong Lee; Minghua Wang; Da-Zhi Wang (Science of The Total Environment, 2024)

Terahertz time-domain spectroscopy imaging combined with convolutional long short-term memory neural network for In situ moisture reduction prediction of particle foods during pulsed fluidized bed drying - Yuqiao Ren; Xianglu Zhu; Brijesh K. Tiwari; Da-Wen Sun (Journal of Food Engineering, 2024)

Cyanide content, nutrient composition, physicochemical properties and sensory quality of flaxseed oil bodies prepared from flaxseeds (Linum usitatissimum L.) treated with different heat treatment methods - Rui Zheng; Hui-Lin Liu; Nan-Nan Cui; Jun-Zhuo Zhou; Xin Sun; Fa-Wen Yin; Da-Yong Zhou (Food Research International, 2024)

A fluorescent Aptasensor based on magnetic-separation strategy with gold nanoclusters for Deoxynivalenol (DON) detection - Nian Lu; Ji Ma; Yuandong Lin; Jun-Hu Cheng; Da-Wen Sun (Food Chemistry, 2024)

In situ investigation of ice fractions and water states during partial freezing of pork loins and shrimps - Zhiwei Zhu; Han Zhang; Xiaohui Liu; Qingqing Zeng; Da-Wen Sun; Zhe Wang (Food Chemistry, 2024)

Boosting oxygen storage capacity of Fe-Cu bimetallic catalysts through sulfide modification for efficient and selective molecular oxygen activation - Yan Sun; Zhicheng Wang; Xiaohui Wu; Wen-Da Oh; Mingjie Huang; Tao Zhou (Chemical Engineering Journal, 2024)

Novel insights and future perspectives on the nanomedicine-mediated synergistic anticancer effect of the combination of ferroptosis and photothermal therapy - Hengkai Qi; Haiying Wang; Lu Wang; Da Sun; Minjie Wei; Zhenhua Li (Chemical Engineering Journal, 2024)

Functionalized porphyrin as a carrier bridge and a passivator for perovskite solar cells - Longchen Tao; Haitao Zhang; Xinyu Zhu; Chenhan Qi; Tianhong Ye; Niping Chen; Lixin Xiao; Baojun Li; Xufei Sun; Da-Qin Yun; Lingling Zheng (Chemical Engineering Journal, 2024)

Recent advances in shellfish toxin biosensing technologies: Micro/nano molecule- and cell-based biosensors - Ruobing Liu; Qilin Pei; Tao Sun; Fei Xu; Xi Shao; Juan Liu; Zedong Yan; Dan Wang; Yulan Tian; Da Jing (Trends in Food Science & Technology, 2024)

Thyroxine regulates pig Sertoli cell line proliferation and maturation through the IKK/NFκB and p38 MAPK signaling pathways - Jing Li; Shao-Xuan Zhang; Da-Li Wang; Jia-Jia Qi; Chun-Yan Bai; Hao Sun; Bo-Xing Sun; Shuang Liang (Theriogenology, 2024)

Analysis of stage parameters of low-temperature oxidation of water-soaked coal based on kinetic principles - Yun-chuan Bu; Hui-yong Niu; Gong-da Wang; Tian Qiu; Yan-xiao Yang; Lu-lu Sun (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Multiomics comprehensive analysis of pre-storage low-temperature on cowpea metabolism - Lichun Han; Zhengrong Wang; Qing Wang; Da-Wen Sun; Xuelian He; Hongwei Wang; Lili Ma; Chunmei Bai; Christopher B. Watkins; Jinhua Zuo; Yanyan Zheng (Postharvest Biology and Technology, 2024)

Gut antibiotic resistome during pregnancy associates with the risk of gestational diabetes mellitus: New evidence from a prospective nested case−control study - Jing Li; Zhonghan Sun; Fengjiang Sun; Yuwei Lai; Xinzhu Yi; Zhang Wang; Jiaying Yuan; Yayi Hu; An Pan; Xiong-Fei Pan; Yan Zheng; Da Chen (Journal of Hazardous Materials, 2024)

Novel cold plasma functionalized water pretreatment for improving drying performance and physicochemical properties of tomato (Solanum lycopersicum L.) fruits during infrared-accelerated pulsed vacuum drying - Obafemi Ibitayo Obajemihi; Jun-Hu Cheng; Da-Wen Sun (Journal of Food Engineering, 2024)

Experimental investigation of the matching boundary and optimization strategy of a variable geometry turbocharged direct-injected hydrogen engine - Feng-yu Lai; Bai-gang Sun; Zhi-fu Zhang; Shi-wei Zhang; Kang-da Wang; Xue-ming Ju; Qing-he Luo; Ling-zhi Bao; Felix Leach (Fuel, 2024)

Tunable thermoresponsive hydrogels for temperature regulation and warning in fruit and vegetables preservation - Libin Sun; Da-Wen Sun; Liang Xu; You Tian; Zhiwei Zhu (Food Chemistry, 2024)

Prediction of freezing point and moisture distribution of beef with dual freeze-thaw cycles using hyperspectral imaging - Qingyi Wei; Chaoying Pan; Hongbin Pu; Da-Wen Sun; Xiaolei Shen; Zhe Wang (Food Chemistry, 2024)

Dynamic performance of fiber-reinforced ultra-high toughness cementitious composites: A comprehensive review from materials to structural applications - Liangming Sun; Shuguang Liu; Hanbing Zhao; Umar Muhammad; Da Chen; Wengui Li (Engineering Structures, 2024)

Effects of cadmium on the intestinal health of the snail Bradybaena ravida Benson - Yan-Mei Da; Shun-Shun Li; Yan-Qi Li; Le-Yu Deng; Ming-Jun Li; Tao Huang; Qing-Ye Sun; Jazbia Shirin; Guo-Wei Zhou (Ecotoxicology, 2024)

Novel Sustained Release Azithromycin Resinate Fabricated by One-Pot Ion-exchange Performed in Hydro-alcoholic Solution - Hongyu Liang; Meihui Zhao; Shaoning Wang; Da Wang; Jingxin Gou; Yanjie Bai; Mingyue Shen; Junfeng Wang; Yujie Cheng; Ning Ge; Yi Zhao; Jie Zeng; et al. (AAPS PharmSciTech, 2024)

Mechanistic and synergistic aspects of ultrasonics and hydrodynamic cavitation for food processing - Jiafei Tang; Xianglu Zhu; Anet Rezek Jambrak; Da-Wen Sun; Brijesh K. Tiwari (Critical Reviews in Food Science and Nutrition, 2024)

Innovative strategy for fabricating nanomaterials to ensure food safety by cold plasma: Principles, mechanisms, and applications - Jun-Hu Cheng; Lijuan Lan; Da-Wen Sun (Trends in Food Science & Technology, 2024)

Green natural deep eutectic agents (GNDEAs) for biocryopreservation: Syntheses, properties and advanced applications - Rui Hu; Da-Wen Sun; You Tian (Trends in Food Science & Technology, 2024)

Nationwide assessment of illicit drug consumption patterns in South Korea using wastewater-based epidemiology during the COVID-19 pandemic (2020–2022) - Da-Hye Kim; Ga-Young Park; Donghyun Kim; Hae Sun Suh; Jeong-Eun Oh (Journal of Hazardous Materials, 2024)

Crusting-fabricated three-dimensional soy-based scaffolds for cultured meat production: A preliminary study - Ermie Mariano; Da Young Lee; Seung Hyeon Yun; Juhyun Lee; Yeong Woo Choi; Jinmo Park; Dahee Han; Jin Soo Kim; Inho Choi; Sun Jin Hur (Food Chemistry, 2024)

Metformin modulates mitochondrial autophagy in renal tubular epithelial injury induced by high glucose via the Keap1/Nrf2 pathway - Da Sun; Huimin Li; Yinke Du; Ying Chen; Li Yao; Lining Wang (Molecular and Cellular Biochemistry, 2024)

BDM: An Assessment Metric for Protein Complex Structure Models Based on Distance Difference Matrix - Jiaqi Zhai; Wenda Wang; Ranxi Zhao; Daiwen Sun; Da Lu; Xinqi Gong (Interdisciplinary Sciences: Computational Life Sciences, 2024)

Variation in leaf N allocation and mesophyll conductance to CO2 in four tree species under low soil P stress in subtropical China - Jingchao Tang; Baodi Sun; Ruimei Cheng; Zuomin Shi; Da Luo; Shirong Liu; Mauro Centritto (Acta Physiologiae Plantarum, 2024)

Green technologies for bio-refinery in marine crustacean shell valorisation from chitin perspective - Wenrui Dong; Jiafei Tang; Janna Cropotova; Da-Wen Sun; Brijesh K. Tiwari (Trends in Food Science & Technology, 2024)

Fast real-time monitoring of meat freshness based on fluorescent sensing array and deep learning: From development to deployment - Yuandong Lin; Ji Ma; Da-Wen Sun; Jun-Hu Cheng; Chenyue Zhou (Food Chemistry, 2024)

Engineering marine phospholipid nanoliposomes via glycerol-infused proliposomes: Mechanisms, strategies, and versatile applications in scalable food-grade nanoliposome production - Dong-wen Fu; Hang Xu; Rui-qi Sun; Xue-li Liu; Zhe Ji; Da-yong Zhou; Liang Song (Food Chemistry, 2024)

Surface charge accumulation of functionalized carbonized polymer dots selectively induces lysosomal membrane permeabilization of breast cancer cells - Yu Lei; Bao-Hua Tian; Xin-Xin Li; Ming-Yuan Sun; Xi-Lin Guo; Yi-Da Wang; Hui-Qing Zhou; Ri-Sheng Ma; Hai-Xia Liang (Chemical Engineering Journal, 2024)

Polyacrylonitrile In-Situ reinforced polyimide superhydrophobic porous fibers: A miraculous thermal insulation and flame-retardant material - Xinbin Ji; Yulong Xiang; Jing Guo; Fucheng Guan; Xiaoqing Xiong; Da Bao; Qiang Yang; Minghan Li; Yihang Zhang; Zheng Li; Jianbin Sun (Chemical Engineering Journal, 2024)

The A subunit of vacuolar H+-ATPase gene (CmVHA-A) plays opposite roles in plant growth and drought tolerance of chrysanthemum under different growing conditions - Yan-Hong Liu; Zhen-Hao Zou; Man-Man Zhang; Zhang-Ji Guan; Lian-Da Du; Da-Gang Hu; Cheng-Shu Zheng; Cui-Hui Sun (Plant Science, 2024)

Corrigendum to “Analysis of commercial fetal bovine serum (FBS) and its substitutes in the development of cultured meat” [Food Res. Int.174P1 (2023) 113617] - Da Young Lee; Seung Hyeon Yun; Seung Yun Lee; Juhyun Lee; Ermie Jr. Mariano; Seon‑Tea Joo; Inho Choi; Jung Seok Choi; Gap‑Don Kim; Jihyun Lee; Seong-Ho Choi; Sun Jin Hur (Food Research International, 2024)

In-situ investigation of supercooling behaviour during high-pressure shift freezing of pure water and sucrose solution - Zhiwei Zhu; Jiayu Mai; Tian Li; Da-Wen Sun; Qingqing Zeng; Xiaohui Liu; Zhe Wang (Food Chemistry, 2024)

Developing a magnetic SERS nanosensor utilizing aminated Fe-Based MOF for ultrasensitive trace detection of organophosphorus pesticides in apple juice - Nengjing Yang; Hongbin Pu; Da-Wen Sun (Food Chemistry, 2024)

A novel acceleration approach to shadow calculation based on sunlight channel for urban building energy modeling - Zhaoru Liu; Xin Zhou; Xiaohan Shen; Hongsan Sun; Da Yan (Energy and Buildings, 2024)

Simulation of saturated–unsaturated seepage problems via the virtual element method - Yinghao Sun; Da Li; Lei Jiao; Zhongxin Liu; Yun Yang; Junda Lyu; Shan Lin (Computers and Geotechnics, 2024)

The effect of extracellular polymeric substances on MICP solidifying rare earth slags and stabilizing Th and U - Chang-xiong Zou; Zhen-bo Sun; Wei-da Wang; Tan Wang; Yan-xin Bo; Zhe Wang; Chun-li Zheng (World Journal of Microbiology and Biotechnology, 2024)

Correction: Structure and Function of Cationic and Ionizable Lipids for Nucleic Acid Delivery - Da Sun; Zheng-Rong Lu (Pharmaceutical Research, 2024)

Perfluoroalkyl sulfonate induces cardiomyocyte apoptosis via endoplasmic reticulum stress activation and autophagy flux inhibition - Yuanhao Wang; Da Yin; Xin Sun; Wei Zhang; Huan Ma; Jingnan Huang; Chuanbin Yang; Jigang Wang; Qingshan Geng (Science of The Total Environment, 2024)

Melatonin enhances vase life and alters physiological responses in peony (Paeonia lactiflora Pall.) cut flowers - Yuxuan Wang; Xiaofei Liu; Miao Sun; Wei Zhu; Yanyi Zheng; Shaocai Zhu; Le Chen; Xi Chen; Jaime A. Teixeira da Silva; Gangqiang Dong; Xiaonan Yu (Postharvest Biology and Technology, 2024)

Soil water potential measurement using fiber-optic sensing technique - Jin-Jian Xu; Chao-Sheng Tang; Qing Cheng; Farshid Vahedifard; Da-Zhan Zhang; Chang Sun; Bin Shi (Journal of Hydrology, 2024)

Enhancing hydrochar production and mitigating heavy metal risks in sewage sludge: The role of ultrasonic pretreatment in hydrothermal carbonization - Chenyu Wang; Weibo Sun; Chao He; Xiaolong Ling; Xiaojun Zuo; Wen-Da Oh; Chaoyue Wu; Houhu Zhang (Journal of Environmental Chemical Engineering, 2024)

Effects of different isochoric freeze-thaw cycles on the physicochemical quality attributes of chicken breast meat - Tsekwi Gracious Rinwi; Da-Wen Sun; Ji Ma; Qi-Jun Wang (Food Bioscience, 2024)

A novel shadow calculation approach based on multithreaded parallel computing - Xin Zhou; Xiaohan Shen; Zhaoru Liu; Hongsan Sun; Jingjing An; Da Yan (Energy and Buildings, 2024)

Cactus-inspired bilayer cooler for high-performance and long-term daytime passive cooling - Liang Xu; Da-Wen Sun; You Tian; Libin Sun; Zhiwei Zhu (Chemical Engineering Journal, 2024)

Porous-carbon/manganese composite catalyst transformed from waste biomass as peroxymonosulfate activator for carbamazepine degradation - Quanfeng Wang; Zhenglin Li; Jujiao Zhao; Ming Zhu; Haoxuan Wei; Demin Yang; Xiaoling Lei; Da Sun; Cenhui Liao (Bioresource Technology, 2024)

Novel analysis of food processes by terahertz spectral imaging: A review of recent research findings - Ying Fu; Yuqiao Ren; Da-Wen Sun (Trends in Food Science & Technology, 2024)

Special chemical reactions combined with SERS techniques for improving detection of trace and Raman-inactive food contaminants: Principles and applications - Hongbin Pu; Qihong Ouyang; Da-Wen Sun (Trends in Food Science & Technology, 2024)

A comparative study on the nutritional composition, protein structure and effects on gut microbiota of 5 fermented soybean products (FSPs) - Xinyu Miao; Honghong Niu; Mubai Sun; Xin Dong; Mei Hua; Ying Su; Jinghui Wang; Da Li (Food Research International, 2024)

Terminal value: A crucial and yet often forgotten element in timber harvest scheduling and timberland valuation - Bruno Kanieski da Silva; Fatemeh Rezaei; Shaun Tanger; Jesse Henderson; Eric McConnell; Changyou Sun (Forest Policy and Economics, 2024)

Unveiling microwave and Roasting-Steam heating mechanisms in regulating fat changes in pork using cell membrane simulation - Fengli Lian; Jun-Hu Cheng; Ji Ma; Da-Wen Sun (Food Chemistry, 2024)

Visible detection of chilled beef freshness using a paper-based colourimetric sensor array combining with deep learning algorithms - Yuandong Lin; Ji Ma; Jun-Hu Cheng; Da-Wen Sun (Food Chemistry, 2024)

Comparative elucidation of bioactive and antioxidant properties of red dragon fruit peel as affected by electromagnetic and conventional drying approaches - Edidiong Joseph Bassey; Jun-Hu Cheng; Da-Wen Sun (Food Chemistry, 2024)

Deep eutectic solvents (DESs) films based on gelatin as active packaging for moisture regulation in fruit preservation - Hongchen Wan; Zhiwei Zhu; Da-Wen Sun (Food Chemistry, 2024)

Dual-bioinspired and ultra-flexible photothermal eutectogels for highly efficient passive anti-freezing - You Tian; Da-Wen Sun; Liang Xu; Libin Sun; Rui Hu (Chemical Engineering Journal, 2024)

Low-frequency Stimulation at the Subiculum Prevents Extensive Secondary Epileptogenesis in Temporal Lobe Epilepsy - Yujia Shen; Yiwei Gong; Xiaoli Da; Shajing Gao; Shuo Zhang; Minjuan Sun; Yuanzhi Yang; Xiaoyun Qiu; Menghan Li; Yang Zheng; Fan Fei; Yi Wang; et al. (Neuroscience Bulletin, 2024)

Scientific Advances and Weather Services of the China Meteorological Administration’s National Forecasting Systems during the Beijing 2022 Winter Olympics - Guo Deng; Xueshun Shen; Jun Du; Jiandong Gong; Hua Tong; Liantang Deng; Zhifang Xu; Jing Chen; Jian Sun; Yong Wang; Jiangkai Hu; Jianjie Wang; et al. (Advances in Atmospheric Sciences, 2024)

Sedimentary Environment, Tectonic Setting, and Uranium Mineralization Implications of the Yimin Formation, Kelulun Depression, Hailar Basin, China - Fanmin Meng; Fengjun Nie; Fei Xia; Zhaobin Yan; Da Sun; Wenbo Zhou; Xin Zhang; Qing Wang (Journal of Marine Science and Engineering, 2024)
The sandstone-type uranium deposit of the Kelulun Depression is the first industrially valuable uranium deposit discovered in the Hailar Basin. This study performed a systematic examination of 17 sandstone samples from the Yimin Formation in the Kelulun Depression based on various analytical techniques. The findings of the current study were synthesized with previous research to investigate the impact of the redox conditions and the tectonic background of the source area, as well as the paleoclimatic evolution of the Yimin Formation on uranium mineralization. The elemental Mo, U/Th, V/Cr, Ni/Co, and V/(V + Ni) ratios indicate that the paleowater was in an oxygen-rich environment during the deposition of the Yimin Formation. Additionally, the C-value, Sr/Cu, Al2O3/MgO, and Rb/Sr ratios indicate that the Yimin Formation was formed in a paleoclimate characterized by arid-to-semi-arid conditions. The geochemical characteristics of the observed elements indicated that the sediment source of the Yimin Formation was mainly felsic rocks from the upper continental crust, the weathering of the rock was weak, and the tectonic background was a passive continental margin. Coffinite is distributed in the form of cementation and stellates within or around pyrite crystals, and uranium-titanium oxide is mostly distributed in an irregular granular distribution in the biotite cleavage fractures of the study area. In summary, the findings of this study reveal that the tectonic settings, provenance, uranium source, paleoclimate, and oxygen-rich paleowater of the Yimin Formation have important geological significance for the large-scale uranium mineralization of the Kelulun Depression.

Identification, distribution, bactericidal and immunoregulatory activities of NK-lysins in grass carp (Ctenopharyngodon idella) - Gai Ling Wang; En Zhong Li; Da Hong Li; Ming Cheng Wang; Shan Shan Sun; Run Yan Xiong; Chuan Feng Li; Bao Jian Sun; Hai Xia Xie (Aquaculture, 2024)

Photothermal detection of food hazards using temperature as an indicator: Principles, sensor developments and applications - Xijia Zhang; Hongbin Pu; Da-Wen Sun (Trends in Food Science & Technology, 2024)

2D Bi2MoO6 nanosheets immobilized on electrospun 1D LaFeO3 hollow nanofibers: An efficacious direct Z-scheme p-n type heterojunction photocatalyst for removal of organic contaminants under visible-light irradiation - Da Xu; Feng Sun; Feng Liu; Hong Shao; Wurigamula He; Lili Wang; Qianli Ma; Wensheng Yu; Hui Yu; Xiangting Dong (Journal of Environmental Chemical Engineering, 2024)

The burgeoning importance of PIWI-interacting RNAs in cancer progression - Xinpei Deng; Tianle Liao; Jindong Xie; Da Kang; Yiwei He; Yuying Sun; Zhangling Wang; Yongluo Jiang; Xuan Miao; Yixuan Yan; Hailin Tang; Lewei Zhu; et al. (Science China Life Sciences, 2024)

MdPRX34L, a class III peroxidase gene, activates the immune response in apple to the fungal pathogen Botryosphaeria dothidea - Yu-Wen Zhao; Wan-Kun Li; Chu-Kun Wang; Quan Sun; Wen-Yan Wang; Xiao-Yu Huang; Ying Xiang; Da-Gang Hu (Planta, 2024)

Intravitreal Delivery of PEGylated-ECO Plasmid DNA Nanoparticles for Gene Therapy of Stargardt Disease - Da Sun; Wenyu Sun; Song-Qi Gao; Jonathan Lehrer; Hong Wang; Ryan Hall; Zheng-Rong Lu (Pharmaceutical Research, 2024)

Minimizing polyphenols and enzymes degradation using hydrogel packaging with combined evaporative and daytime radiative cooling functions during ambient transportation - Liang Xu; Da-Wen Sun; You Tian; Zhiwei Zhu (Food Chemistry, 2024)

Enhancing microorganism inactivation performance through optimization of plate-to-plate dielectric barrier discharge cold plasma reactors - Xiao Yang; Jun-Hu Cheng; Da-Wen Sun (Food Control, 2024)

Molecular and morphological evidences for the hybrid origin of Kushui Rose - Fan Zhao; Ying Wang; Yu-jie Zhang; Kun Sun; Ling-ling Da; Hui Zhang (Genetic Resources and Crop Evolution, 2024)

Role of probiotics/synbiotic supplementation in glycemic control: A critical umbrella review of meta-analyses of randomized controlled trials - Dengfeng Xu; Lingmeng Fu; Da Pan; YiFang Chu; Meiyuan Feng; Yifei Lu; Chao Yang; Yuanyuan Wang; Jiayue Xia; Guiju Sun (Critical Reviews in Food Science and Nutrition, 2024)

High-performance pulse light stable perovskite indoor photovoltaics - Chen Li; Haoxuan Sun; Min Wang; Shan Gan; Da Dou; Liang Li (Science Bulletin, 2024)

Comparison of the poisoning mechanism of different zinc species on Nb-Doped Ce-Ti SCR catalysts - Ye Jiang; Xin Sun; Guomeng Zhang; Yichao Xu; Xiao Dou; Yanan Liu; Da Han; Zhengda Yang (Fuel, 2024)

A durian-shaped multilayer core-shell SERS substrate for flow magnetic detection of pesticide residues on foods - Mingchun Lv; Hongbin Pu; Da-Wen Sun (Food Chemistry, 2024)

The associations between high-levels of urine benzophenone-type UV filters (BPs) and changes in serum lipid concentrations - Qi Chen; Qianyu Chen; Guanyong Su; Da Chen; Zhen Ding; Hong Sun (Chemosphere, 2024)

Modifying structural and techno-functional properties of quinoa proteins through extraction techniques and modification methods - Shuyang Wang; Song Miao; Da-Wen Sun (Trends in Food Science & Technology, 2024)

Chlorogenic acid ameliorates the heat stress-induced impairment of porcine Sertoli cells by suppressing oxidative stress and apoptosis - Shao-Xuan Zhang; Da-Li Wang; Jia-Jia Qi; Yu-Wei Yang; Hao Sun; Bo-Xing Sun; Shuang Liang (Theriogenology, 2024)

Diversification of freshwater crabs on the sky islands in the Hengduan Mountains Region, China - Bo-Yang Shi; Da Pan; Kang-Qin Zhang; Tian-Yu Gu; Darren C.J. Yeo; Peter K.L. Ng; Neil Cumberlidge; Hong-Ying Sun (Molecular Phylogenetics and Evolution, 2024)

Development of HFCVD apparatus for synthesizing diamond films with low thermal budget - Xinchang Wang; Enzhi Liu; Weihan Li; Yu Qiao; Fanghong Sun; Da Shu (Journal of Cleaner Production, 2024)

Predicting wheat gluten concentrations in potato starch using GPR and SVM models built by terahertz time-domain spectroscopy - Qingxia Li; Tong Lei; Yunlong Cheng; Xin Wei; Da-Wen Sun (Food Chemistry, 2024)

In vivo biological analysis of cold plasma on allergenicity reduction of tropomyosin in shrimp - Jun-Hu Cheng; Jilin Li; Da-Wen Sun (Food Chemistry, 2024)

Self-rehydrating and highly entangled hydrogel for sustainable daytime passive cooling - Liang Xu; Da-Wen Sun; You Tian; Libin Sun; Zhiwei Zhu (Chemical Engineering Journal, 2024)

Construction of Rh-N4 single atoms and Rh clusters dual-active sites for synergistic heterogeneous hydroformylation of olefins with ultra-high turnover frequency - Da Yang; Shu Tao; Houyu Zhu; Zhidong Wang; Wenwen Gao; Jinggang Yu; Minmin Wang; Guangxun Sun; Junxi Li; Hsiao-Chien Chen; Bin Liu; Yongming Chai; et al. (Chemical Engineering Journal, 2024)

m6A modification associated with YTHDF1 is involved in Japanese encephalitis virus infection - Xiao-han Li; Jing Chen; Yu-da Ou; Xiang Zhong; Jia-huan Hu; Rui-cong Sun; Ying-jun Lv; Jian-chao Wei; Yun Young Go; Bin Zhou (Veterinary Microbiology, 2023)

Toxic vascular effects of polystyrene microplastic exposure - Jianlong Yan; Yanbin Pan; Junbo He; Xinli Pang; Wenming Shao; Caiping Wang; Rongning Wang; Yaqiong He; Min Zhang; Juheng Ye; Chaolan Lin; Feng Lin; et al. (Science of The Total Environment, 2023)

Neurotrophic phenolic glycosides from the roots of Armoracia rusticana - Tae Hyun Lee; Da Hye Yoon; Kyoung Jin Park; Seong-Min Hong; Minji Kim; Sun Yeou Kim; Chung Sub Kim; Kang Ro Lee (Phytochemistry, 2023)

Experimental application of heterogeneous gliders communication system in South China Sea - Deyan Tian; Xiaochuan Zhang; Sichen Zou; Qindong Sun; Lianglong Da (Ocean Engineering, 2023)

Improved culture procedure for bovine muscle satellite cells for cultured meat - Seung Hyeon Yun; Da Young Lee; Seung Yun Lee; Juhyun Lee; Ermie Jr. Mariano; Seon-Tea Joo; Inho Choi; Jung Seok Choi; Gap-Don Kim; Sun Jin Hur (Food Research International, 2023)

Analysis of commercial fetal bovine serum (FBS) and its substitutes in the development of cultured meat - Da Young Lee; Seung Hyeon Yun; Seung Yun Lee; Juhyun Lee; Ermie Jr. Mariano; Seon‑Tea Joo; Inho Choi; Jung Seok Choi; Gap‑Don Kim; Jihyun Lee; Seong-Ho Choi; Sun Jin Hur (Food Research International, 2023)

Analyzing the effects of nonthermal pretreatments on the quality of microwave vacuum dehydrated beef using terahertz time-domain spectroscopy and near-infrared hyperspectral imaging - Yuqiao Ren; Ying Fu; Da-Wen Sun (Food Chemistry, 2023)

LF-NMR and MRI analyses of water status and distribution in pork patties during combined roasting with steam cooking - Fengli Lian; Jun-Hu Cheng; Ji Ma; Da-Wen Sun (Food Bioscience, 2023)

Effects of salinity stress on the growth performance, health status, and intestinal microbiota of juvenile Micropterus salmoides - Shukui Sun; Cuiping Gong; Chaoyue Deng; Haoran Yu; Da Zheng; Lei Wang; Junlong Sun; Feibiao Song; Jian Luo (Aquaculture, 2023)

Porous materials nanohybridized with metal nanoparticles as substrates for enhancing SERS detection in food safety applications - Qing Yang; Da-Wen Sun; Hongbin Pu (Trends in Food Science & Technology, 2023)

Solidification treatment of rare earth tailings by a renewable biological cementation method - Wei-da Wang; Tan Wang; Zhen-bo Sun; Yan-xin Bo; Chang-xiong Zou; Zhe Wang; Chun-li Zheng (Process Safety and Environmental Protection, 2023)

The ice resistance of self-centering jacket offshore platform with concrete filled double-skin legs: Experimental study and numerical analysis - Feifei Liu; Jigang Zhang; Jia Sun; Di Zhao; Da Gao; Zhehao Ma; Hanyu Song; Ruixue Wu; Weicheng Zhang (Ocean Engineering, 2023)

Effect of sulfuric acid pretreatment on flotation performance of calcite and fluorite - Ruofan Sun; Dingquan Xing; Jiushuai Deng; Da Jin; Shuai Ma; Jixing Liu; Guangsheng Li; Guanglin Qin; Xiao Liu (Minerals Engineering, 2023)

Nano light conversion agents: recent advances, future prospects and challenges in enhancing plant green cultivation - Xinru Yu; Hongbin Pu; Da-Wen Sun (Journal of Cleaner Production, 2023)

The potential of white-rot fungi for algal control: Mechanisms, Strategies, and Challenges - Haiyang Yu; Pengyu Lei; Jiahui Ma; Jiahui Jin; Yilei Ma; Yimeng Fang; Guoming Zeng; Kun Zhang; Libo Jin; Da Sun (Environmental Research, 2023)

Acceleration of state–space method based on parallelization for enhancing building thermal process simulation efficiency - Fan Bu; Xuyuan Kang; Da Yan; Ruhong Wu; Hongsan Sun; Jingjing An; Xiao Wang (Energy and Buildings, 2023)

The role of LOXL2 induced by glucose metabolism-activated NF-κB in maintaining drug resistance through EMT and cancer stemness in gemcitabine-resistant PDAC - Yun Sun Lee; Hyung Sun Kim; Hyo Jung Kim; Hyeon Woong Kang; Da Eun Lee; Myeong Jin Kim; Woosol Chris Hong; Ju Hyun Kim; Minsoo Kim; Jae-Ho Cheong; Joon Seong Park (Journal of Molecular Medicine, 2023)
Gemcitabine is considered a standard treatment for pancreatic cancer, but developing drug resistance greatly limits the effectiveness of chemotherapy and increases the rate of recurrence. Lysyl oxide-like 2 (LOXL2) is highly expressed in pancreatic cancer and is involved in carcinogenesis and EMT regulation. However, studies on the role of LOXL2 in drug resistance are limited. Here, we investigated the mechanism of LOXL2 induction and the effect of LOXL2 on EMT and CSC in gemcitabine-resistant pancreatic cancer. Glucose metabolism was activated in gemcitabine-resistant pancreatic cancer cells, and NF-κB signaling was regulated accordingly. Activated NF-κB directly induces transcription by binding to the promoters of LOXL2 and ZEB1. The EMT process was significantly inhibited by the coregulation of ZEB1 and LOXL2. In addition, LOXL2 inhibition reduced the expression of cancer stemness markers and stemness by regulating MAPK signaling activity. LOXL2 inhibits tumor growth of gemcitabine-resistant pancreatic cancer cells and increases the sensitivity to gemcitabine in mouse models. Key messages We identified a specific mechanism for inducing LOXL2 overexpression in gemcitabine-resistant pancreatic cancer. Taken together, our results suggest LOXL2 has an important regulatory role in maintaining gemcitabine resistance and may be an effective therapeutic target to treat pancreatic cancer.

Fermentation of brown seaweeds Alaria esculenta and Saccharina latissima for new product development using Lactiplantbacillus plantarum, Saccharomyces cerevisiae and kombucha SCOBY - Laura E. Healy; Xianglu Zhu; Myrsini Kakagianni; Mahesha M. Poojary; Carl Sullivan; Uma Tiwari; James Curtin; Da-Wen Sun; Brijesh K. Tiwari (Algal Research, 2023)

Evidence for the circulation of genotype 4 Eurasian avian-like lineage swine H1N1 influenza A viruses on Korean swine farms, obtained using a newly developed one-step multiplex RT-qPCR assay - Soo Hyun Moon; Woonsung Na; Seongho Shin; Hyunil Kim; Ji Yeong Noh; Seong Sik Jang; Min Chan Kim; Hyun A. Lim; Ha Yeon Kim; Da Young Mun; Sun-Woo Yoon; Hye Kwon Kim (Archives of Virology, 2023)

Review of technology and materials for the development of cultured meat - Da Young Lee; Seung Yun Lee; Jae Won Jung; Jae Hyun Kim; Dong Hun Oh; Hyun Woo Kim; Ji Hyeop Kang; Jung Seok Choi; Gap-Don Kim; Seon-Tea Joo; Sun Jin Hur (Critical Reviews in Food Science and Nutrition, 2023)

Bifacial perovskite solar cells: a universal component that goes beyond albedo utilization - Shan Gan; Haoxuan Sun; Chen Li; Da Dou; Liang Li (Science Bulletin, 2023)

Emergence and ecological transition of the Mesozoic marine reptiles: Evidence from the Early Triassic Chaohu and the Middle Triassic Xingyi Faunas - Da-yong Jiang; Min Zhou; Ryosuke Motani; Andrea Tintori; Nicholas C. Fraser; Jian-dong Huang; Olivier Rieppel; Cheng Ji; Wan-lu Fu; Zuo-yu Sun; Hao Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Flexible Au@AgNRs/CMC/qPCR film with enhanced sensitivity, homogeneity and stability for in-situ extraction and SERS detection of thiabendazole on fruits - Bingxue Hu; Hongbin Pu; Da-Wen Sun (Food Chemistry, 2023)

Alternative and legacy flame retardants in marine mammals from three northern ocean regions - Michelle L. Berger; Susan D. Shaw; Charles B. Rolsky; Da Chen; Jiachen Sun; Aqqalu Rosing-Asvid; Sandra Magdalena Granquist; Malene Simon; Britt-Marie Bäcklin; Anna Maria Roos (Environmental Pollution, 2023)

Lateral impact behaviour of post-fire steel-reinforced concrete-filled steel tubular members: Experiment and evaluation method - Sun-Hang Ji; Wen-Da Wang; Wensu Chen; Yan-Li Shi; Wei Xian (Engineering Structures, 2023)

Construction of a novel ferrihydrite/MoS2 heterogeneous Fenton-like catalyst for efficient degradation of organic pollutants under neutral conditions - Da Chang; Juanjuan Sun; Chang Wang; Linlin Hao; Ming Zeng (Environmental Science and Pollution Research, 2023)

Regulating ice formation for enhancing frozen food quality: Materials, mechanisms and challenges - Libin Sun; Zhiwei Zhu; Da-Wen Sun (Trends in Food Science & Technology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Improving the performance of incineration fly ash as cement admixture by high-temperature sintering and its toxic leaching characteristics - Xiaodong Ma; Tingshu He; Yongqi Da; Yongdong Xu; Fengwa Zhao; Yuhao Sun; Renhe Yang (Journal of Cleaner Production, 2023)

Isoreticular chemistry guided enzymodynamic domino effect for biofilm microenvironment-responsive disinfection - Lunjie Huang; Hongbin Pu; Da-Wen Sun (Chemical Engineering Journal, 2023)

The effects of plastic mulching and different fertilization on soil nutrients, yield and soil microbiome in maize field - Qinglan Hu; Jingui Wang; Yizhuo Da; Yi Sun (Cereal Research Communications, 2023)

Characterisation of laminarin extracted from brown seaweed Laminaria digitata, using optimized ultrasound- and ultrafiltration-assisted extraction method - Xianglu Zhu; Laura Healy; Janith Wanigasekara; Ming Zhao; Ramesh Babu Padamati; Shanmugapriya Karuppusamy; James F. Curtin; Saravana Periaswamy Sivagnanam; Dilip K. Rai; Da-Wen Sun; Brijesh K. Tiwari (Algal Research, 2023)

Advancements in recyclable photocatalytic semiconductor substrates for SERS detection in food safety applications - Hongbin Pu; Tianxing Fang; Zhihui Wu; Da-Wen Sun (Trends in Food Science & Technology, 2023)

Feature construction methods for processing and analysing spectral images and their applications in food quality inspection - Hongbin Pu; Jingxiao Yu; Da-Wen Sun; Qingyi Wei; Zhe Wang (Trends in Food Science & Technology, 2023)

In-situ indirect measurements of real-time moisture contents during microwave vacuum drying of beef and carrot slices using terahertz time-domain spectroscopy - Yuqiao Ren; Tong Lei; Da-Wen Sun (Food Chemistry, 2023)

Simultaneous sensing of ammonia and temperatures using a dual-mode freshness indicator based on Au/Cu nanoclusters for packaged seafood - Wenyang Zhang; Da-Wen Sun; Ji Ma; Zhiming Wang; Anjun Qin; Ben Zhong Tang (Food Chemistry, 2023)

Dual-signal fluorescent test strips for spoilage sensing of packaged seafood: Visual monitoring of volatile basic nitrogens - Wenyang Zhang; Ji Ma; Da-Wen Sun (Food Chemistry, 2023)

A pH-Responsive colourimetric sensor array based on machine learning for real-time monitoring of beef freshness - Yuandong Lin; Ji Ma; Da-Wen Sun; Jun-Hu Cheng; Qijun Wang (Food Control, 2023)

Adaptation to hypoxic stress involves amino acid metabolism: A case in sea cucumber - Da Huo; Libin Zhang; Hongsheng Yang; Lina Sun (Environmental Pollution, 2023)

Phthalate exposure with sperm quality among healthy Chinese male adults: The role of sperm cellular function - Pan Yang; Lang-Jing Deng; Jin-Ying Xie; Xiao-Jie Li; Xiao-Na Wang; Bin Sun; Tian-Qing Meng; Cheng-Liang Xiong; Yi-Chao Huang; Yi-Xin Wang; An Pan; Da Chen; et al. (Environmental Pollution, 2023)

Mechanisms of interactions in pattern-recognition of common glycostructures across pectin-derived heteropolysaccharides by Toll-like receptor 4 - Gyu Hwan Hyun; In Ho Cho; Yoon Young Yang; Da-Hye Jeong; Yun Pyo Kang; You-Sun Kim; Seul Ji Lee; Sung Won Kwon (Carbohydrate Polymers, 2023)

Short-chain fatty acids (SCFAs) as potential resuscitation factors that promote the isolation and culture of uncultured bacteria in marine sediments - Chun-Shui Sun; Liu-Yan Zhou; Qi-Yun Liang; Xiao-Man Wang; Yi-Xuan Lei; Zhen-Xing Xu; Feng-Qing Wang; Guan-Jun Chen; Zong-Jun Du; Da-Shuai Mu (Marine Life Science & Technology, 2023)
Many marine bacteria are difficult to culture because they are dormant, rare or found in low-abundances. Enrichment culturing has been widely tested as an important strategy to isolate rare or dormant microbes. However, many more mechanisms remain uncertain. Here, based on 16S rRNA gene high-throughput sequencing and metabolomics technology, it was found that the short-chain fatty acids (SCFAs) in metabolites were significantly correlated with uncultured bacterial groups during enrichment cultures. A pure culture analysis showed that the addition of SCFAs to media also resulted in high efficiency for the isolation of uncultured strains from marine sediments. As a result, 238 strains belonging to 10 phyla, 26 families and 82 species were successfully isolated. Some uncultured rare taxa within Chlorobi and Kiritimatiellaeota were successfully cultured . Amongst the newly isolated uncultured microbes, most genomes, e.g. bacteria, possess SCFA oxidative degradation genes, and these features might aid these microbes in better adapting to the culture media. A further resuscitation analysis of a viable but non-culturable (VBNC) Marinilabiliales strain verified that the addition of SCFAs could break the dormancy of Marinilabiliales in 5 days, and the growth curve test showed that the SCFAs could shorten the lag phase and increase the growth rate. Overall, this study provides new insights into SCFAs, which were first studied as resuscitation factors in uncultured marine bacteria. Thus, this study can help improve the utilisation and excavation of marine microbial resources, especially for the most-wanted or key players.

Revealing the influence of microbiota on the flavor of kombucha during natural fermentation process by metagenomic and GC-MS analysis - Lingyun Yao; Jing Zhang; Jun Lu; Da Chen; Shiqing Song; Huatian Wang; Min Sun; Tao Feng (Food Research International, 2023)

Microscale Modelling of Flow, Heat and Mass Transport During Vacuum Cooling of Porous Foods: Effective Property Computation - Clement Kehinde Ajani; Zhiwei Zhu; Da-Wen Sun (Transport in Porous Media, 2023)
A microscale modelling framework to compute effective properties related to flow, heat and mass transfer during vacuum cooling (VC) of porous foods was developed. A heterogeneous computational domain reconstructed from steamed bread (SB) was used for modelling, while the cellular water transport in SB investigated using nuclear magnetic resonance was applied for model validation. The computed porosity (63.47 ± 1.05%), effective permeability (1.91 ± 0.39 × 10 −11 m 2 ), effective thermal conductivity, (0.33 ± 0.08 W m −1 K −1 ), and effective diffusivity (5.56 × ± 0.24 10 −8 m 2 s −1 ) were in the same range as those measured from the experiment/literature. Also, the analysis revealed that microstructural variability significantly affected the estimated effective properties. The microscale model yielded results similar to the lumped formulation but provided details not visible in the latter. Therefore, the developed model provides a framework for multiscale modelling, which could lead to a better understanding of the underlying moisture loss mechanisms during VC.

Novel biorefinery process for extraction of laminarin, alginate and protein from brown seaweed using hydrodynamic cavitation - Xianglu Zhu; Laura Healy; Rahel Suchintita Das; M.L. Bhavya; Shanmugapriya Karuppusamy; Da-Wen Sun; Colm O'Donnell; Brijesh K. Tiwari (Algal Research, 2023)

Octyl gallate targeting the 3C-like protease exhibits highly efficient antiviral activity against swine enteric coronavirus PEDV - Mingjun Su; Baishuang Yin; Xiaoxu Xing; Zijian Li; Jiyu Zhang; Shufeng Feng; Lu Li; Feiyu Zhao; Xu Yang; Shiping Yu; Jun Wang; Yongchen Zhang; et al. (Veterinary Microbiology, 2023)

Environmentally friendly self-assembly strategy to fabricate novel S and O co-doped carbon nitride aerogel photocatalyst with improved photocatalytic degradation capability - Feng Sun; Da Xu; Yunrui Xie; Feng Liu; Haina Qi; Hong Shao; Ying Yang; Hui Yu; Wensheng Yu; Xiangting Dong (Journal of Environmental Chemical Engineering, 2023)

High-performance homogeneous carboxymethylcellulose-stabilized Au@Ag NRs-CMC surface-enhanced Raman scattering chip for thiram detection in fruits - Bingxue Hu; Da-Wen Sun; Hongbin Pu; Zhibin Huang (Food Chemistry, 2023)

Runx2 overexpression promotes bone repair of osteonecrosis of the femoral head (ONFH) - Hai-Jia Xu; Xiang-Zhong Liu; Lu Yang; Yu Ning; Liang-Liang Xu; Da-Ming Sun; Wen Liao; Yi Yang; Zhang-Hua Li (Molecular Biology Reports, 2023)
Background Runt-related transcription factor-2 (Runx2) has been considered an inducer to improve bone repair ability of mesenchymal stem cells (MSCs). Methods and results Twenty-four rabbits were used to establish Osteonecrosis of the femoral head (ONFH) and randomly devided into four groups: Adenovirus Runx2 (Ad-Runx2) group, Runx2-siRNA group, MSCs group and Model group. At 1 week after model establishment, the Ad-Runx2 group was treated with 5 × 107 MSCs transfected through Ad-Runx2, the Runx2-siRNA group was treated with 5 × 107 MSCs transfected through Runx2-siRNA, the MSCs group was injected with 5 × 107 untreated MSCs, and the Model group was treated with saline. The injection was administered at 1 week and 3 weeks after model establishment. The expression of bone morphogenetic protein 2 (BMP-2), Runx2 and Osterix from the femoral head was detected at 3 and 6 weeks after MSCs being injected, and Masson Trichrome Staining, Gross Morphology, X-ray and CT images observation were used to evaluate the repair effect of ONFH. The data revealed that the expression of BMP-2, Runx2 and Osterix in the Runx2-siRNA group was reduced at 3 weeks compared with the MSCs group, and then the expression further reduced at 6 weeks, but was still higher than the Model group besides Osterix; The expression of these three genes in the Ad-Runx2 group was higher than in the MSCs group. Masson Trichrome Staining, Gross Morphology and X-ray and CT images observation revealed that necrotic femoral head of the MSCs group was more regular and smooth than the Runx2-siRNA group, which has a collapsed and irregular femoral head. In the Ad-Runx2 group, necrotic femoral head was basically completely repaired and covered by rich cartilage and bone tissue. Conclusions Overexpression of Runx2 can improve osteoblastic phenotype maintenance of MSCs and promote necrotic bone repair of ONFH.

Clinical and genome-wide association analysis of chemoradiation-induced hearing loss in nasopharyngeal carcinoma - Yong-Qiao He; Lu-Ting Luo; Tong-Min Wang; Wen-Qiong Xue; Da-Wei Yang; Dan-Hua Li; Hua Diao; Ruo-Wen Xiao; Chang-Mi Deng; Wen-Li Zhang; Ying Liao; Yan-Xia Wu; et al. (Human Genetics, 2023)
Chemoradiation-induced hearing loss (CRIHL) is one of the most devasting side effects for nasopharyngeal carcinoma (NPC) patients, which seriously affects survivors’ long-term quality of life. However, few studies have comprehensively characterized the risk factors for CRIHL. In this study, we found that age at diagnosis, tumor stage, and concurrent cisplatin dose were positively associated with chemoradiation-induced hearing loss. We performed a genome-wide association study (GWAS) in 777 NPC patients and identified rs1050851 (within the exon 2 of NFKBIA ), a variant with a high deleteriousness score, to be significantly associated with hearing loss risk (HR = 5.46, 95% CI 2.93–10.18, P = 9.51 × 10 –08 ). The risk genotype of rs1050851 was associated with higher NFKBIA expression, which was correlated with lower cellular tolerance to cisplatin. According to permutation-based enrichment analysis, the variants mapping to 149 hereditary deafness genes were significantly enriched among GWAS top signals, which indicated the genetic similarity between hereditary deafness and CRIHL. Pathway analysis suggested that synaptic signaling was involved in the development of CRIHL. Additionally, the risk score integrating genetic and clinical factors can predict the risk of hearing loss with a relatively good performance in the test set. Collectively, this study shed new light on the etiology of chemoradiation-induced hearing loss, which facilitates high-risk individuals’ identification for personalized prevention and treatment.

Toxic reactive oxygen species stresses for reconfiguring central carbon metabolic fluxes in foodborne bacteria: Sources, mechanisms and pathways - Jun-Hu Cheng; Sang Zou; Ji Ma; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2023)

Analysis and detection using novel terahertz spectroscopy technique in dietary carbohydrate-related research: Principles and application advances - Qingxia Li; Tong Lei; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2023)

Applications of machine learning techniques for enhancing nondestructive food quality and safety detection - Yuandong Lin; Ji Ma; Qijun Wang; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2023)

Exposure to legacy and alternative flame retardants in two harbor seal populations and the association with blubber fatty acid profiles - Long Zhang; Xiaoshi Zheng; Susan Shaw; Michelle Berger; Anna Roos; Britt-Marie Bäcklin; Jiachen Sun; Xiaotu Liu; Da Chen (Science of The Total Environment, 2023)

Transcatheter closure of perimembranous ventricular septal defect using a novel fully bioabsorbable occluder: multicenter randomized controlled trial - Shouzheng Wang; Zefu Li; Yunbing Wang; Tianli Zhao; Xuming Mo; Taibing Fan; Jianhua Li; Tao You; Rundi Deng; Wenbin Ouyang; Weiwei Wang; Chuangnian Zhang; et al. (Science Bulletin, 2023)

Effects of dielectric barrier discharge cold plasma on structure, surface hydrophobicity and allergenic properties of shrimp tropomyosin - Jun-Hu Cheng; Jilin Li; Da-Wen Sun (Food Chemistry, 2023)

Novel sequential and simultaneous infrared-accelerated drying technologies for the food industry: Principles, applications and challenges - Obafemi Ibitayo Obajemihi; Jun-Hu Cheng; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2023)

Chemical constituents and biological activities of Artemisia argyi H.Lév. & vaniot - Yun-hong Zhang; Zhu-tao Shao; Guang-ming Bi; Yi-wei Sun; Yu-meng Wang; Da-li Meng (Natural Product Research, 2023)

Recent advances in muscle food safety evaluation: Hyperspectral imaging analyses and applications - Hongbin Pu; Qingyi Wei; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2023)

Grouping illuminants by aggregation-induced emission (AIE) mechanisms for designing sensing platforms for food quality and safety inspection - Chenyue Zhou; Ji Ma; Da-Wen Sun (Trends in Food Science & Technology, 2023)

BPA and its alternatives BPF and BPAF exaggerate hepatic lipid metabolism disorders in male mice fed a high fat diet - Fengjiang Sun; Yichao Huang; Hexia Chen; Jialing Huang; Long Zhang; Shuchao Wei; Fangyi Liu; Da Chen; Wei Huang (Science of The Total Environment, 2023)

Triterpenoids from the leaves of Abies koreana and their biological activities - Dong Jun Lee; Seong-Min Hong; Da Hye Yoon; Song Lim Ham; Jonghwan Kim; Sun Yeou Kim; Sang Un Choi; Chung Sub Kim; Kang Ro Lee (Phytochemistry, 2023)

Anti-inflammatory lignan and triterpenoid compounds from the twigs of Ligustrum lucidum - Da Hye Sim; Ngoc Khanh Vu; Duc Dat Le; Ha Ryong Kim; Eun Sook Ma; Byung Sun Min; Mi Hee Woo (Phytochemistry Letters, 2023)

Effects of pretreatments using plasma functionalized water, osmodehydration and their combination on hot air drying efficiency and quality of tomato (Solanum lycopersicum L.) slices - Obafemi Ibitayo Obajemihi; Okon Johnson Esua; Jun-Hu Cheng; Da-Wen Sun (Food Chemistry, 2023)

Glycation of whey protein isolate and stachyose modulates their in vitro digestibility: Promising prebiotics as functional ingredients - Guang-yao Zhang; Cong Sun; Jing-ru Song; Wei-yi Jin; Yue Tang; Da-yong Zhou; Liang Song (Food Bioscience, 2023)

A ratiometric fluorescent tag based on dual-emissive hydrophobic carbon dots for in-situ monitoring of seafood freshness - Wenyang Zhang; Da-Wen Sun; Ji Ma; Anjun Qin; Ben Zhong Tang (Analytica Chimica Acta, 2023)

Understanding gene regulation during the development of the sea cucumber Apostichopus japonicus using comparative transcriptomics - Fang Su; Shilin Liu; Lili Xing; Da Huo; Hongsheng Yang; Lina Sun (Frontiers in Marine Science, 2023)
Embryonic development, especially metamorphosis and settlement, has a major impact on the life history of marine invertebrates. Apostichopus japonicus is an economically important species of sea cucumber. In this study, we performed RNA sequencing on six key stages of A. japonicas development: fertilized eggs, blastula, gastrula, auricularia, doliolaria, and pentactula. A total of 32,353 genes were identified and annotated as a reference gene set for subsequent pairwise comparison analysis. After filtering out low-quality genes, the dynamic molecular responses to development were revealed by WGCNA. The results showed that of the 20 modules, genes in the blue, yellow, and darkslateblue modules were highly correlated with the gastrula, auricularia, and blastula stages, respectively. GO terms for “RNA” and “proteasome complex” were most significantly enriched in the blue module. In the darkslateblue and yellow module, receptors of signaling pathways and metabolic processes were significantly enriched, respectively. All DEGs were categorized into 34 terms, mainly associated with signal transduction and cellular immunity. The expression pattern of genes associated with adhesion, cell cycle, signal, transcription factor, extracellular matrix (ECM), and cytoskeleton was analyzed according to gene function. The results of this study facilitated a more comprehensive understanding of the molecular characteristics of sea cucumber embryonic development and will provide theoretical guidance for larva rearing in sea cucumber culture.

Hybodontiform sharks from Middle Triassic Chang 7 Member of the Ordos Basin, Shaanxi, North China: palaeobiological and palaeoecological significances - Jia-Chun Li; Zuo-Yu Sun; Gilles Cuny; Qing-Qiang Meng; Da-Yong Jiang (Palaeoworld, 2023)

Designing direct redox reaction chemically coupling NO and SO2 removal - Dongyue Zhao; Qiuqiao Jiang; Bo Peng; Jun Liu; Ruoyu Wang; Menglong Feng; Shangcong Sun; Hao Sha; Kai Zhu; Haitao Song; Wei Lin; Zhijian Da (Fuel, 2023)

Effects of isochoric freezing on freezing process and quality attributes of chicken breast meat - Tsekwi Gracious Rinwi; Da-Wen Sun; Ji Ma; Qi-Jun Wang (Food Chemistry, 2023)

Enhancement of Wheat Seed Germination, Seedling Growth and Nutritional Properties of Wheat Plantlet Juice by Plasma Activated Water - Junhong Wang; Jun-Hu Cheng; Da-Wen Sun (Journal of Plant Growth Regulation, 2023)
Previous studies have shown the great potential of using plasma-activated water (PAW) on improving agriculture seed germination, however, information on the influence of PAW on crop plantlet juice remains scanty. In this research, the effect of PAW generated by atmosphere pressure Ar–O 2 plasma jet for 1–5 min on wheat seed germination, seedling growth and nutritional properties of wheat plantlet juice was investigated. Results revealed that all PAWs could enhance wheat seed germination and seedling growth in 7 days by improving the germination rate, germination index, fresh weight, dry weight and vigour index, and especially that PAW activated for 3 min (PAW-3) showed the best overall performance. In addition, the application of PAWs enhanced the nutritional properties of wheat plantlet juice from those grown for 14 days by improving total soluble solids, protein content, photosynthetic pigments, total phenolic content, antioxidant activity, enzyme activity, free amino acids and minerals content, and the best enhancement was also observed in PAW-3. It was concluded that PAWs would be an effective technique to enhance the growth and nutritional properties of crop sprouts, which could be served as functional foods in many forms.

T-2 toxin-induced intestinal damage with dysregulation of metabolism, redox homeostasis, inflammation, and apoptosis in chicks - Meng Liu; Ling Zhao; Jin-Tao Wei; Yu-Xuan Huang; Mahmoud Mohamed Khalil; Wen-Da Wu; Kamil Kuča; Lv-Hui Sun (Archives of Toxicology, 2023)

Inhibitory effects of dielectric barrier discharge cold plasma on pathogenic enzymes and anthracnose for mango postharvest preservation - Yue Wu; Jun-Hu Cheng; Kevin M. Keener; Da-Wen Sun (Postharvest Biology and Technology, 2023)

Genotoxicity assessment of root extracts of Paeonia lactiflora Pall - Su-Min Bak; Seng-Min Back; Da Yeon Kim; Na-Young Jeung; Nan-Young Kim; Jun-Young Yang; Kang-Hyun Han; Yong-Bum Kim; Byung Sun Min; Byoung-Seok Lee; Seong-Hoon Park (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2023)

Physicochemical properties of nanosized biochar regulated by heat treatment temperature dictates algal responses: From the perspective of fatty acid metabolism - Yichao Huang; Jia Lv; Saibo Liu; Shishu Zhu; Wencong Yao; Jiachen Sun; Hua Wang; Da Chen; Xiaochen Huang (Journal of Hazardous Materials, 2023)

Ultrasensitive hydrogel grating detector for real-time continuous-flow detection of trace threat Pb2+ - Xiao-Yu Tian; Meng-Wei Sun; Guo-Yu Wen; Min Cao; Da-Wei Pan; Rui Xie; Xiao-Jie Ju; Zhuang Liu; Wei Wang; Liang-Yin Chu (Journal of Hazardous Materials, 2023)

Electrospun self-supporting double Z-scheme tricolor-typed microfiber oriented-heterostructure photocatalyst with highly effective hydrogen evolution and organic pollutants degradation - Feng Sun; Yunrui Xie; Da Xu; Feng Liu; Haina Qi; Qianli Ma; Ying Yang; Hui Yu; Wensheng Yu; Xiangting Dong (Journal of Environmental Chemical Engineering, 2023)

Deconstruction of pineapple peel cellulose based on Fe2+ assisted cold plasma pretreatment for cellulose nanofibrils preparation - Hong Zhu; Jun-Hu Cheng; Ji Ma; Da-Wen Sun (Food Chemistry, 2023)

Nanocellulose-based polymeric nanozyme as bioinspired spray coating for fruit preservation - Lunjie Huang; Da-Wen Sun; Hongbin Pu; Cuiyun Zhang; Daorui Zhang (Food Hydrocolloids, 2023)

Nanocomposite hydrogel for daytime passive cooling enabled by combined effects of radiative and evaporative cooling - Liang Xu; Da-Wen Sun; You Tian; Tianhao Fan; Zhiwei Zhu (Chemical Engineering Journal, 2023)

Nitric Oxide Alleviates Submergence-Induced Maize Seedling Root Tip Cell Death - Yaoqi Li; Qiong Nan; Yinai Liu; Sue Lin; Hao Ji; Da Sun; Libo Jin; Renyi Peng (Journal of Plant Growth Regulation, 2023)

Shrinkage during vacuum cooling of porous foods: Conjugate mechanistic modelling and experimental validation - Clement Kehinde Ajani; Zhiwei Zhu; Da-Wen Sun (Journal of Food Engineering, 2023)

Ca2+ATPase enzyme activities and lipid and protein oxidations of grass carp (Ctenopharyngodon idellus) stored at 4 °C for 30 min under electromagnetic fields - Swati Mahato; Da-Wen Sun; Zhiwei Zhu (Food Chemistry, 2023)

Balance the rapid release of insecticide microcapsules using double-layer shielding effect when the foliar application - Rui Wang; Song Liu; Feng-shou Sun; Xin Yu; Xiao Liu; Bei-xing Li; Wei Mu; Da-xia Zhang; Feng Liu (Chemical Engineering Journal, 2023)

Bio-interface engineering of MXene nanosheets with immobilized lysozyme for light-enhanced enzymatic inactivation of methicillin-resistant Staphylococcus aureus - Daorui Zhang; Lunjie Huang; Da-Wen Sun; Hongbin Pu; Qingyi Wei (Chemical Engineering Journal, 2023)

Control of side reactions using LiNbO3 mixed/doped solid electrolyte for enhanced sulfide-based all-solid-state batteries - Ji-Un Cho; Rajesh Rajagopal; Da Hye Yoon; Yong Joon Park; Kwang-Sun Ryu (Chemical Engineering Journal, 2023)

Structure and Function of Cationic and Ionizable Lipids for Nucleic Acid Delivery - Da Sun; Zheng-Rong Lu (Pharmaceutical Research, 2023)

Temperature and dissolved oxygen influence the immunity, digestion, and antioxidant level in sea cucumber Apostichopus japonicus - Da Huo; Fang Su; Libin Zhang; Hongsheng Yang; Lina Sun (Frontiers in Marine Science, 2022)

STING/NF-κB/IL-6-Mediated Inflammation in Microglia Contributes to Spared Nerve Injury (SNI)-Induced Pain Initiation - Jia Sun; Ya-qun Zhou; Bing-yang Xu; Jia-yan Li; Long-qing Zhang; Dan-yang Li; Shuang Zhang; Jia-yi Wu; Shao-jie Gao; Da-wei Ye; Wei Mei (Journal of Neuroimmune Pharmacology, 2022)

Germanium enrichment in sphalerite with acicular and euhedral textures: an example from the Zhulingou carbonate-hosted Zn(-Ge) deposit, South China - Kai Luo; Alexandre Cugerone; Mei-Fu Zhou; Jia-Xi Zhou; Guo-Tao Sun; Jing Xu; Kang-Jian He; Mao-Da Lu (Mineralium Deposita, 2022)

A novel hollow microsphere composite MnOx/PAA: effective catalyst for ozone decomposition at high humidity - Wei Liu; Jingwen Zhang; Zhao Dai; Ning Luo; Jing Qu; Peiyun Sun; Da Li; Weilong Liao; Junfu Wei; Huan Zhang (Environmental Science and Pollution Research, 2022)

Risk of thyroid cancer and benign nodules associated with exposure to parabens among Chinese adults in Wuhan, China - Nan-Xin Wu; Lang-Jing Deng; Feng Xiong; Jin-Ying Xie; Xiao-Jie Li; Qiang Zeng; Jia-Chen Sun; Da Chen; Pan Yang (Environmental Science and Pollution Research, 2022)

Correction: Microstructural Classification and Reconstruction of the Computational Geometry of Steamed Bread Using Descriptor‑Based Approach - Clement Kehinde Ajani; Zhiwei Zhu; Da‑Wen Sun (Transport in Porous Media, 2022)

Microstructural Classification and Reconstruction of the Computational Geometry of Steamed Bread Using Descriptor-Based Approach - Clement Kehinde Ajani; Zhiwei Zhu; Da-Wen Sun (Transport in Porous Media, 2022)
Microstructures affect the properties of food products; accurate and relatively less complex microstructural representations are thus needed for modelling of transport phenomena during food processing. Hence, the present study aimed at developing computational microstructures of steamed bread using descriptor-based approach. Relevant information was extracted from the scanning electron microscope (SEM) images of the steamed bread and evaluated using seven classifiers. For the automatic classification and using all descriptors, bagged trees ensembles (BTE) had the highest accuracy of 98.40%, while Gaussian Naïve Bayes was the least with 92.10% accuracy. In the “step forward” analysis, five descriptors had higher classification accuracy (98.80%) than all descriptors, implying that increase in descriptors might or might not increase classification accuracy. Microstructural validation revealed that the ellipse fitting method with a p value of 0.7984 for the area was found to be superior to the Voronoi method with a corresponding p value of 1.4554 × 10 −5 , confirming that the ellipse developed microstructure was more suitable for microscale modelling of transport phenomena in steamed bread.

Protective effect of nicorandil against myocardial ischemia/reperfusion injury mediated via IL33/ST2 signaling pathway - Yi Zheng; Xueyin Li; Fan Zhang; Bo Zhao; Wanting Du; Da Sun; Guangping Li (Molecular and Cellular Biochemistry, 2022)

Recent developments in vibrational spectral analyses for dynamically assessing and monitoring food dehydration processes - Yuqiao Ren; Xiaohui Lin; Tong Lei; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2022)

Recent developments in Raman spectral analysis of microbial single cells: Techniques and applications - Heera Jayan; Hongbin Pu; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2022)

Precision release systems of food bioactive compounds based on metal-organic frameworks: synthesis, mechanisms and recent applications - Mingchun Lv; Da-Wen Sun; Lunjie Huang; Hongbin Pu (Critical Reviews in Food Science and Nutrition, 2022)

Novel graphene oxide/polymer composite membranes for the food industry: structures, mechanisms and recent applications - Leyin Zeng; Zhiwei Zhu; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2022)

Designing specific bacterial 16S primers to sequence and quantitate plant endo-bacteriome - Liying Chen; Mengting Zhang; Da Liu; Hongbo Sun; Jianxiang Wu; Yan Huo; Xiaoying Chen; Rongxiang Fang; Lili Zhang (Science China Life Sciences, 2022)

Two new dammarane-type triterpenoids from the green walnut husks of Juglans mandshurica Maxim - Yuan-Yuan Zhou; Hui-Rui Gao; Hong-Juan Song; Dan-Da Ma; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Xiao-Li Wang; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2022)

COCH-related autosomal dominant nonsyndromic hearing loss: a phenotype–genotype study - Kyung Seok Oh; Daniel Walls; Sun Young Joo; Jung Ah Kim; Jee Eun Yoo; Young Ik Koh; Da Hye Kim; John Hoon Rim; Hye Ji Choi; Hye-Youn Kim; Seyoung Yu; Richard J. Smith; et al. (Human Genetics, 2022)

Differential genetic diagnoses of adult post-lingual hearing loss according to the audiogram pattern and novel candidate gene evaluation - John Hoon Rim; Byunghwa Noh; Young Ik Koh; Sun Young Joo; Kyung Seok Oh; Kyumin Kim; Jung Ah Kim; Da Hye Kim; Hye-Youn Kim; Jee Eun Yoo; Seung-Tae Lee; Jin Woong Bok; et al. (Human Genetics, 2022)
Ski-slope hearing loss (HL), which refers to increased auditory threshold at high frequencies, is common in adults. However, genetic contributions to this post-lingual HL remain largely unknown. Here, we prospectively investigated deafness-associated and novel candidate genes causing ski-slope HL. We analyzed 192 families with post-lingual HL via gene panel and/or exome sequencing. With an overall molecular diagnostic rate of 35.4% (68/192) in post-lingual HL, ski-slope HL showed a lower diagnostic rate (30.7%) compared with other conditions (40.7%). In patients who showed HL onset before the age of 40, genetic diagnostic probability was significantly lower for ski-slope HL than for other conditions. Further analysis of 51 genetically undiagnosed patients in the ski-slope HL group identified three variants in delta-like ligand 1 ( DLL1 ), a Notch ligand, which presented in vitro gain-of-function effects on Notch downstream signaling. In conclusion, genetic diagnostic rates in post-lingual HL varied according to audiogram patterns with age-of-onset as a confounding factor. DLL1 was identified as a candidate gene causing ski-slope HL.

The Impact of Fasciation on Maize Inflorescence Architecture - Da Eun Kim; Jin-hee Jeong; Yu Mi Kang; Young-Hoon Park; Yong-Jae Lee; Jum-soon Kang; Young-Whan Choi; Beung-Gu Son; Sun Tae Kim; Dave Jackson; Byoung Il Je (Journal of Plant Biology, 2022)
How functional genetics research can be applied to improving crop yields is a timely challenge. One of the most direct methods is to produce larger inflorescences with higher productivity, which should be accompanied by a balance between stem cell proliferation and lateral organ initiation in meristems. Unbalanced proliferation of stem cells causes the fasciated inflorescences, which reflect the abnormal proliferation of meristems, derived from the Latin word ‘fascis’, meaning ‘bundle’. Maize, a model system for grain crops, has shown tremendous yield improvements through the mysterious transformation of the female inflorescence during domestication. In this review, we focus on maize inflorescence architecture and highlight the patterns of fasciation, including recent progress.

Mitogenome of Knodus borki (Cypriniformes: Characidae): genomic characterization and phylogenetic analysis - Cheng-He Sun; Ya-Nan Zhang; Xiao-Shu Zeng; Da-Wei Liu; Qi Huang; Xiao-Li Zhang; Qun Zhang (Molecular Biology Reports, 2022)

Alternation of stromatolites and vertical burrows controlled by storm processes and sea-level changes in the middle Cambrian carbonates of central China - Bingchen Liu; Mingyue Dai; Yong’an Qi; Xiaofang Sun; Wei Zheng; Min Wang; Zhifeng Xing; Da Li; Yuchao Fan (Journal of Earth System Science, 2022)

Effect of Chromium Supplementation on Blood Glucose and Lipid Levels in Patients with Type 2 Diabetes Mellitus: a Systematic Review and Meta-analysis - Fengyi Zhao; Da Pan; Niannian Wang; Hui Xia; Hong Zhang; Shaokang Wang; Guiju Sun (Biological Trace Element Research, 2022)

Rapid visual detection of porcine reproductive and respiratory syndrome virus via recombinase polymerase amplification combined with a lateral flow dipstick - Xiao-Xiao Tian; Tao Wang; Xing-Yang Cui; Xin-Yi Huang; Yue Sun; Da-Song Xia; Yong-Bo Yang; Xue-Hui Cai; Tong-Qing An (Archives of Virology, 2022)

Turning depths of internal tides in the South China Sea inferred from profile data - Kun Liu; Lianglong Da; Wuhong Guo; Chenglong Liu; Junchuan Sun (Acta Oceanologica Sinica, 2022)

A new open‐path eddy covariance method for nitrous oxide and other trace gases that minimizes temperature corrections - Da Pan; Ilya Gelfand; Lei Tao; Michael Abraha; Kang Sun; Xuehui Guo; Jiquan Chen; G. Philip Robertson; Mark A. Zondlo (Global Change Biology, 2022)
Low‐power, open‐path gas sensors enable eddy covariance (EC) flux measurements in remote areas without line power. However, open‐path flux measurements are sensitive to fluctuations in air temperature, pressure, and humidity. Laser‐based, open‐path sensors with the needed sensitivity for trace gases like methane (CH 4 ) and nitrous oxide (N 2 O) are impacted by additional spectroscopic effects. Corrections for these effects, especially those related to temperature fluctuations, often exceed the flux of gases, leading to large uncertainties in the associated fluxes. For example, the density and spectroscopic corrections arising from temperature fluctuations can be one or two orders of magnitude greater than background N 2 O fluxes. Consequently, measuring background fluxes with laser‐based, open‐path sensors is extremely challenging, particularly for N 2 O and gases with similar high‐precision requirements. We demonstrate a new laser‐based, open‐path N 2 O sensor and a general approach applicable to other gases that minimizes temperature‐related corrections for EC flux measurements. The method identifies absorption lines with spectroscopic effects in the opposite direction of density effects from temperature and, thus, density and spectroscopic effects nearly cancel one another. The new open‐path N 2 O sensor was tested at a corn ( Zea mays L.) field in Southwestern Michigan, United States. The sensor had an optimal precision of 0.1 ppbv at 10 Hz and power consumption of 50 W. Field trials showed that temperature‐related corrections were 6% of density corrections, reducing EC random errors by 20‐fold compared to previously examined lines. Measured open‐path N 2 O EC fluxes showed excellent agreement with those made with static chambers ( m = 1.0 ± 0.3; r 2 = .96). More generally, we identified absorption lines for CO 2 and CH 4 flux measurements that can reduce the temperature‐related corrections by 10–100 times compared to existing open‐path sensors. The proposed method provides a new direction for future open‐path sensors, facilitating the expansion of accurate EC flux measurements.

Genetic diversity and structure of Oncomelania hupensis hupensis in two eco-epidemiological settings as revealed by the mitochondrial COX1 gene sequences - Jie-Ying Zhang; Man-Man Gu; Qiu-Fu Yu; Meng-Tao Sun; Hui-Ying Zou; Zhi-Jun Zhou; Da-Bing Lu (Molecular Biology Reports, 2022)

Sequence-dependent structural properties of B-DNA: what have we learned in 40 years? - Gabriela da Rosa; Leandro Grille; Victoria Calzada; Katya Ahmad; Juan Pablo Arcon; Federica Battistini; Genís Bayarri; Thomas Bishop; Paolo Carloni; Thomas Cheatham III; Rosana Collepardo-Guevara; Jacek Czub; et al. (Biophysical Reviews, 2021)

Relationship Between Selenium in Human Tissues and Breast Cancer: a Meta-analysis Based on Case-Control Studies - Xiaopan Zhu; Da Pan; Niannian Wang; Shaokang Wang; Guiju Sun (Biological Trace Element Research, 2021)

On the Diurnal Cycle of Heavy Rainfall over the Sichuan Basin during 10–18 August 2020 - Rudi Xia; Yali Luo; Da-Lin Zhang; Mingxin Li; Xinghua Bao; Jisong Sun (Advances in Atmospheric Sciences, 2021)
A sustained heavy rainfall event occurred over the Sichuan basin in southwest China during 10–18 August 2020, showing pronounced diurnal rainfall variations with nighttime peak and afternoon minimum values, except on the first day. Results show that the westward extension of the anomalously strong western Pacific subtropical high was conducive to the maintenance of a southerly low-level jet (LLJ) in and to the southeast of the basin, which favored continuous water vapor transport and abnormally high precipitable water in the basin. The diurnal cycle of rainfall over the basin was closely related to the periodic oscillation of the LLJ in both wind speed and direction that was caused by the combination of inertial oscillation and terrain thermal forcing. The nocturnally enhanced rainfall was produced by moist convection mostly initiated during the evening hours over the southwest part of the basin where high convective available potential energy with moister near-surface moist air was present. The convective initiation took place as cold air from either previous precipitating clouds from the western Sichuan Plateau or a larger-scale northerly flow met a warm and humid current from the south. It was the slantwise lifting of the warm, moist airflow above the cold air, often facilitated by southwest vortices and quasi-geostrophic ascent, that released the convective instability and produced heavy rainfall.

Synthesis of pyrazole-4-carboxamides as potential fungicide candidates - Cuntao Dong; Wei Gao; Xiaotian Li; Susu Sun; Jingqian Huo; Yanen Wang; Da Ren; Jinlin Zhang; Lai Chen (Molecular Diversity, 2021)

A taxonomic review of Penicillium section Charlesia - Bing-Da Sun; Cobus M. Visagie; Amanda Juan Chen; Jos Houbraken (Mycological Progress, 2021)

High-frequency sequence and sedimentary microfacies evolution characteristics of the 3rd member of the Ordovician Yingshan Formation in the Gucheng area, Tarim Basin, NW China - Chunyan Sun; Mingyi Hu; Xiao Luo; Da Gao (Arabian Journal of Geosciences, 2021)

Phytohormones in postharvest storage of fruit and vegetables: mechanisms and applications - Wenjuan Xiang; Hsiao-Wen Wang; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2021)

Pressure-related cooling and freezing techniques for the food industry: fundamentals and applications - Zhiwei Zhu; Tian Li; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2021)

Raman spectroscopic techniques for detecting structure and quality of frozen foods: principles and applications - Wenyang Zhang; Ji Ma; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2021)

Microbiogenic thrombolites from the Cambrian Miaolingian Series of southern North China Craton - Xiaofang Sun; Mingyue Dai; Yong’an Qi; Bingchen Liu; Wei Zheng; Zhifeng Xing; Min Wang; Da Li; Yuchao Fan (Carbonates and Evaporites, 2021)

Recent advances in multiscale CFD modelling of cooling processes and systems for the agrifood industry - Clement Kehinde Ajani; Zhiwei Zhu; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2021)

DNA functionalized metal and metal oxide nanoparticles: principles and recent advances in food safety detection - Xiyi Zhou; Hongbin Pu; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2021)

Synthesis of bimetallic core-shelled nanoparticles modified by 2-mercaptoethanol as SERS substrates for detecting ferbam and thiabendazole in apple puree - Nisar Hussain; Hongbin Pu; Da-Wen Sun (Food Additives & Contaminants: Part A, 2021)

Efficacy of Targeted ECO/miR-200c Nanoparticles for Modulating Tumor Microenvironment and Treating Triple Negative Breast Cancer as Non-invasively Monitored by MR Molecular Imaging - Andrew L. Schilb; Nadia R. Ayat; Amita M. Vaidya; Laura M. Hertz; Ryan C. Hall; Josef H. Scheidt; Da Sun; Zhanhu Sun; Ramamurthy Gopalakrishnan; Zheng-Rong Lu (Pharmaceutical Research, 2021)

Effects of Copper Supplementation on Blood Lipid Level: a Systematic Review and a Meta-Analysis on Randomized Clinical Trials - Shaokang Wang; Niannian Wang; Da Pan; Hong Zhang; Guiju Sun (Biological Trace Element Research, 2021)

Decreased calcium concentration interferes with life history defense strategies of Ceriodaphnia cornuta in response to fish kairomone - Jing Huang; Xiaoqing Xu; Da Li; Yunfei Sun; Lei Gu; Lu Zhang; Kai Lyu; Zhou Yang (Limnology and Oceanography, 2021)
Declining calcium in freshwater lakes has become a serious threat to aquatic organisms, which may affect the anti‐fish defense of cladocerans with high calcium demand. To evaluate the effects of low calcium on life history strategies of cladocerans for defending against fish predation, we exposed Ceriodaphnia cornuta to eight concentrations of calcium ranging from 0.5 to 50.0 mg L −1 in the absence and presence of fish kairomone, and observed the changes in body surface, recorded the key life‐history traits, and calculated the degree of its induced defense response. Results showed that, on average, low calcium (0.5, 1.0, 1.5 mg L −1 ) significantly reduced survival, maternal body size at maturation, and total offspring per female by 66.7%, 8.0%, and 48.8%, respectively, compared with those exposed to normal calcium level (10.0 mg L −1 ). At the normal calcium level, fish kairomone shortened the time to maturation, reduced maternal body size at maturation, and increased total offspring by 15.7%, 11.0%, and 29.6%, respectively, compared with those not exposed to fish kairomone. In the presence of fish kairomone, the reproduction of C. cornuta was affected by a narrower range of calcium concentrations. Calcium concentrations and fish kairomone showed a significant interaction on maternal body size at maturation, total offspring, and body size of neonates, i.e., low calcium impaired the life history defenses involved in maternal development, but enhanced the defense traits involved in reproductive performance, which indicated the diversified interference effects of decreased calcium on the life history defense strategies of C. cornuta against fish predators.

Optical nanosensors for biofilm detection in the food industry: principles, applications and challenges - Hongbin Pu; Yiwen Xu; Da-Wen Sun; Qingyi Wei; Xiaoli Li (Critical Reviews in Food Science and Nutrition, 2021)

Inhibition of fruit softening by cold plasma treatments: affecting factors and applications - Ya-Wen Pan; Jun-Hu Cheng; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2021)

Genetic characterization and phylogenetic analysis of duck-derived waterfowl parvovirus in Anhui province, eastern China - Yong Wang; Jianfei Sun; Da Zhang; Xu Guo; Wenhao Shen; Yongdong Li (Archives of Virology, 2021)

Regional climates shape the biogeographic history of a broadly distributed freshwater crab species complex - Boyang Shi; Da Pan; Yufang Sun; Xiaorui Liu; Xiulin Lv; Neil Cumberlidge; Hongying Sun (Journal of Biogeography, 2021)
Aim The evolutionary importance of paleoclimate regimes has been noted in biogeographic studies. However, little is known about how paleoclimate differences shaped the biogeographic pattern and diversification history of the freshwater fauna in important zoogeographical boundary regions. Here, we aim to investigate how past regional climatic differences have shaped the biogeographic history of the inland aquatic fauna in China using an endemic freshwater crab species complex found on both sides of the Qinling Mountains–Huaihe River Line (QHL), a critical ecological boundary in eastern China, as a model system. Location Eastern China, the Qinling Mountains–Huaihe River Line. Taxon The Sinopotamon yangtsekiense species complex. Methods A total of 482 individuals of Sinopotamon yangtsekiense sensu lato were collected from 34 localities throughout its entire distributional range. The phylogeographic analyses of population structure, morphological and genetic variations, and demographic dynamics were made based on multiple mtDNA and nuDNA loci and on morphological traits. Fine‐tuned ecological niche modeling was used to reconstruct the location of climatically suitable areas that existed during the Last Glacial Maximum. Results The divergence of two freshwater crab lineages across the QHL correlated with significant past variations in monsoon intensity and with the location of multiple refuges. The divergence time was broadly consistent with the timing of the critical paleoclimate transition event in the mid‐Pleistocene (95% HPD, 0.48–1.06 Ma). Each freshwater crab lineage has evolved distinct male genital traits associated with their isolation in areas with different precipitation rates and temperatures in the past. The patterns of crab distribution observed today reflect past contractions of the two lineages in response to glacial and interglacial cycles during the Pleistocene, followed by their subsequent rapid expansion after the Last Glacial Maximum (~15 kya). Main conclusions Populations of the widespread species Sinopotamon yangtsekiense s.l. experienced a deep division in the past that led to the phylogeographical isolation observed today. The two main drivers of genetic isolation in this taxon were (a) differences in the intensity of the monsoons on each side of the QHL boundary during the mid‐Pleistocene, and (b) isolation of different populations of S. yangtsekiense s.l. in a number of separate refuges during the LGM.

Depositional facies and diagenesis of the Lianglitage Formation in northwestern Tazhong Uplift, Tarim Basin, China: implications for the genesis of ultra-deep limestone reservoir - Da Gao; Changsong Lin; Lili Huang; Mingyi Hu; Ping Ren; Chunyan Sun; Yuru Zhao (Arabian Journal of Geosciences, 2021)

Heavy metals and health risk of rice sampled in Yangtze River Delta, China - Jian Lin; Da Sun; Ziliang Zhang; Zengqiang Duan; Jinlong Dong (Food Additives & Contaminants Part B-Surveillance, 2021)

Challenges of terrestrial shale gas exploration and development from Chang 7 shale in the Ordos Basin - Boling Pu; Feng-qin Wang; Da-zhong Dong; Jian-bo Sun (Arabian Journal of Geosciences, 2021)

The effects of low-dose biochar amendments on arsenic accumulation in rice (Oryza sativa L.) - Da Lv; Zhigang Wang; Yafei Sun; Wenjia Jin; Yongjie Wang; Limin Zhou; Xiangmin Zheng (Environmental Science and Pollution Research, 2021)

Functionalization of water as a nonthermal approach for ensuring safety and quality of meat and seafood products - Okon Johnson Esua; Jun-Hu Cheng; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2021)

Understanding the dynamical-microphysical-electrical processes associated with severe thunderstorms over the Beijing metropolitan region - Xiushu Qie; Shanfeng Yuan; Zhixiong Chen; Dongfang Wang; Dongxia Liu; Mengyu Sun; Zhuling Sun; Abhay Srivastava; Hongbo Zhang; Jingyu Lu; Hui Xiao; Yongheng Bi; et al. (Science China Earth Sciences, 2021)

Distribution of carbonate rocks and variation analysis of karst water resources in China - Wenjie Sun; Jianxin Song; Wenkai Yang; Yuejun Zheng; Chunyan Li; Da Kuang (Carbonates and Evaporites, 2020)

Systemic effect of dietary lipid levels and α-lipoic acid supplementation on nutritional metabolism in zebrafish (Danio rerio): focusing on the transcriptional level - Chen-cui Huang; Jian Sun; Hong Ji; Gen Kaneko; Xing-da Xie; Zhi-guang Chang; Wei Deng (Fish Physiology and Biochemistry, 2020)

Chemical, physical and physiological quality attributes of fruit and vegetables induced by cold plasma treatment: Mechanisms and application advances - Ya-Qi Chen; Jun-Hu Cheng; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2020)

Application of a Faecalibacterium 16S rDNA genetic marker for species identification of dog fecal waste - Kun Zhang; Da Sun; Chuanren Duan; Hang Chen; Ahmad Ud Din; Xiangjun Kong; Xian Qin; Baoyun Zhang (Environmental Science and Pollution Research, 2020)

Mixture of Pb, Zn and Cu on root permeability and radial oxygen loss in the mangrove Bruguiera gymnorrhiza - Hao Cheng; You-Shao Wang; Chang-Da Li; Zhi-Hong Ye; Shafi Muhammad; Mei-Lin Wu; Fun-Lin Sun (Ecotoxicology, 2020)

Dynamics of radial oxygen loss in mangroves subjected to waterlogging - Hao Cheng; Mei-Lin Wu; Chang-Da Li; Fu-Lin Sun; Cui-Ci Sun; You-Shao Wang (Ecotoxicology, 2020)

Combination of emerging technologies for the extraction of bioactive compounds - Le Wen; Zhihang Zhang; Da-Wen Sun; Saravana Periaswamy Sivagnanam; Brijesh K. Tiwari (Critical Reviews in Food Science and Nutrition, 2020)

Contrasting the Pb (II) and Cd (II) tolerance of Enterobacter sp. via its cellular stress responses - Zhongquan Jiang; Liu Jiang; Lin Zhang; Mu Su; Da Tian; Tong Wang; Yalin Sun; Ying Nong; Shuijin Hu; Shimei Wang; Zhen Li (Environmental Microbiology, 2020)
Summary Successful application of microorganisms to heavy metal remediation depends on their resistance to toxic metals. This study contrasted the differences of tolerant mechanisms between Pb 2+ and Cd 2+ in Enterobacter sp. Microbial respiration and production of formic acid showed that Enterobacter sp. had a higher tolerant concentration of Pb (>1000 mg l −1 ) than Cd (about 200 mg l −1 ). Additionally, SEM confirmed that most of Pb and Cd nanoparticles (NPs) were adsorbed onto cell membrane. The Cd stress, even at low concentration (50 mg l −1 ), significantly enlarged the sizes of cells. The cellular size raised from 0.4 × 1.0 to 0.9 × 1.6 μm on average, inducing a platelet‐like shape. In contrast, Pb cations did not stimulate such enlargement even up to 1000 mg l −1 . Moreover, Cd NPs were adsorbed homogeneously by almost all the bacterial cells under TEM. However, only a few cells work as ‘hot spots’ on the sorption of Pb NPs. The heterogeneous sorption might result from a ‘self‐sacrifice’ mechanism, i.e., some cells at a special life stage contributed mostly to Pb sorption. This mechanism, together with the lower mobility of Pb cations, caused higher microbial tolerance and removal efficiency towards Pb 2+ . This study sheds evident contrasts of bacterial resistance to the two most common heavy metals.

Bacteriocin of Pediococcus acidilactici HW01 Inhibits Biofilm Formation and Virulence Factor Production by Pseudomonas aeruginosa - Da-Hye Lee; Bong Sun Kim; Seok-Seong Kang (Probiotics and Antimicrobial Proteins, 2020)

Effects of high-intensity interval training on adipose tissue lipolysis, inflammation, and metabolomics in aged rats - Lei Sun; Fang-Hui Li; Tao Li; Zhu Min; Luo-Dan Yang; Hao-En Gao; Da-Shuai Wu; Tian Xie (Pflügers Archiv - European Journal of Physiology, 2020)

Relative roles of formation and preservation on gold endowment along the Sanshandao gold belt in the Jiaodong gold province, China: importance for province- to district-scale gold exploration - Liang Zhang; David I. Groves; Li-Qiang Yang; Gong-Wen Wang; Xiang-Dong Liu; Da-Peng Li; Ying-Xin Song; Wei Shan; Si-Chen Sun; Zhao-Kun Wang (Mineralium Deposita, 2020)

Differences in macrophage polarization in the adipose tissue of obese mice under various levels of exercise intensity - Kyung-Wan Baek; Da-In Lee; Shin Ae Kang; Hak Sun Yu (Journal of Physiology and Biochemistry, 2020)

Short-term PM2.5 forecasting based on CEEMD-RF in five cities of China - Da Liu; Kun Sun (Environmental Science and Pollution Research, 2019)

Choline, not folate, can attenuate the teratogenic effects ofdibutyl phthalate (DBP) during early chick embryo development - Rui Wang; Da-Guang Sun; Ge Song; Chun Yi Guan; Yi Cui; Xu Ma; Hong-Fei Xia (Environmental Science and Pollution Research, 2019)

GIS-Supported Airfield Selection near Zhongshan Station, East Antarctica, based on Multi-Mission Remote Sensing Data - Xiangbin Cui; Jiaxin Liu; Yixiang Tian; Bo Sun; Rongxing Li; Alexey Markov; Da Lv; Gang Hai; Gang Qiao; Tiantian Feng (Marine Geodesy, 2019)

Isolation and characterization of a novel strain (YH01) of Micropterus salmoides rhabdovirus and expression of its glycoprotein by the baculovirus expression system - Sun-jian Lyu; Xue-mei Yuan; Hai-qi Zhang; Wei-da Shi; Xiao-ying Hang; Li Liu; Ying-lei Wu (Journal of Zhejiang University-SCIENCE B, 2019)

Recent advances in the detection of 17β-estradiol in food matrices: A review - Hongbin Pu; Zhibin Huang; Da-Wen Sun; Haohua Fu (Critical Reviews in Food Science and Nutrition, 2019)

Arabidopsis GIGANTEA negatively regulates chloroplast biogenesis and resistance to herbicide butafenacil - Joon-Yung Cha; Da-Yeon Lee; Imdad Ali; Song Yi Jeong; Bobae Shin; Hyunjung Ji; Jung Sun Kim; Min-Gab Kim; Woe-Yeon Kim (Plant Cell Reports, 2019)

SERS detection of urea and ammonium sulfate adulterants in milk with coffee ring effect - Abid Hussain; Da-Wen Sun; Hongbin Pu (Food Additives & Contaminants: Part A, 2019)

Development of a Highly Sensitive Colorimetric Method for Detecting 17β-Estradiol Based on Combination of Gold Nanoparticles and Shortening DNA Aptamers - Hongbin Pu; Zhibin Huang; Da-Wen Sun; Xiaohui Xie; Weibiao Zhou (Water, Air, & Soil Pollution, 2019)

CaMYC, A Novel Transcription Factor, Regulates Anthocyanin Biosynthesis in Color-leaved Pepper (Capsicum annuum L.) - Bo-Ya Lu; Guo-Xin Cheng; Zhen Zhang; Jian-Tian Sun; Muhammad Ali; Qing-Li Jia; De-Xu Luo; Zhen-Hui Gong; Da-Wei Li (Journal of Plant Growth Regulation, 2019)

Rapid detection of multiple organophosphorus pesticides (triazophos and parathion-methyl) residues in peach by SERS based on core-shell bimetallic Au@Ag NPs - Tehseen Yaseen; Hongbin Pu; Da-Wen Sun (Food Additives & Contaminants: Part A, 2019)

Reduced thiamine binding is a novel mechanism for TPK deficiency disorder - Wenjie Huang; Jiao Qin; Dingdong Liu; Yan Wang; Xiaofei Shen; Na Yang; Hui Zhou; Xiao-Tang Cai; Zhi-Ling Wang; Dan Yu; Rong Luo; Qingxiang Sun; et al. (Molecular Genetics and Genomics, 2019)

Activities and conformation changes of food enzymes induced by cold plasma: A review - Yongxu Han; Jun-Hu Cheng; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2019)

Diagnostics of plasma reactive species and induced chemistry of plasma treated foods - Kexin Zhang; Camila A. Perussello; Vladimir Milosavljević; P. J. Cullen; Da-Wen Sun; Brijesh K. Tiwari (Critical Reviews in Food Science and Nutrition, 2019)

Applications of Raman spectroscopic techniques for quality and safety evaluation of milk: A review of recent developments - Huirong He; Da-Wen Sun; Hongbin Pu; Lijun Chen; Li Lin (Critical Reviews in Food Science and Nutrition, 2019)

Effects of pretreatments on quality attributes of long-term deep frozen storage of vegetables: a review - Ximing Zhan; Zhiwei Zhu; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2019)

Principles and recent applications of novel non-thermal processing technologies for the fish industry—a review - Yi-Ming Zhao; Maria de Alba; Da-Wen Sun; Brijesh Tiwari (Critical Reviews in Food Science and Nutrition, 2019)

Measurements of lycopene contents in fruit: A review of recent developments in conventional and novel techniques - Abid Hussain; Hongbin Pu; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2019)

Developments of mathematical models for simulating vacuum cooling processes for food products – a review - Zhiwei Zhu; Ying Li; Da-Wen Sun; Hsiao-Wen Wang (Critical Reviews in Food Science and Nutrition, 2019)

Influences of zinc oxide nanoparticles on Allium cepa root cells and the primary cause of phytotoxicity - Zhiqiang Sun; Tiantian Xiong; Ting Zhang; Nanfang Wang; Da Chen; Shaoshan Li (Ecotoxicology, 2019)

Time Effects on Resting EEG in Children With/Without AD/HD - Da-Wei Zhang; Stuart J. Johnstone; Hui Li; Robert J. Barry; Adam R. Clarke; Qihua Zhao; Yan Song; Lu Liu; Qiujin Qian; Yufeng Wang; Li Sun (Brain Topography, 2019)

Microsatellite records for volume 11, issue 1 - Da-Qing Chen; Zaijie Dong; Min Fang; Jianjun Fu; Xiang-Yang Jia; Bingjie Jiang; Jingmiao Li; Qingqing Li; Suhui Liao; Ping Liu; Yulin Liu; Guocheng Shu; et al. (Conservation Genetics Resources, 2019)

Application of Stable Strontium Isotope Geochemistry and Fluid Inclusion Microthermometry to Studies of Dolomitization of the Deeply Buried Cambrian Carbonate Successions in West-Central Tarim Basin, NW China - Ngong Roger Ngia; Mingyi Hu; Da Gao; Zhonggui Hu; Chun-Yan Sun (Journal of Earth Science, 2019)

Determination of dietary nitrite in patients with esophageal pre-cancerous lesion and normal people: a duplicate diet study - Ting Zhang; Da Pan; Ming Su; Ling-Meng Fu; Cai-Yun Miao; Qing-Yang Yan; Jing Wang; Li-Gang Yang; Shao-Kang Wang; Gui-Ju Sun (Food Additives & Contaminants: Part A, 2018)

Improving the quality and safety of frozen muscle foods by emerging freezing technologies: A review - Ximing Zhan; Da-Wen Sun; Zhiwei Zhu; Qi-Jun Wang (Critical Reviews in Food Science and Nutrition, 2018)

Using power ultrasound to accelerate food freezing processes: Effects on freezing efficiency and food microstructure - Peizhi Zhang; Zhiwei Zhu; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2018)

Recent advances in nanofabrication techniques for SERS substrates and their applications in food safety analysis - Xiaohui Xie; Hongbin Pu; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2018)

Recent developments in intelligent packaging for enhancing food quality and safety - Muhammad Sohail; Da-Wen Sun; Zhiwei Zhu (Critical Reviews in Food Science and Nutrition, 2018)

Carbon dots: Principles and their applications in food quality and safety detection - Jia-Huan Qu; Qingyi Wei; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2018)

Enhancing Food Processing by Pulsed and High Voltage Electric Fields: Principles and Applications - Qijun Wang; Yifei Li; Da-Wen Sun; Zhiwei Zhu (Critical Reviews in Food Science and Nutrition, 2018)

Development and evaluation of a storm surge warning system in Taiwan - Mei-Ying Lin; Wen-Yih Sun; Ming-Da Chiou; Chih-Ying Chen; Hao-Yuan Cheng; Cheng-Hsin Chen (Ocean Dynamics, 2018)

Clinacanthus nutans Mitigates Neuronal Apoptosis and Ischemic Brain Damage Through Augmenting the C/EBPβ-Driven PPAR-γ Transcription - Jui-Sheng Wu; Mei-Han Kao; Hsin-Da Tsai; Wai-Mui Cheung; Jin-Jer Chen; Wei-Yi Ong; Grace Y. Sun; Teng-Nan Lin (Molecular Neurobiology, 2018)

Uhrf2 deletion impairs the formation of hippocampus-dependent memory by changing the structure of the dentate gyrus - Xiao-Rong Chen; Shi-Cheng Sun; Shuai-Wen Teng; Liang Li; Yi-Fan Bie; Hui Yu; Da-Li Li; Zhe-Yu Chen; Yue Wang (Brain Structure and Function, 2018)

M-type thioredoxins are involved in the xanthophyll cycle and proton motive force to alter NPQ under low-light conditions in Arabidopsis - Qingen Da; Ting Sun; Menglong Wang; Honglei Jin; Mengshu Li; Dongru Feng; Jinfa Wang; Hong-Bin Wang; Bing Liu (Plant Cell Reports, 2018)

Wide phenotypic spectrum in axonal Charcot–Marie–Tooth neuropathy type 2 patients with KIF5A mutations - Da Eun Nam; Da Hye Yoo; Sun Seong Choi; Byung-Ok Choi; Ki Wha Chung (Genes & Genomics, 2018)

The phosphodiesterase-4 inhibitor roflumilast decreases ethanol consumption in C57BL/6J mice - Xin Liu; Pi-Da Hao; Ming-Feng Yang; Jing-Yi Sun; Lei-Lei Mao; Cun-Dong Fan; Zong-Yong Zhang; Da-Wei Li; Xiao-Yi Yang; Bao-Liang Sun; Han-Ting Zhang (Psychopharmacology, 2017)

Molecular identification of differential expression genes associated with sex pheromone biosynthesis in Spodoptera exigua - Ya-Nan Zhang; Long-Wa Zhang; Da-Song Chen; Liang Sun; Zhao-Qun Li; Zhan-Feng Ye; Mei-Yan Zheng; Jin-Bu Li; Xiu-Yun Zhu (Molecular Genetics and Genomics, 2017)

A new hexahydrobenzopyran derivative from the gorgonian-derived Fungus Eutypella sp - Hai-Xia Liao; Da-Wei Sun; Cai-Juan Zheng; Chang-Yun Wang (Natural Product Research, 2017)

Erratum to: International academy of agricultural and biosystems engineering (iAABE): a new instrument for recognizing the top profession - Da-Wen Sun (Paddy and Water Environment, 2017)

International academy of agricultural and biosystems engineering (iAABE): a new instrument for recognizing the top profession - Da-Wen Sun (Paddy and Water Environment, 2017)

Quality analysis, classification, and authentication of liquid foods by near-infrared spectroscopy: A review of recent research developments - Lu Wang; Da-Wen Sun; Hongbin Pu; Jun-Hu Cheng (Critical Reviews in Food Science and Nutrition, 2017)

Vis/NIR Chemical Imaging Technique for Predicting Sodium Humate Contents in Aquaculture Environment - Jia-Huan Qu; Da-Wen Sun; Hongbin Pu (Water, Air, & Soil Pollution, 2017)

Applications of Imaging Spectrometry in Inland Water Quality Monitoring—a Review of Recent Developments - Hongbin Pu; Dan Liu; Jia-Huan Qu; Da-Wen Sun (Water, Air, & Soil Pollution, 2017)

Identification of the Genetic Cause for Childhood Disintegrative Disorder by Whole-Exome Sequencing - Zhu Wen; Tian-Lin Cheng; Da-Zhi Yin; Shi-Bang Sun; Zheng Wang; Shun-Ying Yu; Yi Zhang; Zilong Qiu; Ya-Song Du (Neuroscience Bulletin, 2017)

Methods for measuring water activity ( a w ) of foods and its applications to moisture sorption isotherm studies - Lida Zhang; Da-Wen Sun; Zhihang Zhang (Critical Reviews in Food Science and Nutrition, 2017)

Non-Destructive and rapid evaluation of staple foods quality by using spectroscopic techniques: A review - Wen-Hao Su; Hong-Ju He; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2017)

Emerging techniques for assisting and accelerating food freezing processes: A review of recent research progresses - Lina Cheng; Da-Wen Sun; Zhiwei Zhu; Zi Zhang (Critical Reviews in Food Science and Nutrition, 2017)

Applications of emerging imaging techniques for meat quality and safety detection and evaluation: A review - Zhenjie Xiong; Da-Wen Sun; Hongbin Pu; Wenhong Gao; Qiong Dai (Critical Reviews in Food Science and Nutrition, 2017)

Enhanced Therapeutic Potential of Nano-Curcumin Against Subarachnoid Hemorrhage-Induced Blood–Brain Barrier Disruption Through Inhibition of Inflammatory Response and Oxidative Stress - Zong-yong Zhang; Ming Jiang; Jie Fang; Ming-feng Yang; Shuai Zhang; Yan-xin Yin; Da-wei Li; Lei-lei Mao; Xiao-yan Fu; Ya-jun Hou; Xiao-ting Fu; Cun-dong Fan; et al. (Molecular Neurobiology, 2017)

Quantitative approaches to identify floristic units and centres of species endemism in the Qinghai‐Tibetan Plateau, south‐western China - Da‐Cai Zhang; Jiang‐Xia Ye; Hang Sun (Journal of Biogeography, 2016)
Aims To determine floristic units and centres of plant species endemism using quantitative methods and different taxonomic groups. Location The Qinghai‐Tibetan Plateau in south‐western China – the world's highest and geologically youngest plateau. Methods The plateau was divided into 260 grid cells, each 1° × 1°, and the numbers of different seed‐plant taxa, including genera, total species, endemic species and alpine species, were recorded in each cell. Hierarchical clustering and non‐metric multidimensional scaling ( NMDS ) ordination were used to divide the flora quantitatively, and ANOSIM (analysis of similarities) was used to evaluate differences between the derived groups in the composition of taxa. The stress value was used to assess the fitness of the NMDS ordination. Species endemism was measured using corrected weighted endemism, and centres of species endemism were delimited on the basis of floristic units. Results The plateau harbours a total of 12,058 seed‐plant species and infraspecific taxa in 1619 genera; 38.2% of the species are endemic to the plateau and 27.7% are alpine plants. When two or four groups were considered, cluster analysis based on genera gave the best definition, whereas when 12 groups were considered, analysis of endemic species gave the best definition. The flora of the Qinghai‐Tibetan Plateau represents two floristic subkingdoms, four floristic regions and 12 floristic subregions. Three centres of species endemism were identified, associated with five floristic subregions. Main conclusions Quantitative analysis can reveal associations within a flora, and partly confirm intuitive classifications. Genera provide clear divisions of higher floristic ranks, and endemic species give the clearest classifications of lower floristic ranks. Alpine species are important taxa for classifying the flora of mountainous regions. A centre of species endemism based on a floristic unit can be conveniently identified and delimited, and the spatial scale of this centre is determined by the taxonomic rank used.

Molecular epidemiology and phylogenetic analysis of HA gene of influenza A(H1N1)pdm09 strain during 2010–2014 in Dalian, North China - Yan Han; Nan Sun; Qiu-yue Lv; Dan-hong Liu; Da-peng Liu (Virus Genes, 2016)

Comparing Four Dimension Reduction Algorithms to Classify Algae Concentration Levels in Water Samples Using Hyperspectral Imaging - Hongbin Pu; Lu Wang; Da-Wen Sun; Jun-Hu Cheng (Water, Air, & Soil Pollution, 2016)

Clinacanthus nutans Protects Cortical Neurons Against Hypoxia-Induced Toxicity by Downregulating HDAC1/6 - Hsin-Da Tsai; Jui-Sheng Wu; Mei-Han Kao; Jin-Jer Chen; Grace Y. Sun; Wei-Yi Ong; Teng-Nan Lin (NeuroMolecular Medicine, 2016)

DSePA Antagonizes High Glucose-Induced Neurotoxicity: Evidences for DNA Damage-Mediated p53 Phosphorylation and MAPKs and AKT Pathways - Kun Wang; Xiao-yan Fu; Xiao-ting Fu; Ya-jun Hou; Jie Fang; Shuai Zhang; Ming-feng Yang; Da-wei Li; Lei-lei Mao; Jing-yi Sun; Hui Yuan; Xiao-yi Yang; et al. (Molecular Neurobiology, 2016)

Amygdalin inhibits HSC-T6 cell proliferation and fibrosis through the regulation of TGF-β/CTGF - Huanhuan Luo; Liang Li; Jianbang Tang; Fengxue Zhang; Fang Zhao; Da Sun; Fengling Zheng; Xinhua Wang (Molecular & Cellular Toxicology, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

The application of catalyst-recovered SnO2 as an anode material for lithium secondary batteries - Da-Jeong Ryu; Hee-Won Jung; Sung-Hun Lee; Da-Jeong Park; Kwang-Sun Ryu (Environmental Science and Pollution Research, 2016)

Highly selective and efficient biotransformation of linarin to produce tilianin by naringinase - Pan Cui; Tong-Yi Dou; Shi-Yang Li; Jun-Xia Lu; Li-Wei Zou; Ping Wang; Yan-Ping Sun; Da-Cheng Hao; Guang-Bo Ge (Biotechnology Letters, 2016)

Isolation, identification and genomic characterization of the Asian lineage Zika virus imported to China - Yong-Qiang Deng; Hui Zhao; Xiao-Feng Li; Na-Na Zhang; Zhong-Yu Liu; Tao Jiang; Da-Yong Gu; Lei Shi; Jian-An He; Hong-Jiang Wang; Zhao-Zeng Sun; Qing Ye; et al. (Science China Life Sciences, 2016)

Application of Faecalibacterium 16S rDNA genetic marker for accurate identification of duck faeces - Da Sun; Chuanren Duan; Yaning Shang; Yunxia Ma; Lili Tan; Jun Zhai; Xu Gao; Jingsong Guo; Guixue Wang (Environmental Science and Pollution Research, 2016)

Activation of anthocyanin biosynthesis by expression of the radish R2R3-MYB transcription factor gene RsMYB1 - Sun-Hyung Lim; Ji-Hye Song; Da-Hye Kim; Jae Kwang Kim; Jong-Yeol Lee; Young-Mi Kim; Sun-Hwa Ha (Plant Cell Reports, 2016)

MdSOS2L1 phosphorylates MdVHA-B1 to modulate malate accumulation in response to salinity in apple - Da-Gang Hu; Cui-Hui Sun; Mei-Hong Sun; Yu-Jin Hao (Plant Cell Reports, 2016)

Feasibility of an enhanced washing process to extract PBDEs/heavy metals/antibiotics from antibiotic resistance gene-affected soil with aqueous DNA followed by microbial augmentation - Mao Ye; Mingming Sun; Jinzhong Wan; Yu Zhao; Shanni Xie; Da Tian; Feng Hu; Huixin Li; Lianggang Zong; Fredrick Orori Kengara; Jiang Xin (Journal of Soils and Sediments, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Potential natural exposure of endangered red-crowned crane (Grus japonensis) to mycotoxins aflatoxin B1, deoxynivalenol, zearalenone, T-2 toxin, and ochratoxin A - Da-wei Liu; Hong-yi Liu; Hai-bin Zhang; Ming-chang Cao; Yong Sun; Wen-da Wu; Chang-hu Lu (Journal of Zhejiang University-SCIENCE B, 2016)

Applications of Computer Vision for Assessing Quality of Agri-food Products: A Review of Recent Research Advances - Ji Ma; Da-Wen Sun; Jia-Huan Qu; Dan Liu; Hongbin Pu; Wen-Hong Gao; Xin-An Zeng (Critical Reviews in Food Science and Nutrition, 2016)

Intranasal Delivery of Granulocyte Colony-Stimulating Factor Enhances Its Neuroprotective Effects Against Ischemic Brain Injury in Rats - Bao-liang Sun; Mei-qing He; Xiang-yu Han; Jing-yi Sun; Ming-feng Yang; Hui Yuan; Cun-dong Fan; Shuai Zhang; Lei-lei Mao; Da-wei Li; Zong-yong Zhang; Cheng-bi Zheng; et al. (Molecular Neurobiology, 2016)

Strategy to Suppress Oxidative Damage-Induced Neurotoxicity in PC12 Cells by Curcumin: the Role of ROS-Mediated DNA Damage and the MAPK and AKT Pathways - Xiao-yan Fu; Ming-feng Yang; Ming-zhi Cao; Da-wei Li; Xiao-yi Yang; Jing-yi Sun; Zong-yong Zhang; Lei-lei Mao; Shuai Zhang; Feng-ze Wang; Feng Zhang; Cun-dong Fan; et al. (Molecular Neurobiology, 2016)

RETRACTED ARTICLE: Relationship of Serum Heart-Type Fatty Acid-Binding Protein Levels and Cerebral Infarction: a Meta-analysis - Bao-Liang Sun; Ming-Feng Yang; Xiao-Yi Yang; Jing-Yi Sun; Da-Wei Li; Zong-Yong Zhang; Lei-Lei Mao; Cun-Dong Fan; Cheng-Bi Zheng; Hong-Li Gao; Feng-Ze Wang; Feng Zhang; et al. (Molecular Neurobiology, 2015)

Calcitonin Gene-Related Peptide-Induced Calcium Alginate Gel Combined with Adipose-Derived Stem Cells Differentiating to Osteoblasts - Chang-zhi Huang; Xiao-ning Yang; Da-cheng Liu; Yi-gong Sun; Xing-ming Dai (Cell Biochemistry and Biophysics, 2015)
Calcitonin gene-related peptide (CGRP) has been confirmed with induction osteoblastic differentiation, but if it can make the three-dimensional culture of adipose-derived stem cells (ADSCs) to the osteoblastic differentiation, thus constructing tissue-engineered bone rare reports. To investigate the feasibility of exogenous CGRP-induced calcium alginate gel combined with ADSCs from rabbits in three-dimensional condition to construct tissue-engineered bone. ADSCs were obtained by collagenase I digestion of the subcutaneous adipose tissue of inguinal region of New Zealand rabbits. At the third passage, cells were mixed with sodium alginate to prepare calcium alginate gel, and the cells were assigned into two-group cultivates in 24 orifice plates. ADSCs in the control group were treated with DMEM/F-12 medium supplemented with 10 −2 mol/L β-glycerophosphate sodium, 10 −7 mol/L dexamethasone, 50 mg/L ascorbic acid, 0.1 % volume fraction of fetal bovine serum. ADSCs in the experimental group were incubated with the same medium as above, and in addition 1.5 µg/L CGRP was added. The cells proliferation and the mRNA expressions of collagen I and osteocalcin were detected by MTT and RT-PCR assays, respectively and alkaline phosphatase(ALP)and calcium concentration at different induction time were detected. The cell proliferation curves were S shaped. The OD values of experimental group were higher than those of control group at 1, 3, 5, 7, 14, and 21 days after osteogenic induction ( P < 0.05). ALP and alizarin red stains of ADSCs were all positive, but golden round nodes became bigger and more in the experimental group compared with the control group after 2 weeks. At 7 and 14 days, collagen I and osteocalcin mRNA expression were greater in the experimental group than the control group. ALP and calcium concentration of experimental group were higher than that of control group at 1, 2, 3, 4 weeks after osteogenic induction ( P < 0.05). Thus, these results show that the CGRP-induced ADSCs combined with calcium alginate gel to osteoblasts differentiation.

Applications of Near-infrared Spectroscopy in Food Safety Evaluation and Control: A Review of Recent Research Advances - Jia-Huan Qu; Dan Liu; Jun-Hu Cheng; Da-Wen Sun; Ji Ma; Hongbin Pu; Xin-An Zeng (Critical Reviews in Food Science and Nutrition, 2015)

Recent Developments and Applications of Hyperspectral Imaging for Quality Evaluation of Agricultural Products: A Review - Dan Liu; Xin-An Zeng; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2015)

Identification of insecticidal constituents of the essential oils of Dahlia pinnata Cav. against Sitophilus zeamais and Sitophilus oryzae - Da-Cheng Wang; Da-Ren Qiu; Li-Na Shi; Hong-Yu Pan; Ya-Wei Li; Jin-Zhu Sun; Ying-Jie Xue; Dong-Sheng Wei; Xiang Li; Ya-Mei Zhang; Jian-Chun Qin (Natural Product Research, 2015)

Full tensor gravity gradiometry data inversion: Performance analysis of parallel computing algorithms - Zhen-Long Hou; Xiao-Hui Wei; Da-Nian Huang; Xu Sun (Applied Geophysics, 2015)

Advances in Feature Selection Methods for Hyperspectral Image Processing in Food Industry Applications: A Review - Qiong Dai; Jun-Hu Cheng; Da-Wen Sun; Xin-An Zeng (Critical Reviews in Food Science and Nutrition, 2015)

Angiopoietin-like protein 2 may mediate the inflammation in murine mastitis through the activation of interleukin-6 and tumour necrosis factor-α - Ji-Ying Wang; Hong-Bo Xiao; Zhi-Liang Sun; Da-Sheng Zhang (World Journal of Microbiology and Biotechnology, 2015)

A Potent Multi-functional Neuroprotective Derivative of Tetramethylpyrazine - Hai-Yun Chen; Da-Ping Xu; Guo-Lian Tan; Wei Cai; Gao-Xiao Zhang; Wei Cui; Jin-Zhao Wang; Cheng Long; Ye-Wei Sun; Pei Yu; Karl Wahkeung Tsim; Zai-Jun Zhang; et al. (Journal of Molecular Neuroscience, 2015)

Foxl2 of the Hong Kong catfish (Clarias fuscus): cDNA cloning, tissue distribution and changes in gene expression towards methyltestosterone, estradiol and letrozole exposure of the fries during gonadal differentiation - Si-ping Deng; Chun-hua Zhu; Jing Sun; Wen-da Wang; Tian-li Wu; Hua-pu Chen; Shang-li Shi; Guang-li Li (Genes & Genomics, 2015)

Research Developments in Methods to Reduce the Carbon Footprint of the Food System: A Review - Zhongyue Xu; Da-Wen Sun; Xin-An Zeng; Dan Liu; Hongbin Pu (Critical Reviews in Food Science and Nutrition, 2015)

Applications of Hyperspectral Imaging in Chicken Meat Safety and Quality Detection and Evaluation: A Review - Zhenjie Xiong; Anguo Xie; Da-Wen Sun; Xin-An Zeng; Dan Liu (Critical Reviews in Food Science and Nutrition, 2015)

Laboratory investigation of the microbiologically influenced corrosion (MIC) resistance of a novel Cu-bearing 2205 duplex stainless steel in the presence of an aerobic marine Pseudomonas aeruginosa biofilm - Jin Xia; Chunguang Yang; Dake Xu; Da Sun; Li Nan; Ziqing Sun; Qi Li; Tingyue Gu; Ke Yang (Biofouling, 2015)

Recovery and electrochemical performance in lithium secondary batteries of biochar derived from rice straw - Da-Jeong Ryu; Rye-Gyeong Oh; Yong-Deuk Seo; Seok-Young Oh; Kwang-Sun Ryu (Environmental Science and Pollution Research, 2015)

Recent Advances in Methods and Techniques for Freshness Quality Determination and Evaluation of Fish and Fish Fillets: A Review - Jun-Hu Cheng; Da-Wen Sun; Xin-An Zeng; Dan Liu (Critical Reviews in Food Science and Nutrition, 2015)

Effects of phenotypic and RAPD variations on ecophysiological characterization of reeds (Phragmites australis) in Suncheon Bay - In Seon Jeon; Da Som Kwon; Hoon Shin; Won Bok Kim; Na Roo Kang; Sun Mi Whang; Mi Sun Kim; Soo Jin Wi; Ky Young Park (Journal of Plant Biology, 2015)

Nondestructive Spectroscopic and Imaging Techniques for Quality Evaluation and Assessment of Fish and Fish Products - Hong-Ju He; Di Wu; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2015)

Docetaxel Modulates the Delayed Rectifier Potassium Current (I K) and ATP-Sensitive Potassium Current (I KATP) in Human Breast Cancer Cells - Tao Sun; Zhi-Guo Song; Da-Qing Jiang; Hong-Guang Nie; Dong-Yun Han (The Journal of Membrane Biology, 2015)

Comparison of biological characteristics of H9N2 avian influenza viruses isolated from different hosts - Yinbiao Zhu; Yang Yang; Wei Liu; Xin Liu; Da Yang; Zhihao Sun; Yong Ju; Sujuan Chen; Daxin Peng; Xiufan Liu (Archives of Virology, 2015)

Enhancement of Food Processes by Ultrasound: A Review - Yang Tao; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2015)

17β-Estradiol protects against apoptosis induced by interleukin-1β in rat nucleus pulposus cells by down-regulating MMP-3 and MMP-13 - Si-Dong Yang; Da-Long Yang; Ya-Peng Sun; Bao-Lin Wang; Lei Ma; Shi-Qing Feng; Wen-Yuan Ding (Apoptosis, 2015)

Historical development and future perspectives of Environmental Specimen Bank in China: a mini review - Fang Qiu; Xiang-Zhou Meng; Yan-Ling Qiu; Qing-Hui Huang; Ying Liu; Ling-Ling Wu; Qian-Fen Xiao; Ya-Jie Sun; Rui Wang; Yi-Hui Zhou; Zhen-Yang Yu; Da-Qiang Yin; et al. (Environmental Science and Pollution Research, 2015)

Profiling of mitochondrial proteome in wheat roots - Da-Eun Kim; Swapan Kumar Roy; Abu Hena Mostafa Kamal; Kun Cho; Soo Jeong Kwon; Seong-Woo Cho; Chul-Soo Park; Jong-Soon Choi; Setsuko Komatsu; Moon-Soon Lee; Sun-Hee Woo (Molecular Biology Reports, 2014)

Alterations of chemical composition, construction cost and payback time in needles of Masson pine (Pinus massoniana L.) trees grown under pollution - Nan Liu; Lan-Lan Guan; Fang-Fang Sun; Da-Zhi Wen (Journal of Plant Research, 2014)

17β-Estradiol protects against apoptosis induced by levofloxacin in rat nucleus pulposus cells by upregulating integrin α2β1 - Si-Dong Yang; Lei Ma; Ti-Xin Gu; Wen-Yuan Ding; Feng Zhang; Yong Shen; Ying-Ze Zhang; Da-Long Yang; Di Zhang; Ya-Peng Sun; Yan-Li Song (Apoptosis, 2014)

Embelin Suppresses Dendritic Cell Functions and Limits Autoimmune Encephalomyelitis Through the TGF-β/β-catenin and STAT3 Signaling Pathways - Zhenyi Xue; Zhenzhen Ge; Kai Zhang; Rui Sun; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; Wen Li; Da Zhang; Junwei Hao; Yurong Da; et al. (Molecular Neurobiology, 2014)

Expressions of ER, PR, HER-2, COX-2, and VEGF in Primary and Relapsed/Metastatic Breast Cancers - Li Sun; Da-hai Yu; San-Yuan Sun; Shi-Chao Zhuo; Su-sheng Cao; Ling Wei (Cell Biochemistry and Biophysics, 2014)

Construction, characterization and expression of full length cDNA clone of sheep YAP1 gene - Wei Sun; Da Li; Rui Su; Hassan H. Musa; Ling Chen; Hong Zhou (Molecular Biology Reports, 2014)

An improved method to extract DNA from mango Mangifera indica - Mohammad S. Uddin; Wenli Sun; Xinhua He; Jaime A. Teixeira da Silva; Qi Cheng (Biologia, 2014)

Advances in Wine Aging Technologies for Enhancing Wine Quality and Accelerating Wine Aging Process - Yang Tao; Juan Francisco García; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2014)

Anti-tumor activity of the X-linked inhibitor of apoptosis (XIAP) inhibitor embelin in gastric cancer cells - Da-Guang Wang; Ya-Bin Sun; Fei Ye; Wei Li; Punyaram Kharbuja; Ling Gao; David Y. Zhang; Jian Suo (Molecular and Cellular Biochemistry, 2014)

Attachment of Acidithiobacillus ferrooxidans onto different solid substrates and fitting through Langmuir and Freundlich equations - Le-Xian Xia; Zhen Shen; Tomas Vargas; Wen-Juan Sun; Ren-Man Ruan; Zhen-Da Xie; Guan-Zhou Qiu (Biotechnology Letters, 2013)

Climate change in the 21st century simulated by HadGEM2-AO under representative concentration pathways - Hee-Jeong Baek; Johan Lee; Hyo-Shin Lee; Yu-Kyung Hyun; ChunHo Cho; Won-Tae Kwon; Charline Marzin; Sun-Yeong Gan; Min-Ji Kim; Da-Hee Choi; Jonghwa Lee; Jaeho Lee; et al. (Asia-Pacific Journal of Atmospheric Sciences, 2013)

Effects of rainfall and manure application on phosphorus leaching in field lysimeters during fallow season - Qiao Yun Xue; Pei Bin Dai; Da Sheng Sun; Cheng Liang Sun; Ling Yu Qi; Anne Ostermann; Yao He; Xian Yong Lin (Journal of Soils and Sediments, 2013)

A Novel Homogeneous Time-Resolved Fluoroimmunoassay for Carcinoembryonic Antigen Based on Water-Soluble Quantum Dots - Zhen-Hua Chen; Ying-Song Wu; Mei-Jun Chen; Jing-Yuan Hou; Zhi-Qi Ren; Da Sun; Tian-Cai Liu (Journal of Fluorescence, 2013)

The detection of QTLs controlling bacterial wilt resistance in tobacco (N. tabacum L.) - Yi-liang Qian; Xin-sheng Wang; Da-zhou Wang; Li-na Zhang; Chao-long Zu; Zheng-liang Gao; Hong-jun Zhang; Zhi-yong Wang; Xue-yong Sun; Da-nian Yao (Euphytica, 2013)

The association between a single nucleotide polymorphism rs11966200 in MHC region and clinical features of generalized vitiligo in Chinese Han population - Jin Tang; Jian Lan Liu; Cheng Zhang; Da Yan Hu; Su Min He; Xian Bo Zuo; Pei Guang Wang; Liang Dan Sun; Xue Jun Zhang; Sen Yang (Molecular Biology Reports, 2013)

Down-regulation of eIF5A-2 prevents epithelial-mesenchymal transition in non-small-cell lung cancer cells - Guo-dong Xu; Xin-bao Shi; Le-bo Sun; Qing-yun Zhou; Da-wei Zheng; Huo-shun Shi; Yong-liang Che; Zi-shan Wang; Guo-feng Shao (Journal of Zhejiang University-SCIENCE B, 2013)

Impact of manure application on forms and quantities of phosphorus in a Chinese Cambisol under different land use - Qiao Yun Xue; Imran Haider Shamsi; Da Sheng Sun; Anne Ostermann; Qi Chun Zhang; Yong Song Zhang; Xian Yong Lin (Journal of Soils and Sediments, 2013)

Polymorphisms of the Interleukin 6 gene contribute to cervical cancer susceptibility in Eastern Chinese women - Ting-Yan Shi; Mei-Ling Zhu; Jing He; Meng-Yun Wang; Qiao-Xin Li; Xiao-Yan Zhou; Meng-Hong Sun; Zhi-Ming Shao; Ke-Da Yu; Xi Cheng; Xiaohua Wu; Qingyi Wei (Human Genetics, 2013)

Computational Fluid Dynamics in the Design and Analysis of Thermal Processes: A Review of Recent Advances - Tomás Norton; Brijesh Tiwari; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2013)

HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Increased Expression of TRPV1 in the Cortex and Hippocampus from Patients with Mesial Temporal Lobe Epilepsy - Fei-Ji Sun; Wei Guo; Da-Hai Zheng; Chun-Qing Zhang; Song Li; Shi-Yong Liu; Qing Yin; Hui Yang; Hai-Feng Shu (Journal of Molecular Neuroscience, 2013)

Characterization, genomic organization, and expression profiles of MyD88, a key adaptor molecule in the TLR signaling pathways in miiuy croaker (Miichthys miiuy) - Da Tang; Yunhang Gao; Rixin Wang; Yuena Sun; Tianjun Xu (Fish Physiology and Biochemistry, 2012)

Principles and Applications of Hyperspectral Imaging in Quality Evaluation of Agro-Food Products: A Review - Gamal Elmasry; Mohammed Kamruzzaman; Da-Wen Sun; Paul Allen (Critical Reviews in Food Science and Nutrition, 2012)

Application of Hyperspectral Imaging in Food Safety Inspection and Control: A Review - Yao-Ze Feng; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2012)

Vacuum Cooling of Meat Products: Current State-of-the-Art Research Advances - Chaohui Feng; Liana Drummond; Zhihang Zhang; Da-Wen Sun; Qijun Wang (Critical Reviews in Food Science and Nutrition, 2012)

Effects of drought stress on phosphorus and potassium uptake dynamics in summer maize (Zea mays) throughout the growth cycle - Ti-Da Ge; Ning-Bo Sun; Li-Ping Bai; Chen-Li Tong; Fang-Gong Sui (Acta Physiologiae Plantarum, 2012)

Multi-environment mapping and meta-analysis of 100-seed weight in soybean - Ya-nan Sun; Jun-bo Pan; Xiang-lin Shi; Xiang-yu Du; Qiong Wu; Zhao-ming Qi; Hong-wei Jiang; Da-wei Xin; Chun-yan Liu; Guo-hua Hu; Qing-shan Chen (Molecular Biology Reports, 2012)

Changes in physiology and protein abundance in salt-stressed wheat chloroplasts - Abu Hena Mostafa Kamal; Kun Cho; Da-Eun Kim; Nobuyuki Uozumi; Keun-Yook Chung; Sang Young Lee; Jong-Soon Choi; Seong-Woo Cho; Chang-Seob Shin; Sun Hee Woo (Molecular Biology Reports, 2012)

Meat Quality Evaluation by Hyperspectral Imaging Technique: An Overview - Gamal Elmasry; Douglas F. Barbin; Da-Wen Sun; Paul Allen (Critical Reviews in Food Science and Nutrition, 2012)

Peroxisome Proliferator-Activated Receptor Gamma (PPAR-γ) and Neurodegenerative Disorders - Yu-Chang Chen; Jui-Sheng Wu; Hsin-Da Tsai; Chien-Yu Huang; Jin-Jer Chen; Grace Y. Sun; Teng-Nan Lin (Molecular Neurobiology, 2012)

Characterization and expression pattern of KIFC1-like kinesin gene in the testis of the Macrobrachium nipponense with discussion of its relationship with structure lamellar complex (LCx) and acroframosome (AFS) - Yan-Ting Wang; Huan Mao; Cong-Cong Hou; Xiao Sun; Da-Hui Wang; Hong Zhou; Wan-Xi Yang (Molecular Biology Reports, 2012)

Recognition of early Carboniferous alkaline granite in the southern Altai orogen: post-orogenic processes constrained by U–Pb zircon ages, Nd isotopes, and geochemical data - Ying Tong; Tao Wang; Wolfgang Siebel; Da-Wei Hong; Min Sun (International Journal of Earth Sciences, 2012)

Production of cloned transgenic cow expressing omega-3 fatty acids - Xia Wu; Hongsheng Ouyang; Biao Duan; Daxin Pang; Li Zhang; Ting Yuan; Lian Xue; Daibang Ni; Lei Cheng; Shuhua Dong; Zhuying Wei; Lin Li; et al. (Transgenic Research, 2012)

Secretory expression and characterization of a soluble laccase from the Ganoderma lucidum strain 7071-9 in Pichia pastoris - Jing Sun; Ri-He Peng; Ai-Sheng Xiong; Yongsheng Tian; Wei Zhao; Hu Xu; Da-Tong Liu; Jian-Min Chen; Quan-Hong Yao (Molecular Biology Reports, 2012)

Functional analysis of Waardenburg syndrome-associated PAX3 and SOX10 mutations: report of a dominant-negative SOX10 mutation in Waardenburg syndrome type II - Hua Zhang; Hongsheng Chen; Hunjin Luo; Jing An; Lin Sun; Lingyun Mei; Chufeng He; Lu Jiang; Wen Jiang; Kun Xia; Jia-Da Li; Yong Feng (Human Genetics, 2012)

Genetic transformation of Populus tomentosa to improve salt tolerance - Ningxia Du; Xin Liu; Yun Li; Shouyi Chen; Jinsong Zhang; Da Ha; Wenguang Deng; Chunkui Sun; Yingzhi Zhang; Paula M. Pijut (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

The effect of sevoflurane on the expression of M1 acetylcholine receptor in the hippocampus and cognitive function of aged rats - Sheng Peng; Yan Zhang; Guo-Jun Li; Deng-Xin Zhang; Da-Peng Sun; Qiang Fang (Molecular and Cellular Biochemistry, 2012)

Phylogenic analysis of Chinese Leishmania isolates based on small subunit ribosomal RNA (SSU rRNA) and 7 spliced leader RNA (7SL RNA) - Wang Guan; De-Ping Cao; Ke sun; Jia-nan Xu; Jun-rong Zhang; Da-Li Chen; Jian-Ping Chen (Acta Parasitologica, 2012)
The leishmaniases are zoonotic diseases caused by protozoan parasites of the genus Leishmania. Leishmaniases are still endemic in China, especially in the west and northwest froniter regions. To revalue the preliminary phylogenetic results of Chinese Leishmania isolates, we amplified partial fragment of small subunit ribosomal RNA (SSU rRNA) and 7 spliced leader RNA (7SL RNA), then tested the phylogenetic relationships among Chinese Leishmania isolates and their relatives by analyzing SSU rRNA gene sequences and 7SL RNA gene sequences. 19 SSU RNA sequences and 9 7SL RNA sequences were obtained in our study, then analyzed with 42 SSU RNA sequences and 32 7SL RNA sequences retrieved from Genbank, respectively. In the Bayesian analysis of the SSU RNA gene, the isolate MHOM/CN/93/GS7 and the isolate IPHL/CN/77/XJ771 are members of Leishmania donovani complex, while the isolate MHOM/CN/84/JS1 clustered with Leishmania tropica. The other 11 Chinese Leishmania isolates (MHOM/CN/90/WC, MCAN/CN/90/SC11, MHOM/CN/80/XJ801, MHOM/CN/85/GS4, MHOM/CN/84/SD1, MCAN/CN/86/SC7, MHOM/CN/54/#3, MHOM/CN/83/GS2, MHOM/CN/90/SC10H2, MHOM/CN/89/GS6 and MHOM/CN/ 89/GS5) form an unclassified group, defined as Leishmania sp., and the most relative species to this group is L. tarentolae. In the Bayesian analysis of the 7SL RNA gene, 9 Chinese Leishmania isolates also formed an unclassified group with L. tarentolae, including canine isolate 10, MHOM/CN/85/GS4, MHOM/CN/84/SD1, MCAN/CN/86/SC7, MHOM/CN/54/#3, MHOM/ CN/83/GS2, MHOM/CN/90/SC10H2, MHOM/CN/89/GS6 and MHOM/CN/89/GS5. We concluded that: (1) Chinese Leishmania isolates are non-monophyly group; (2) an unclassified group may exist in China, and the most relative species to this group is L. tarentolae; (3) MHOM/CN/84/JS1, which was previously assigned as L. donovani, was most genetically related to L. tropica strain MHOM/SU/74/K27.

Evaluation of Left Ventricular Twist in Acute Myocardial Infarction Patients Using Speckle Tracking Imaging - Da-lin Jia; Chun-yan Ma; Shuang Liu; Lu-fan Sun (Cell Biochemistry and Biophysics, 2011)

Clostridium beijerinckii mutant obtained by atmospheric pressure glow discharge producing high proportions of butanol and solvent yields - Ting Guo; Yan Tang; Yong-lan Xi; Ai-yong He; Bai-jun Sun; Hao Wu; Da-feng Liang; Min Jiang; Ping-kai Ouyang (Biotechnology Letters, 2011)

Ototoxic destruction by co-administration of kanamycin and ethacrynic acid in rats - Hong Liu; Da-lian Ding; Hai-yan Jiang; Xue-wen Wu; Richard Salvi; Hong Sun (Journal of Zhejiang University-SCIENCE B, 2011)

Retinol, vitamins A, C, and E and breast cancer risk: a meta-analysis and meta-regression - Hu Fulan; Jiang Changxing; Wang Yi Baina; Zhang Wencui; Lin Chunqing; Wang Fan; Li Dandan; Sun Dianjun; Wang Tong; Pang Da; Zhao Yashuang (Cancer Causes & Control, 2011)

The Protective Effect of ENA Actimineral Resource A on CCl4-Induced Liver Injury in Rats - Il-Hwa Hong; Hoon Ji; Sung-Yong Hwa; Won-Il Jeong; Da-Hee Jeong; Sun-Hee Do; Ji-Min Kim; Mi-Ran Ki; Jin-Kyu Park; Moon-Jung Goo; Ok-Kyung Hwang; Kyung-Sook Hong; et al. (Marine Biotechnology, 2011)

Characteristics of CO2 release from forest soil in the mountains near Beijing - Xiang Yang Sun; Cheng Da Gao; Lin Zhang; Su Yan Li; Yong Qiao (Environmental Monitoring and Assessment, 2011)

Proteomics Analysis of Embryo and Endosperm from Mature Common Buckwheat Seeds - Abu Hena Mostafa Kamal; Ill-Dong Jang; Da-Eun Kim; Tatsuro Suzuki; Keun-Yook Chung; Jong-Soon Choi; Moon-Soon Lee; Cheol-Ho Park; Sang-Un Park; Seong Hee Lee; Heon Sang Jeong; Sun-Hee Woo (Journal of Plant Biology, 2011)

Cerebellar Long-term Depression is Deficient in Niemann–Pick Type C Disease Mice - Cheng-Long Sun; Li-Da Su; Qiong Li; Xin-Xin Wang; Ying Shen (The Cerebellum, 2011)

The effect of sevoflurane anesthesia on cognitive function and the expression of Insulin-like Growth Factor-1 in CA1 region of hippocampus in old rats - Sheng Peng; Yan Zhang; Da-Peng Sun; Deng-Xin Zhang; Qiang Fang; Guo-Jun Li (Molecular Biology Reports, 2011)

Rapid simultaneous screening of seven clinically important enteric pathogens using a magnetic bead based DNA microarray - Hong Sun; Qiu-Hua Mo; Ji-Can Lin; Ze Yang; Cheng-Ning Tu; Da-Yong Gu; Lei Shi; Wei-Ping Lu (World Journal of Microbiology and Biotechnology, 2011)

The mixture of procyanidins extracted from the lotus seed pod and bilobalide ameliorates scopolamine-induced memory impairment in mice - Li Zhang; Ji-Qu Xu; Shuang Rong; Bi-Jun Xie; Zhi-Da Sun; Yun-Jian Zhang; Lie-Gang Liu (Neuroscience Bulletin, 2009)

Concentrations of sulphur and heavy metals in needles and rooting soils of Masson pine (Pinus massoniana L.) trees growing along an urban–rural gradient in Guangzhou, China - Fang Fang Sun; Da Zhi Wen; Yuan Wen Kuang; Jiong Li; Ji Guang Zhang (Environmental Monitoring and Assessment, 2009)

Lactational coumestrol exposure increases ovarian apoptosis in adult rats - Hyun-Ju Moon; Ji Hyun Seok; Soon Sun Kim; Gyu Seek Rhee; Rhee Da Lee; Jun Young Yang; Soo Yeong Chae; Seung Hee Kim; Ji Young Kim; Jin-Yong Chung; Jong-Min Kim; Soo Youn Chung (Archives of Toxicology, 2009)

Effect of the untranslated region and signal peptide sequence of the insecticidal gene from Pseudomonas pseudoalcaligenes on the activity of its expression products in tobacco - Min Huang; Da-Xu Li; Wen-Liang Xiang; Hao Chen; Jian-Hua Guo; Jian Zhao; Jie Zhang; Zhi-Rong Yang; Qun Sun (World Journal of Microbiology and Biotechnology, 2009)

Changes in estrogen receptor-α variant (ER-α36) expression during mouse ovary development and oocyte meiotic maturation - Bao-Zeng Xu; Sheng-Li Lin; Mo Li; Jia-Qiao Zhu; Sen Li; Ying-Chun Ouyang; Da-Yuan Chen; Qing-Yuan Sun (Histochemistry and Cell Biology, 2009)

Elevational patterns of species richness and endemism for some important taxa in the Hengduan Mountains, southwestern China - Da-Cai Zhang; Yong-Hong Zhang; David E. Boufford; Hang Sun (Biodiversity and Conservation, 2009)

Comparison of base composition and codon usage in insect mitochondrial genomes - Zheng Sun; Dong-Guang Wan; Robert W Murphy; Liang Ma; Xian-Sheng Zhang; Da-Wei Huang (Genes & Genomics, 2009)

Comparative Physicochemical Characterization of Phospholipids Complex of Puerarin Formulated by Conventional and Supercritical Methods - Ying Li; Da-Jian Yang; Shi-Lin Chen; Si-Bao Chen; Albert Sun-Chi Chan (Pharmaceutical Research, 2008)

AICAR induces phosphorylation of AMPK in an ATM-dependent, LKB1-independent manner - Yan Sun; Katie E. Connors; Da-Qing Yang (Molecular and Cellular Biochemistry, 2007)

Genotypic Analysis of Multidrug-Resistant Mycobacterium tuberculosis Isolates Recovered From Central China - Shu-Lin Zhang; Hua Qi; Dun-Lian Qiu; Da-Xu Li; Jie Zhang; Chang-Mei Du; Guo-Bin Wang; Zhi-Rong Yang; Qun Sun (Biochemical Genetics, 2007)

Association of functional catechol O-methyl transferase (COMT) Val108Met polymorphism with smoking severity and age of smoking initiation in Chinese male smokers - Song Guo; Da Fang Chen; Dong Feng Zhou; Hong Qiang Sun; Gui Ying Wu; Colin N. Haile; Therese A. Kosten; Thomas R. Kosten; Xiang Yang Zhang (Psychopharmacology, 2007)

Effects of bio-active ceramic resources in cutaneous wound healing and the role of TGF-β signaling - Jae-Yong Chung; Sun Hee Do; Won-Il Jeong; Da-Hee Jeong; Sang-Joon Park; Mi-Ran Ki; Dong-Mi Kwak; Soon-Bok Kim; Kyu-Shik Jeong (Molecular and Cellular Biochemistry, 2007)

Up-regulation of Metabotropic glutamate receptor 3 (mGluR3) in rat fibrosis and cirrhosis model of persistent hypoxic condition - Sun Hee Do; Hae-Sun Yun; Won-Il Jeong; Da-Hee Jeong; Mi-Ran Ki; Jae-Yong Chung; Sang-Joon Park; Soon-Bok Kim; Kyu-Shik Jeong (Molecular and Cellular Biochemistry, 2007)

Computational analysis of genetic loci required for amphid structure and functions and their possibly corresponding microRNAs in C. elegans - Ya-Ou Hu; Yang Sun; Bo-Ping Ye; Da-Yong Wang (Neuroscience Bulletin, 2007)

Haplotype Frequency Distribution and Linkage Disequilibrium Analysis of Single Nucleotide Polymorphisms at the Human FMO3 Gene Locus - Da-Cheng Hao; Jie Sun; Bjarte Furnes; Daniel Schlenk; Zhen-Fang Hou; Ya-Ping Zhang; Sheng-Li Yang; Ling Yang (Biochemical Genetics, 2006)

Influx of extracellular Ca2+ involved in jasmonic-acid-induced elevation of [Ca2+]cyt and JR1 expression in Arabidopsis thaliana - Qing-Peng Sun; Yi Guo; Ying Sun; Da-Ye Sun; Xiao-Jing Wang (Journal of Plant Research, 2006)

Hg0 absorption in potassium persulfate solution - Qun-feng Ye; Cheng-yun Wang; Da-hui Wang; Guan Sun; Xin-hua Xu (Journal of Zhejiang University-SCIENCE B, 2006)

Alcohol-induced bone degradation and its early detection in the alcohol-fed castrated rats - Sun Hee Do; Won Il Jeong; Da Hee Jeong; Mi-Ran Ki; In-Seon Lee; Dong-Mi Kwak; Tae Hwan Kim; Yoo Kyeong Kim; Soon-Bok Kim; Kyu-Shik Jeong (Molecular and Cellular Biochemistry, 2006)

Characterization of a cDNA coding for an extracellular calmodulin-binding protein from suspension-cultured cells of Angelica dahurica - Guo-Hong Mao; Li-Xia Hou; Cun-Bao Ding; Su-Juan Cui; Da-Ye Sun (Planta, 2005)

Genetic analysis of four wild chum salmonOncorhynchus keta populations in China based on microsatellite markers - Jin-Ping Chen; Da-Jiang Sun; Chong-Zhi Dong; Bing Liang; Wen-Hua Wu; Shu-Yi Zhang (Environmental Biology of Fishes, 2005)

A taxonomic study ofNorbanus Walker (Hymenoptera: Pteromalidae) from China - Hui Xiao; Da-Wei Huang; Lei Sun (Phytoparasitica, 2005)

Cluster characterisation and temporal expression of porcine sarcomeric myosin heavy chain genes - Y. M. Sun; N. Da Costa; K. C. Chang (Journal of Muscle Research and Cell Motility, 2003)

Sequence Analysis of the Complete Genome of Rice Black-Streaked Dwarf Virus Isolated from Maize with Rough Dwarf Disease - Zhao-Hui Wang; Shou-Guo Fang; Jia-Ling Xu; Li-Ying Sun; Da-Wei Li; Jia-Lin Yu (Virus Genes, 2003)

Long-term cattle manure application in soil. II. Effect on soil microbial populations and community structure - J. A. Parham; S. P. Deng; H. N. Da; H. Y. Sun; W. R. Raun (Biology and Fertility of Soils, 2003)

Cloning and expression of soluble recombinant protein comprising the extracellular domain of the human type I interferon receptor 2c subunit (IFNAR-2c) in E. coli - Sun-Ok Yoon; Rosario D.C. Hirata; Ana C.R. da Silva; Nga Y. Nguyen; Mario H. Hirata (Biotechnology Letters, 2002)

Molecular and quantitative characterisation of the porcine embryonic myosin heavy chain gene - Y. M. Sun; N. da Costa; R. Birrell; A. L. Archibald; H. Alzuherri; K. C. Chang (Journal of Muscle Research and Cell Motility, 2001)

THE CULTURE OF FIBROBLASTS FROM DIAPHRAGM OF GIANT PANDA - Zhi-Ming Han; Da-Yuan Chen; Jin-Song Li; Qing-Yuan Sun; Peng-Yang Wang; Yang Huang; Jun Du (In Vitro Cellular & Developmental Biology - Animal, 2001)

The 5′-end of the porcine perinatal myosin heavy chain gene shows alternative splicing and is clustered with repeat elements - Nuno Da Costa; Nicolas Beuzen; Irene Johnston; Christine McGillivray; Yuh-man Sun; Kin Chow Chang (Journal of Muscle Research and Cell Motility, 2000)

Culture of skeletal muscle cells from giant panda - Ji-Long Liu; Yu-Cun Chen; Qing-Yuan Sun; Xiang-Fen Song; Da-Yuan Chen (In Vitro Cellular & Developmental Biology - Animal, 1999)

Hair concentrations of calcium, iron, and zinc in pregnant women and effects of supplementation - Po Lau Leung; Han Ming Huang; Da Ze Sun; MeI Guang Zhu (Biological Trace Element Research, 1999)

Hair and serum calcium, iron, copper, and zinc levels during normal pregnancy at three trimesters - Han Ming Huang; Po Lau Leung; Da Ze Sun; Mei Guang Zhu (Biological Trace Element Research, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)